Water-soluble fibers having post-processing modifications and articles containing same

By treating fibers with hydrolyzable polymers using a hydrolytic agent solution, the method addresses the challenge of forming fibers with desired solubility profiles, achieving enhanced solubility control and improved fiber properties.

JP7659577B2Active Publication Date: 2025-04-09MONOSOL LLC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2022572333
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-06-02
Filing Date
2021-06-02
Publication Date
2025-04-09
Estimated Expiration
2041-06-02

AI Technical Summary

Technical Problem

Existing water-soluble fibers, particularly those formed from polymers with a desired degree of hydrolysis and polymerization for specific solubility profiles, often fail to withstand the fiber-making process, limiting the availability of fibers with desired properties.

Method used

A method is introduced to treat fibers containing hydrolyzable polymers, such as those with vinyl acetate or vinyl alcohol moieties, by increasing the degree of hydrolysis through contact with a hydrolytic agent solution. This can be done by mixing the fibers with the solution or by contacting the fiber surface with the solution, allowing for the modification of the solubility profile after fiber formation.

Benefits of technology

The method enables the creation of fibers with tailored solubility profiles, including core-sheath structures and gradient profiles, which are not otherwise available. This approach enhances the control over the microstructure and solubility of the fibers, improving their chemical compatibility and absorbent capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007659577000020
    Figure 0007659577000020
  • Figure 0007659577000021
    Figure 0007659577000021
  • Figure 0007659577000022
    Figure 0007659577000022
Patent Text Reader

Abstract

The fiber has a surface region and an internal region, and the fiber includes a polymer containing at least one of vinyl acetate or vinyl alcohol moieties, and the fiber has a cross-section including an internal region containing a polymer having a first degree of hydrolysis and a surface region containing a polymer having a second degree of hydrolysis higher than the first degree of hydrolysis. The present disclosure generally relates to water-soluble fibers. More specifically, the present disclosure relates to water-soluble fibers containing polyvinyl alcohol that has been modified after fiber formation by hydrolysis.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Priority claims and cross-references This application claims the benefit of U.S. Provisional Patent Application No. 63 / 033,601, filed June 2, 2020, which is expressly incorporated by reference herein in its entirety.

[0002] Field The present disclosure relates generally to water soluble fibers. More particularly, the present disclosure relates to water soluble fibers comprising polyvinyl alcohol that has been modified after fiber formation by hydrolysis. [Background technology]

[0003] background Nonwoven webs are traditionally used in many single-use consumer products, including personal care products such as bandages, diaper constructions, feminine care and adult incontinence, as well as single-use wipes in industrial, medical, cleaning and personal / baby care applications. The traditional chemicals used in such products, such as viscose, polypropylene or cotton fibers, are generally non-persistent, non-biodegradable, potential causative agents of microplastics, and are often disposed of incorrectly, such as by being flushed down the toilet and entering wastewater treatment and sewage systems. Known wipes must be disposed of in the trash, which may not be hygienic or convenient for users. Improper disposal of these items can result in clogging of home plumbing and the formation of "fatbergs," or agglomerates of solidified masses of biodegradable and non-biodegradable materials composed of solidified grease and cooking fats and disposable wipes, in residential and municipal wastewater systems, which may contribute to marine microplastics and require changes in consumer behavior.

[0004] The solubility profile and mechanism of a water-soluble article (e.g., hot water solubility vs. cold water solubility, easy solubility vs. delayed solubility or extended release) may need to be adjusted based on the end use of the article. For articles that include water-soluble fibers, the solubility profile and mechanism are generally varied by selecting a fiber-forming material with a degree of hydrolysis or degree of polymerization. However, the degree of hydrolysis and degree of polymerization of the fiber-forming material also affect the ability of the fiber-forming material to form fibers. Thus, fibers formed with a particular polymer with the desired degree of hydrolysis and degree of polymerization that results in fibers with a desired solubility profile may not be available because the fiber-forming material may not be able to withstand the fiber making process. Summary of the Invention [Means for solving the problem]

[0005] overview One aspect of the present disclosure provides a method of treating a fiber comprising a hydrolyzable polymer, such as a polymer comprising at least one of a vinyl acetate moiety or a vinyl alcohol moiety, having a degree of hydrolysis less than 100%, comprising mixing the fiber and a hydrolyzing agent solution to increase the degree of hydrolysis of at least a portion of the polymer in the fiber.

[0006] Another aspect of the present disclosure provides a method of treating a fiber comprising a hydrolyzable polymer, such as a polymer comprising at least one of a vinyl acetate moiety or a vinyl alcohol moiety, having a degree of hydrolysis less than 100%, comprising contacting a surface of the fiber with a hydrolyzing agent solution to increase the degree of hydrolysis of the polymer in a region of the fiber comprising at least the surface of the fiber.

[0007] Another aspect of the present disclosure provides fibers prepared according to the methods of the present disclosure.

[0008] Another aspect of the present disclosure provides a fiber having a surface region and an interior region, the fiber comprising a hydrolyzable polymer, the polymer comprising at least one of a vinyl acetate moiety or a vinyl alcohol moiety, and having a cross-section characterized by the polymer in the surface region having a higher degree of hydrolysis than the polymer in the interior region. Optionally, the cross-section of the fiber is characterized by an increasing gradient of the degree of hydrolysis of the polymer from the interior region to the surface region.

[0009] Another aspect of the present disclosure provides a fiber comprising a cross-section characterized by a core-sheath structure, also referred to as a core-shell structure, having a first core region comprising a hydrolyzable polymer, such as a polymer comprising at least one of a vinyl acetate moiety or a vinyl alcohol moiety, having a degree of hydrolysis less than 100%, and a second shell region comprising such a polymer having a higher degree of hydrolysis than the polymer of the first region.

[0010] Another aspect of the present disclosure provides a method of treating a nonwoven web comprising a plurality of fibers comprising a hydrolyzable polymer, such as a polymer comprising at least one of a vinyl acetate moiety or a vinyl alcohol moiety, having a degree of hydrolysis less than 100%, comprising contacting at least a portion of the nonwoven web with a hydrolyzing agent solution to increase the degree of hydrolysis of the polymer of the fibers of a portion of the nonwoven web.

[0011] Another aspect of the present disclosure provides a nonwoven web treated according to the method of the present disclosure.

[0012] Another aspect of the present disclosure provides a nonwoven web comprising the fibers of the present disclosure.

[0013] Another aspect of the present disclosure provides a multi-layer nonwoven web comprising a first layer comprising a nonwoven web treated according to the method of the present disclosure or a nonwoven web comprising fibers of the present disclosure.

[0014] Another aspect of the present disclosure provides a pouch comprising a nonwoven web according to the present disclosure in the form of a pouch defining an interior pouch volume.

[0015] Another aspect of the present disclosure provides a sealing article comprising a nonwoven web of the present disclosure.

[0016] Another aspect of the present disclosure provides a flushable article comprising a nonwoven web of the present disclosure.

[0017] Another aspect of the present disclosure provides a wearable absorbent article comprising an absorbent core having a wearer-facing surface and an outer surface, and a liquid acquisition layer, the liquid acquisition layer comprising the nonwoven web of the present disclosure.

[0018] Further aspects and advantages will become apparent to those skilled in the art from a consideration of the following detailed description. While the fibers, nonwoven webs, pouches, articles, and methods of making them are capable of embodiment in a variety of forms, the following description herein includes specific embodiments with the understanding that the present disclosure is illustrative and is not intended to limit the invention to the specific embodiments described herein.

[0019] To facilitate a further understanding of the present disclosure, 14 figures are attached hereto. [Brief description of the drawings]

[0020] [Figure 1] 1A-1D show cross sections of various fiber geometries, with lines indicating fiber diameters.

[0021] [Figure 2A] FIG. 2A shows the cross-section of a round fiber characterized by a core-sheath structure, where the polymer of the sheath 202 has a higher degree of hydrolysis than the polymer of the core 201.

[0022] [Figure 2B] FIG. 2B shows a cross-section of a round fiber characterized by an increasing gradient of the degree of hydrolysis of the polymer from an interior region 301 to a surface region 302.

[0023] [Figure 2C]FIG. 2C shows the cross-section of a round fiber characterized by the polymer having the same degree of hydrolysis across the cross-section.

[0024] [Diagram 3] FIG. 3 shows a cross-section of a round fiber having a first core region 401, a second sheath or shell region 402, and two intermediate regions 403A and 403B disposed between the first and second regions, where the cross-section of the fiber is characterized by an increasing gradient of the degree of hydrolysis of the polymer from the first region to the second region.

[0025] [Figure 4] FIG. 4 is a diagram of a wire frame cage (shown open at the top to better show the water-soluble pouch contained therein) for use in the liquid release tests described herein.

[0026] [Diagram 5] FIG. 5 shows an apparatus for conducting liquid release tests that includes a beaker mounted on a stand, a stand that holds a rod for lowering a cage into the beaker, and the rod can be secured by a collar having a set screw (not shown).

[0027] [Figure 6A] FIG. 6A is a photomicrograph image of a nonwoven web of the present disclosure having a softness rating of 1.

[0028] [Figure 6B] FIG. 6B is a photomicrograph image of a nonwoven web of the present disclosure having a softness rating of 5.

[0029] [Figure 7] FIG. 7 shows a nonwoven web with the outer surfaces of the web designated 100 and 101.

[0030] [Figure 8]FIG. 8 shows the instrument setup used to measure shrinkage along the longitudinal axis of the fiber by contacting the fiber with water at temperatures ranging from 10° C. to 23° C.

[0031] [Figure 9] FIG. 9 shows the ATR-FTIR results of the fiber (Fiber A) before and after treating the fiber with 0.05 M base (NaOH or KOH) in solvent (methanol or 10% methanol / 90% hexane), respectively, at 40° C. for 1 min.

[0032] [Figure 10] FIG. 10 shows the fiber shrinkage along the longitudinal axis of different fibers having different degrees of hydrolysis upon contacting the fibers with water at temperatures of 10° C. or 23° C.

[0033] [Figure 11] FIG. 11 shows the time to rupture (seconds) and disintegration time (seconds) of a nonwoven web having an exemplary fiber (Fiber A) before and after exposure to heated methanol.

[0034] [Figure 12] FIG. 12 shows the rupture time (seconds) of nonwoven webs containing fibers with different degrees of hydrolysis.

[0035] [Figure 13] FIG. 13 shows the disintegration time (seconds) of nonwoven webs containing fibers with different degrees of hydrolysis.

[0036] [Figure 14] FIG. 14 shows ATR-FTIR results for the interior ("inner") and surface ("outer") regions of an exemplary block comprising a copolymer of vinyl acetate and vinyl alcohol. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0037] Detailed Description As described in the Background, fibers formed from a particular polymer with the desired degree of hydrolysis and polymerization that results in a fiber with a desired solubility profile may not be available because the fiber-forming material may not survive the fiber fabrication process. It would therefore be advantageous to provide a method for modifying the solubility profile of a fiber after fiber formation to obtain a solubility profile that is otherwise unavailable.

[0038] Additionally, since the solubility profile of the fibers or water-soluble articles prepared therefrom may be engineered for a particular end use, it would be advantageous to provide a method for modifying the solubility profile of the fibers after fiber formation for inventory control. The ability to modify the degree of hydrolysis, and therefore the solubility profile of the fibers, post-processing would advantageously allow for a variety of fiber types to be obtained starting with one or more fiber types.

[0039] Provided herein is a method for treating a fiber or its surface by contacting the fiber or its surface with a hydrolyzing agent solution to increase the degree of hydrolysis of the hydrolyzing polymer that constitutes the fiber or its surface. The method of the present disclosure can advantageously provide fibers with an increased average degree of hydrolysis of the hydrolyzing polymer that constitutes the fiber, fibers with a core-sheath structure, where the polymer in the sheath or surface region has a higher degree of hydrolysis than the polymer in the core or inner region, and / or fibers with an increasing gradient of the degree of hydrolysis of the polymer that constitutes the fiber from the inner region to the surface region. Optionally, the hydrolyzing polymer comprises at least one of a vinyl acetate moiety or a vinyl alcohol moiety. As used herein, "at least one of a vinyl acetate moiety or a vinyl alcohol moiety" and "vinyl acetate moiety and / or vinyl alcohol moiety" describe examples of hydrolyzing polymers that comprise only vinyl acetate moieties, only vinyl alcohol moieties, or both vinyl acetate moieties and vinyl alcohol moieties. In an embodiment, the fibers of the present disclosure are water-soluble before treatment with a hydrolyzing agent solution and remain water-soluble after treatment with a hydrolyzing agent solution. In an embodiment, the fibers of the present disclosure are cold water soluble before treatment with the hydrolysis agent solution and hot water soluble after treatment with the hydrolysis agent solution. In an embodiment, the fibers of the present disclosure are cold water soluble before treatment with the hydrolysis agent solution and at least a portion of the outer surface of the fibers is hot water soluble after treatment with the hydrolysis agent solution. In an embodiment, the fibers are not water soluble before treatment with the hydrolysis agent solution and the fibers are water soluble after treatment with the hydrolysis agent solution. In an embodiment, the fibers are not water soluble after mixing the fibers with the hydrolysis agent.

[0040] The methods and fibers of the present disclosure may provide one or more benefits including, but not limited to, providing control over the microstructure of the fiber, altering the solubility profile and / or mechanism of the fiber, improving the chemical compatibility of the fiber to chemical agents, increasing the absorption capacity of the fiber, increasing and / or controlling the loading of active materials within the fiber, and / or providing control over the release of compositions or active materials from within the fiber.

[0041] As used herein, unless otherwise specified, the term "water-soluble" refers to any nonwoven web or article containing the same having a dissolution time of 300 seconds or less at a particular temperature as determined according to MSTM-205 as set forth herein, or any fiber having a complete dissolution time of less than 30 seconds at a particular temperature as determined according to the method for determining single fiber solubility disclosed herein. For example, the solubility parameter may be a property of a nonwoven web having a thickness of 6 mils (about 152 μm) or an article made therefrom. The dissolution time of the nonwoven web may be 200 seconds or less, 100 seconds or less, 60 seconds or less, or 30 seconds or less at temperatures of about 100°C, about 90°C, about 80°C, about 70°C, about 60°C, about 50°C, about 40°C, about 20°C, or about 10°C, as appropriate. In embodiments where no dissolution temperature is specified, the water-soluble nonwoven web has a dissolution time of 300 seconds or less at a temperature of about 100°C or less. The fibers may have a complete dissolution time of 30 seconds or less at temperatures of about 100°C, about 90°C, about 80°C, about 70°C, about 60°C, about 50°C, about 40°C, about 20°C, or about 10°C. As used herein, a fiber is "insoluble," "water-insoluble," or "water-insoluble" if it has a complete dissolution time of more than 30 seconds at a particular temperature according to the method of determining single fiber solubility disclosed herein. In embodiments where a complete dissolution temperature is not specified, a water-soluble fiber has a complete dissolution time of 30 seconds or less at a temperature of about 100°C or less, and a water-insoluble fiber has a complete dissolution time of more than 30 seconds at a temperature of about 100°C or less. As used herein, unless otherwise specified, the term "cold water-soluble" refers to any nonwoven web having a dissolution time of 300 seconds or less at 10°C as determined according to MSTM-205. For example, the dissolution time can be 200 seconds or less, 100 seconds or less, 60 seconds or less, or 30 seconds, as appropriate, at 10° C. As used herein, unless otherwise specified, the term "cold water soluble" in reference to fibers refers to fibers that have a complete dissolution time of 30 seconds or less at a temperature of 10° C. or less, according to the method for determining single fiber solubility disclosed herein.

[0042] As used herein, unless otherwise specified, the term "water-dispersible" refers to a nonwoven web or article containing the same that physically separates into smaller constituent pieces upon immersion in water at a particular temperature. The smaller pieces may or may not be visible to the naked eye, may or may not remain suspended in water, and may or may not ultimately dissolve. In embodiments where a dispersion temperature is not specified, the nonwoven web or pouch disintegrates in 300 seconds or less at a temperature of about 100°C or less according to MSTM-205. For example, the disintegration time may be 200 seconds or less, 100 seconds or less, 60 seconds or less, or 30 seconds or less at a temperature of about 80°C, about 70°C, about 60°C, about 50°C, about 40°C, about 20°C, or about 10°C according to MSTM-205, as appropriate. For example, such dispersion parameters may be properties of a nonwoven web or article made therefrom having a thickness of 6 mils (about 152 μm).

[0043] As used herein, the term "flushable" refers to an article, e.g., a nonwoven web or pouch, that is dispersible in an aqueous environment, e.g., a sewer system, such that disposal of the web(s) or pouch(es) does not result in such article remaining in the plumbing of the water supply and drainage system or accumulating over time to cause blockage of such plumbing. The INDA / EDANA standard for flushability requires that greater than 95% of the starting material must pass through a 12.5 mm sieve after a 60 minute slosh box test using 28 RPM and an 18° tilt angle. The flushability test presented herein provides a more stringent flushability test. A commercially available nonwoven web in the form of a flushable wipe, referred to herein as Commercial Wipe A, is certified flushable and has a disintegration time of 20 seconds as measured by the flushability test presented herein. Thus, as used herein, unless otherwise specified, the term "flushable" refers to an article, e.g., a nonwoven web or pouch, that has a percent disintegration as measured by the Flushability Test set forth herein that meets or exceeds the percent disintegration of Commercial Wipe A (20%). Flushable nonwoven webs and articles containing same have the advantage that they are more processable in reuse processes or can simply be flushed, for example, into a municipal wastewater treatment system for purification, and that the web, structure or pouch does not need to be landfilled, incinerated or otherwise disposed of after use.

[0044] As used herein, unless otherwise specified, the term "nonwoven web" refers to a web or sheet that includes, consists of, or consists essentially of fibers that are arranged (e.g., by carding) and bonded to one another. Thus, the term nonwoven web can be considered shorthand for nonwoven fiber-based web. Furthermore, as used herein, "nonwoven web" includes any structure that includes a nonwoven web or sheet, including, for example, a nonwoven web or sheet having a film laminated to its surface. Methods for preparing nonwoven webs from fibers are well known in the art and are described, for example, in Nonwoven Fabrics Handbook, prepared by Ian Butler, edited by Subhash Batra et al., Printing by Design, 1999, which is incorporated herein by reference in its entirety. As used herein, unless otherwise specified, the term "film" refers to a continuous film or sheet prepared, for example, by casting or extrusion methods.

[0045] "Comprising" as used herein means that various components, ingredients or steps can be used jointly to carry out the present disclosure. Thus, the term "comprising" encompasses the more restrictive terms "consisting essentially of" and "consisting of". The present composition can include, consist essentially of, or consist of any of the necessary and optional elements disclosed herein. For example, a thermoformed packet can "consist essentially of" a nonwoven web as described herein for use of its thermoformable properties, while including a non-thermoformable film or nonwoven web (e.g., a lid portion) and optional markings on the film, for example by inkjet printing. The present invention illustratively disclosed herein may be suitably carried out in the absence of any element or step not specifically disclosed herein.

[0046] All percentages, parts and ratios referred to herein are based on the total dry weight of the nonwoven web or film compositions of the present disclosure, or the total weight of the packet contents compositions, as the case may be, and all measurements are made at about 25° C., unless otherwise specified. All such weights are based on the active level and therefore do not include carriers or by-products that may be included in commercially available materials, unless otherwise specified.

[0047] All ranges set forth herein include all possible subsets of ranges and any combination of such subset ranges. By default, unless otherwise stated, a range includes the stated endpoints. When a range of values ​​is provided, it is understood that each intervening value between the upper and lower limits of that range, and any other stated or intervening values ​​in that stated range, are included within the disclosure. The upper and lower limits of these smaller ranges may be independently included in the smaller ranges, and are also included within the disclosure, subject to any specifically excluded limits in the stated range. When a stated range includes one or both limits, it is contemplated that ranges excluding either or both of the included limits are also part of the disclosure.

[0048] For example, for any numerical values ​​set forth herein as part of a parameter of or a range relevant to the described subject matter, alternatives forming part of the description are expressly contemplated as functionally equivalent ranges surrounding the particular numerical value (e.g., for a dimension disclosed as "40 mm," an alternative embodiment contemplated is "about 40 mm").

[0049] As used herein, the terms packet(s) and pouch(s) should be considered interchangeable. In certain embodiments, the terms packet(s) and pouch(s) are used to refer to containers made using nonwoven webs and / or films, respectively, and fully sealed containers, preferably having materials sealed therein, for example in the form of a metered dose delivery system. Sealed pouches can be made from any suitable method, including processes and features such as heat sealing, solvent welding, and adhesive sealing (e.g., by using water-soluble adhesives).

[0050] As used herein, unless otherwise specified, the terms "wt.%" and "wt%" are intended to refer to the composition of a particular element of the entire referenced article or composition, e.g., the "dry" (non-aqueous) weight of a nonwoven web or film or laminate structure, including residual moisture in the nonwoven web or film (if applicable), or the weight of a composition enclosed within a pouch (if applicable).

[0051] As used herein, unless otherwise specified, the term "PHR" ("phr") is intended to refer to the composition of a particular element in parts per 100 parts of water-soluble polymer (whether PVOH or other polymer, unless otherwise specified) in the solution used to make the referenced polymer-containing article, e.g., water-soluble film, fiber or nonwoven web, or fiber or film.

[0052] The nonwoven webs, pouches and related articles, and methods of making and using, unless otherwise stated, are intended to include embodiments that include any combination of one or more of the additional optional elements, features and steps further described below (including those shown in the examples and figures).

[0053] Fiber-forming materials

[0054] Generally, the fibers of the present disclosure may comprise a single fiber-forming material or a combination (i.e., blend) of fiber-forming materials. A single fiber may comprise one or more water-soluble fiber-forming materials, one or more water-insoluble fiber-forming materials, or a combination of water-soluble and water-insoluble fiber-forming materials. The fibers of the present disclosure may generally comprise synthetic fiber-forming materials, natural fiber-forming materials, plant-based fiber-forming materials, bio-based fiber-forming materials, biodegradable fiber-forming materials, compostable fiber-forming materials, or combinations thereof. Plant-based fiber-forming materials may be naturally occurring (e.g., cotton) or reconstituted (e.g., bamboo).

[0055] Generally, the fibers of the present disclosure include fiber-forming materials that contain hydrolyzable groups before contact with a hydrolysis agent. Hydrolyzable groups generally include (a) any functional group that can be displaced by a nucleophilic group, such as water or hydroxyl ion, in the presence of an acid or base catalyst, (b) a cyclic functional group (e.g., a cyclic ester such as a lactone) that can be opened by a nucleophilic group, (c) a functional group that can be cleaved by water in the presence of an enzyme to provide an -OH moiety on the polymer backbone, and / or (d) any functional group that can be reduced to provide an -OH moiety on the polymer backbone. Suitable hydrolyzable groups include, but are not limited to, esters, amides, ethers, acetals, nitriles, sulfhydryls, or combinations thereof. Suitable polymers containing hydrolyzable groups include polyvinyl acetate, polyvinyl propionate, polyvinyl alcohol polymers having a degree of hydrolysis less than 100%, poly(N-vinyl acetamide) polymers, polyvinyl butyral polymers, poly(butyl acrylate) polymers, poly(butyl methacrylate) polymers, cellulose acetate polymers, polyacrylonitrile polymers, poly(N-isopropylacrylamide) polymers, poly(N,N-diethylacrylamide) polymers, poly(N,N-dimethylacrylamide) polymers, poly(methyl vinyl ether) polymers, poly(N,N-dimethylaminoethyl methacrylate) polymers, poly(N-vinyl formamide) polymers, poly(N-vinyl caprolactam) polymers, polyvinyl pyrrolidone polymers, polylactic acid and combinations thereof.

[0056] In an embodiment, the fibers of the present disclosure include a polymer that includes at least one vinyl acetate or vinyl alcohol moiety. Such polymers are hydrolyzable. Unless otherwise expressly indicated, the term "polymer that includes at least one vinyl acetate or vinyl alcohol moiety" as used herein is understood to encompass any polymer that has at least one moiety derived from only vinyl acetate, only vinyl alcohol, or both vinyl acetate and vinyl alcohol. In some embodiments, suitable examples of such polymers (or polymers thereof) include, without limitation, polyvinyl alcohol homopolymers, polyvinyl acetate homopolymers, polyvinyl alcohol copolymers, modified polyvinyl alcohol copolymers, and combinations thereof. For example, polyvinyl alcohol copolymers, in some embodiments, are copolymers of vinyl acetate and vinyl alcohol. For example, in some embodiments, modified polyvinyl alcohol copolymers include anionically modified copolymers, which may be copolymers of vinyl acetate and vinyl alcohol further including additional groups such as carboxylate, sulfonate, or combinations thereof. Such polymers that include at least one vinyl acetate or vinyl alcohol moiety may also include additional polymers, for example, in blends.

[0057] Unless otherwise clearly indicated, the term "degree of hydrolysis" is understood as the percentage (e.g., molar percentage) of hydrolyzed moieties among all hydrolyzable moieties that the polymer initially has. For example, in the case of a polymer containing at least one vinyl acetate moiety or vinyl alcohol moiety, partial replacement of the ester groups of the vinyl acetate moiety by hydroxyl groups occurs during hydrolysis, and the vinyl acetate moiety becomes a vinyl alcohol moiety. The degree of hydrolysis of a polyvinyl acetate homopolymer is considered to be zero, while the degree of hydrolysis of a polyvinyl alcohol homopolymer is 100%. The degree of hydrolysis of a copolymer of vinyl acetate and vinyl alcohol is equal to the percentage of vinyl alcohol moieties among the total vinyl acetate and vinyl alcohol moieties, which is between zero and 100%.

[0058] Polyvinyl alcohol is a synthetic polymer that can be prepared by alcoholysis, also called hydrolysis or saponification, of polyvinyl acetate. Fully hydrolyzed PVOH, in which virtually all acetate groups have been converted to alcohol groups, is a strongly hydrogen-bonded, highly crystalline polymer that is soluble only in hot water above about 140°F (about 60°C). If a sufficient number of acetate groups are allowed to remain after hydrolysis of polyvinyl acetate, i.e., the PVOH polymer is partially hydrolyzed, the polymer is less hydrogen-bonded, less crystalline, and generally soluble in cold water below about 50°F (about 10°C). Thus, the partially hydrolyzed polymer is generally referred to as "polyvinyl alcohol (PVOH)" or "PVOH polymer", although it is a vinyl alcohol-vinyl acetate copolymer that is a PVOH copolymer. For the sake of brevity, the term "PVOH polymer" as used herein is understood to encompass homopolymers, copolymers, and modified copolymers that contain vinyl alcohol moieties, e.g., 50% or more vinyl alcohol moieties.

[0059] The fibers described herein may include polyvinyl acetate, one or more polyvinyl alcohol (PVOH) homopolymers, one or more polyvinyl alcohol copolymers, or combinations thereof. As used herein, the term "homopolymer" generally includes polymers having a single type of monomer repeat unit (e.g., a polymer chain consisting of or consisting essentially of a single monomer repeat unit). In the specific case of "PVOH", the term "PVOH polymer" as an example of a hydrolyzable polymer or a polymer containing at least one vinyl acetate or vinyl alcohol moiety includes a polymer consisting of a distribution of vinyl alcohol monomer units and vinyl acetate monomer units depending on the degree of hydrolysis (e.g., a polymer chain consisting of or consisting essentially of vinyl alcohol and vinyl acetate monomer units). In the limiting case of 100% hydrolysis, a PVOH homopolymer may include a true homopolymer having only vinyl alcohol units. In some embodiments, the fibers and / or films of the present disclosure include such polymers containing at least one vinyl acetate or vinyl alcohol moiety. In some embodiments, the fibers and / or films of the present disclosure include a heat-soluble polymer containing at least one vinyl acetate or vinyl alcohol moiety.

[0060] In some embodiments, the hydrolyzable polymers described herein include modified polyvinyl alcohols, e.g., copolymers. Modified polyvinyl alcohols can include copolymers or higher order polymers (e.g., terpolymers) that include one or more monomers in addition to vinyl acetate / vinyl alcohol groups. Optionally, the modification is neutral, e.g., by ethylene, propylene, N-vinylpyrrolidone, or other uncharged monomer species. Optionally, the modification is cationic, e.g., by positively charged monomer species. Optionally, the modification is anionic. Thus, in some embodiments, polyvinyl alcohol includes anionically modified polyvinyl alcohol. Anionically modified polyvinyl alcohol can include partially or fully hydrolyzed PVOH copolymers that include anionic monomer units, vinyl alcohol monomer units, and optionally vinyl acetate monomer units (i.e., if not fully hydrolyzed). In some embodiments, the PVOH copolymer can include two or more anionic monomer units. General classes of anionic monomer units that can be used in PVOH copolymers include vinyl polymerized units corresponding to vinyl sulfonic acid monomers and their esters, vinyl monocarboxylic acid monomers, their esters and anhydrides, dicarboxylic acid monomers having a polymerizable double bond, their esters and anhydrides, and alkali metal salts of any of the foregoing.Examples of suitable anionic monomer units are vinyl acetate, maleic acid, monoalkyl maleates, dialkyl maleates, maleic anhydride, fumaric acid, monoalkyl fumarates, dialkyl fumarates, itaconic acid, monoalkyl itaconates, dialkyl itaconates, citraconic acid, monoalkyl citraconates, dialkyl citraconates, citraconic anhydride, mesaconic acid, monoalkyl mesaconates, dialkyl mesaconates, glutaconic acid, monoalkyl glutaconates, dialkyl glutaconates, glutaconic anhydride, alkyl acrylates, alkacrylates, vinyl sulfonic acids, alkoxy acrylates, vinyl sulphonic ... The PVOH copolymers include vinyl polymerized units corresponding to vinyl anionic monomers including alkylsulfonic acid, ethylenesulfonic acid, 2-acrylamido-1-methylpropanesulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, 2-methylacrylamido-2-methylpropanesulfonic acid, 2-sulfoethyl acrylate, alkali metal salts of the foregoing (e.g., sodium, potassium or other alkali metal salts), esters of the foregoing (e.g., methyl, ethyl or other C1-C4 or C6 alkyl esters), and combinations of the foregoing (e.g., multiple anionic monomers or equivalent forms of the same anionic monomer). In some embodiments, the PVOH copolymers may include two or more monomer units selected from neutral, anionic, and cationic monomer units.

[0061] The level of incorporation / modification of one or more monomer units of the PVOH copolymer is not particularly limited. In an embodiment, the one or more monomer units / modifications are present in the PVOH copolymer in an amount ranging from about 1 mol.% or 2 mol.% to about 6 mol.% or 10 mol.% (e.g., at least 1.0, 1.5, 2.0, 2.5, 3.0, 3.5 or 4.0 mol.% and / or up to about 3.0, 4.0, 4.5, 5.0, 6.0, 8.0 or 10 mol.%) in various embodiments. In embodiments, the modification is an anionic modification, and the anionic monomer units are present in the PVOH copolymer in an amount ranging from about 1 mol.% or 2 mol.% to about 6 mol.% or 10 mol.% (e.g., in various embodiments, at least 1.0, 1.5, 2.0, 2.5, 3.0, 3.5 or 4.0 mol.% and / or up to about 3.0, 4.0, 4.5, 5.0, 6.0, 8.0 or 10 mol.%).

[0062] Polyvinyl alcohol can be subjected to changes in dissolution characteristics. It is known to those skilled in the art that the acetate groups of co-poly(vinyl acetate=vinyl alcohol) polymers (PVOH copolymers) can be hydrolyzed by either acid or alkaline hydrolysis. As the degree of hydrolysis increases, the polymer compositions made with PVOH copolymers have increased mechanical strength but have decreased solubility at lower temperatures (e.g., hot water temperatures are required for dissolution). Thus, exposure of PVOH copolymers to an alkaline environment (e.g., resulting from laundry bleach additives) can transform the polymer from one that dissolves quickly and completely in a given aqueous environment (e.g., cold water medium) to one that dissolves slowly and / or incompletely in the aqueous environment, which can result in undissolved polymer residue at the end of the wash cycle.

[0063] For example, PVOH copolymers with pendant carboxyl groups, such as vinyl alcohol / hydrolyzed methyl acrylate sodium salt polymers, may form lactone rings between adjacent pendant carboxyl and alcohol groups, thus decreasing the aqueous solubility of the PVOH copolymer. In the presence of a strong base, the lactone rings can be opened over the course of several weeks in relatively warm (ambient) and humid conditions (e.g., via lactone ring-opening reaction, the corresponding pendant carboxyl and alcohol groups are formed, increasing the aqueous solubility). Thus, contrary to the effect observed with PVOH copolymers without pendant carboxyl groups, it is believed that such PVOH copolymers may become more soluble due to chemical interactions between the polymer and the alkaline composition inside the pouch during storage.

[0064] Certain sulfonic acids and their derivatives with polymerizable vinyl bonds can be copolymerized with vinyl acetate to provide cold water-soluble PVOH polymers that are stable in the presence of strong base. The base-catalyzed alcoholysis products of these copolymers used in the formulation of water-soluble films are fast-dissolving vinyl alcohol-sulfonate salt copolymers. Although the sulfonate groups of the PVOH copolymers can revert to sulfonic acid groups in the presence of hydrogen ions, the sulfonic acid groups still provide the polymer with excellent cold water solubility. In embodiments, the vinyl alcohol-sulfonate salt copolymers do not contain residual acetate groups (i.e., are fully hydrolyzed) and therefore cannot be further hydrolyzed by either acid or alkaline hydrolysis. In general, as the amount of modification increases, the water solubility increases, and thus sufficient modification via sulfonate or sulfonic acid groups inhibits hydrogen bonding and crystallinity to allow dissolution in cold water. In the presence of acidic or basic species, the copolymer is generally unaffected except for the sulfonate or sulfonic acid groups, which maintain excellent cold water solubility even in the presence of acidic or basic species. Examples of suitable sulfonic acid comonomers (and / or their alkali metal salt derivatives) include vinyl sulfonic acid, alkyl sulfonic acids, ethylene sulfonic acid, 2-acrylamido-1-methylpropanesulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, 2-methacrylamido-2-methylpropanesulfonic acid, and 2-sulfoethyl acrylate, with the sodium salt of 2-acrylamido-2-methylpropanesulfonic acid (AMPS) being the preferred comonomer.

[0065] The fiber-forming polymers can be blended, whether polyvinyl alcohol polymers or not. When the polymer blend comprises a blend of polyvinyl alcohol polymers, the PVOH polymer blend can comprise a first PVOH polymer ("first PVOH polymer"), which can comprise a PVOH copolymer or a modified PVOH copolymer comprising one or more anionic monomer units (e.g., a PVOH ter(or higher copolymer), and a second PVOH polymer ("second PVOH polymer"), which can comprise a PVOH co-polymer or a modified PVOH copolymer comprising one or more anionic monomer units (e.g., a PVOH ter(or higher copolymer). In some embodiments, the PVOH polymer blend comprises only a first PVOH polymer and a second PVOH polymer (e.g., a binary blend of two polymers). Alternatively or additionally, the PVOH polymer blend or the fiber or nonwoven web made therefrom can be characterized as being free or substantially free of other polymers (e.g., other polymers in general, other PVOH-based polymers in particular, or both). As used herein, "substantially free" means that the first and second PVOH polymers constitute at least 95 wt.%, at least 97 wt.%, or at least 99 wt.% of the total amount of water-soluble polymers in the water-soluble fiber or film. In other embodiments, the fiber may contain one or more additional water-soluble polymers. For example, the PVOH polymer blend may contain a third PVOH polymer, a fourth PVOH polymer, a fifth PVOH polymer, etc. (e.g., one or more additional PVOH copolymers or modified PVOH copolymers with or without anionic monomer units). For example, the fiber may contain at least a third (or fourth, fifth, etc.) water-soluble polymer other than the PVOH polymer (e.g., other than the PVOH copolymer or modified PVOH copolymer with or without anionic monomer units).

[0066] The degree of hydrolysis (DH) of the PVOH copolymers included in the fibers of the present disclosure can range from about 75% to about 99.9% (e.g., for cold water-soluble compositions, about 79% to about 99.9%, about 79% to about 92%, about 80% to about 90%, about 88% to 92%, about 86.5% to about 89%, or about 88%, 90% or 92%; about 90% to about 99%, about 92% to about 99%, about 95% to about 99%, about 98% to about 99%, about 98% to about 99.9%, about 96%, about 98%, about 99% or more than 99%). As the degree of hydrolysis decreases, fibers made from the polymer have decreased mechanical strength but dissolve faster at temperatures below about 20° C. As the degree of hydrolysis increases, fibers or films made from the polymer tend to have increased mechanical strength and decreased thermoformability. The degree of hydrolysis can be selected so that the water solubility of the polymer is temperature dependent, and thus the solubility of the fibers made from the polymer is also affected. In one alternative, the fiber or film is cold water soluble. In the case of co-poly(vinyl acetate=vinyl alcohol) polymers that do not contain any other monomers (e.g., homopolymers that do not copolymerize with anionic monomers), cold water soluble fibers that are soluble in water at temperatures below 10°C can include PVOH with a degree of hydrolysis in the range of about 75% to about 90%, or in the range of about 80% to about 90%, or in the range of about 85% to about 90%. In another alternative, the fiber is hot water soluble. In the case of co-poly(vinyl acetate=vinyl alcohol) polymers that do not contain any other monomers (e.g., homopolymers that do not copolymerize with anionic monomers), hot water soluble fibers that are soluble in water at temperatures of at least about 60°C can include PVOH with a degree of hydrolysis of at least about 98%.

[0067] The degree of hydrolysis of the polymer blends can also be calculated using the arithmetically weighted, average degree of hydrolysis (OD) of the polymer blend.

number

number

number

[0068] The viscosity (μ) of the PVOH polymer is determined by measuring the freshly made solution using a Brookfield LV type viscometer with UL adapter as described in British Standard EN ISO 15023-2:2006 Annex E Brookfield test method. It is an international standard to describe the viscosity of a 4% polyvinyl alcohol solution in water at 20°C. All viscosities (units of centipoise (cp)) specified herein should be understood to refer to the viscosity of a 4% polyvinyl alcohol solution in water at 20°C, unless otherwise specified. Similarly, when a polymer is described as having (or not having) a particular viscosity, unless otherwise specified, the particular viscosity is intended to be the average viscosity of the polymer, which essentially has a corresponding molecular weight distribution, i.e., a weighted natural logarithmic average viscosity as described below. The viscosity of the PVOH polymer is determined by the weight average molecular weight of the PVOH polymer.

number

number

[0069] In embodiments, the PVOH polymer may have a viscosity of about 1.0 to about 50.0 cP, about 1.0 to about 40.0 cP, or about 1.0 to about 30.0 cP, such as about 4 cP, 8 cP, 15 cP, 18 cP, 23 cP, or 26 cP. In embodiments, the PVOH homopolymer and / or copolymer may have a viscosity of about 1.0 to about 40.0 cP, or about 5 cP to about 23 cP, such as about 1 cP, 1.5 cP, 2 cP, 2.5 cP, 3 cP, 3.5 cP, 4 cP, 4.5 cP, 5 cP, 5.5 cP, 6 cP, 6.5 cP, 7 cP, 7.5 cP, 8 cP, 8.5 cP, 9 cP, The PVOH homopolymer and / or copolymer may have a viscosity of about 21 cP to about 26 cP. In embodiments, the PVOH homopolymer and / or copolymer may have a viscosity of about 5 cP to about 14 cP. In embodiments, the PVOH homopolymer and / or copolymer may have a viscosity of about 5 cP to about 23 cP.

[0070] For reference, in the polymer blend, the first PVOH polymer is designated as having a first 4% solution viscosity (μ1) at 20° C. and the second PVOH polymer is designated as having a second 4% solution viscosity (μ2) at 20° C. In various embodiments, the first viscosity μ1 can range from about 4 cP to about 70 cP (e.g., at least about 4, 8, 10, 12, or 16 cP and / or up to about 12, 16, 20, 24, 28, 30, 32, 35, 37, 40, 45, 48, 50, 56, 60, or 70 cP, e.g., from about 4 cP to about 70 cp, from about 4 cp to about 60 cp, from about 4 cP to about 46 cP, from about 4 cP to about 24 cP, from about 10 cP to about 16 cP, or from about 10 cP to about 20 cP, or from about 20 cP to about 30 cP). Alternatively, or in addition, the second viscosity μ2 can be in the range of about 4 cP to about 70 cP (e.g., at least about 4, 8, 10, 12 or 16 cP and / or up to about 12, 16, 20, 24, 28, 30, 32, 35, 37, 40, 45, 48, 50, 56, 60 or 70 cP, e.g., about 12 cP to about 30 cP, about 10 cP to about 16 cP, or about 10 cP to about 20 cP, or about 20 cP to about 30 cP). When the PVOH polymer blend includes three or more PVOH polymers selected from PVOH polymers and PVOH copolymers, the aforementioned viscosity values ​​can apply to each PVOH polymer or PVOH copolymer individually. Thus, the weight average molecular weight of the water-soluble polymers, including the first PVOH copolymer and the second PVOH copolymer, can be, for example, in the range of about 30,000 to about 175,000, or about 30,000 to about 100,000, or about 55,000 to about 80,000. When referring to the average viscosity of a PVOH polymer blend, the weighted natural logarithm average viscosity is

number

number

number

[0071] In an embodiment in which the water-soluble fiber comprises a blend of polyvinyl alcohol homopolymer and polyvinyl alcohol copolymer, the relative amount of homopolymer and copolymer is not particularly limited. The polyvinyl alcohol homopolymer may comprise about 15wt.% to about 70wt.% of the total weight of the water-soluble polymer blend, for example, at least about 15wt.%, at least about 20wt.%, at least about 25wt.%, at least about 30wt.%, at least about 40wt.%, at least about 50wt.% or at least about 60wt.% and up to about 70wt.%, up to about 60wt.%, up to about 50wt.%, up to about 40wt.% or up to about 30wt.%, based on the total weight of the water-soluble polymer blend, and may be a single homopolymer or a blend of one or more homopolymers (e.g., with differences in viscosity and / or degree of hydrolysis). The remainder of the water-soluble polymer blend may be a water-soluble polyvinyl alcohol copolymer. Without intending to be bound by theory, it is believed that the ability of the blend of polyvinyl alcohol homopolymers and copolymers to form fibers decreases as the amount of homopolymer decreases below about 15 wt.%. The water-soluble polyvinyl alcohol copolymer may comprise about 30 wt.% to about 85 wt.% of the total weight of the water-soluble polymer blend, for example, at least about 30 wt.%, at least about 40 wt.%, at least about 50 wt.%, at least about 60 wt.%, at least about 70 wt.%, at least about 75 wt.% or at least about 80 wt.% and up to about 85 wt.%, up to about 80 wt.%, up to about 70 wt.%, up to about 60 wt.%, up to about 50 wt.% or up to about 40 wt.%, based on the total weight of the water-soluble polymer blend, and may be a single copolymer or a blend of one or more copolymers. The blend may consist of polyvinyl alcohol homopolymer and polyvinyl alcohol copolymer. The blend may consist of a polyvinyl alcohol homopolymer and a plurality of polyvinyl alcohol copolymers. The blend may consist of more than one polyvinyl alcohol homopolymer and more than one polyvinyl alcohol copolymer.

[0072] In an embodiment, the fiber comprises polyvinyl acetate, polyvinyl alcohol homopolymer, polyvinyl alcohol copolymer, modified polyvinyl alcohol copolymer, or a combination thereof. In an embodiment, the fiber comprises polyvinyl alcohol homopolymer, polyvinyl alcohol copolymer, modified polyvinyl alcohol copolymer, or a combination thereof. In an embodiment, the fiber comprises a polyvinyl alcohol copolymer. In an embodiment, the fiber comprises a modified polyvinyl alcohol copolymer. In an embodiment, the fiber comprises a polyvinyl alcohol copolymer that is an anionically modified copolymer. In an embodiment, the fiber comprises an anionically modified copolymer, the anionically modified comprises a carboxylate, a sulfonate, or a combination thereof. In an embodiment, the polyvinyl alcohol polymer is water soluble prior to mixing the fiber with the hydrolysis agent solution. In an embodiment, the polymer has a degree of hydrolysis of greater than about 79% and less than about 99.9% (e.g., from about 79% to about 96%) prior to mixing the fiber with the hydrolysis agent solution.

[0073] The fibers of the present disclosure may include water-soluble polymers other than polyvinyl acetate and PVOH, including but not limited to polyacrylates, water-soluble acrylate copolymers, polyvinylpyrrolidone, polyethyleneimine, pullulan, water-soluble natural polymers, including but not limited to guar gum, acacia gum, xanthan gum, carrageenan, and water-soluble starch, water-soluble polymer derivatives, including but not limited to modified starch, ethoxylated starch, and hydroxypropylated starch, copolymers of the foregoing, and combinations of any of the foregoing additional polymers or copolymers. Still other water-soluble polymers may include polyalkylene oxides, polyacrylamides, polyacrylic acids and their salts, water-soluble celluloses, cellulose ethers, cellulose esters, cellulose amides, additional polyvinyl acetates, polycarboxylic acids and their salts, polyamino acids, polyamides, gelatin, methylcellulose, carboxymethylcellulose and its salts, dextrins, ethylcellulose, hydroxyethylcellulose, hydroxypropylmethylcellulose, maltodextrins, polymethacrylates, and combinations of any of the foregoing. Such water-soluble polymers, whether PVOH or otherwise, are commercially available from a variety of sources.

[0074] In an embodiment, the fibers comprise a polyvinyl alcohol polymer and an additional polymer including polyvinyl alcohol, polyvinyl acetate, polyacrylate, water soluble acrylate copolymer, polyvinylpyrrolidone, polyethyleneimine, pullulan, guar gum, acacia gum, xanthan gum, carrageenan, starch, modified starch, polyalkylene oxide, polyacrylamide, polyacrylic acid, cellulose, cellulose ethers, cellulose esters, cellulose amides, polycarboxylic acids, polyamino acids, polyamides, gelatin, dextrin, copolymers of the foregoing, and combinations of any of the foregoing additional polymers or copolymers.

[0075] The fiber may further comprise water-insoluble fiber-forming materials.Suitable water-insoluble fiber-forming materials include, but are not limited to, cotton, polyester, copolyester, polyethylene (e.g., high-density polyethylene and low-density polyethylene), polypropylene, wood pulp, fluff pulp, Manila hemp, viscose, insoluble cellulose, insoluble starch, hemp, jute, flax, ramie, sisal, bagasse, banana fiber, white pine, silk, tendon, cut gut, wool, sea silk, mohair, angora, cashmere, collagen, actin, nylon, Dacron, rayon, bamboo fiber, modal, diacetate fiber, triacetate fiber, polyester, copolyester, polylactide (PLA), polyethylene terephthalate (PET), polypropylene (PP) and combinations thereof.In an embodiment, the water-insoluble fiber does not comprise cotton or rayon. In an embodiment, the water insoluble fibers include wool, diacetate, triacetate, nylon, PLA, PET, PP, or combinations thereof.

[0076] The fibers may further include non-fiber forming materials, referred to herein as auxiliary or secondary components. The adjuvants may include active agents and processing agents in amounts suitable for their intended purpose, such as, but not limited to, activators, plasticizers, plasticizer compatibilizers, surfactants, lubricants, release agents, fillers, extenders, crosslinkers, antiblocking agents, antioxidants, detackifying agents, antifoaming agents, nanoparticles such as layered silicate-type nanoclays (e.g., sodium montmorillonite), bleaching agents (e.g., sodium metabisulfite, sodium bisulfite or others), aversive agents such as bittering agents (e.g., denatonium salts such as denatonium benzoate, denatonium sugar and denatonium chloride; sucrose octaacetate; quinine; flavonoids such as quercetin and naringenin; and cassinoids such as cassine and brucine) and pungent agents (e.g., capsaicin, piperine, allyl isocyanate and resiniferatoxin), and other functional ingredients. As used herein, unless otherwise specified, "auxiliary agents" includes secondary additives, treatment agents, and active agents. Particular such auxiliary agents and treatment agents may be selected from those suitable for use in water soluble fibers, water insoluble fibers, nonwoven webs, or those suitable for use in water soluble films.

[0077] In embodiments, the fibers of the present disclosure are adjunct-free. As used herein, unless otherwise specified, "adjunct-free" with respect to a fiber means that the fiber contains less than about 0.01 wt.%, less than about 0.005 wt.%, or less than about 0.001 wt.% adjunct, based on the total weight of the fiber.

[0078] A plasticizer is a liquid, solid, or semi-solid that is added to a material (usually a resin or elastomer) to make it softer, more flexible (by lowering the glass transition temperature of the polymer), and easier to process. Alternatively, a polymer may be plasticized internally by chemically modifying the polymer or monomer. Additionally or alternatively, a polymer may be plasticized externally by adding a suitable plasticizer. Water is recognized as a very efficient plasticizer for PVOH and other polymers, including but not limited to water-soluble polymers, however, its volatility limits its use, since polymer films must have at least some resistance (robustness) to variations in ambient conditions, including low and high relative humidity.

[0079] Plasticizers may include, but are not limited to, glycerin, diglycerin, sorbitol, ethylene glycol, diethylene glycol, triethylene glycol, dipropylene glycol, tetraethylene glycol, propylene glycol, polyethylene glycols up to 400 MW, neopentyl glycol, trimethylolpropane, polyether polyols, sorbitol, 2-methyl-1,3-propanediol (MPDiol®), ethanolamine and mixtures thereof. The total amount of non-aqueous plasticizer provided in the fibers can be in the range of about 1 wt.% to about 45 wt.%, or about 5 wt.% to about 45 wt.%, or about 10 wt.% to about 40 wt.%, or about 20 wt.% to about 30 wt.%, about 1 wt.% to about 4 wt.%, or about 1.5 wt.% to about 3.5 wt.%, or about 2.0 wt.% to about 3.0 wt.%, for example, about 1 wt.%, about 2.5 wt.%, about 5 wt.%, about 10 wt.%, about 15 wt.%, about 20 wt.%, about 25 wt.%, about 30 wt.%, about 35 wt.% or about 40 wt.%, based on the total fiber weight.

[0080] Surfactants for use in fibers are well known in the art. Surfactants for use in films are also well known in the art and can be suitably used in the fibers and / or nonwoven webs of the present disclosure. Optionally, surfactants are included to aid in the dispersion of fibers during processing. Surfactants suitable for the fibers of the present disclosure include, but are not limited to, dialkyl sulfosuccinates, lactylated fatty acid esters of glycerol and propylene glycol, lactic acid esters of fatty acids, sodium alkyl sulfates, polysorbate 20, polysorbate 60, polysorbate 65, polysorbate 80, alkyl polyethylene glycol ethers, lecithin, acetylated fatty acid esters of glycerol and propylene glycol, sodium lauryl sulfate, acetylated esters of fatty acids, myristyl dimethylamine oxide, trimethyl tallow alkyl ammonium chloride, quaternary ammonium compounds, alkali metal salts of higher fatty acids containing about 8 to 24 carbon atoms, alkyl sulfates, alkyl polyethoxylate sulfates, alkyl benzene sulfonates, monoethanolamines, lauryl alcohol ethoxylates, propylene glycol, diethylene glycol, salts thereof, and combinations of any of the foregoing.

[0081] Suitable surfactants may include nonionic, cationic, anionic and zwitterionic classes. Suitable surfactants include, but are not limited to, propylene glycol, diethylene glycol, monoethanolamine, polyoxyethylated polyoxypropylene glycol, alcohol ethoxylates, alkylphenol ethoxylates, tertiary acetylenic glycols and alkanolamides (nonionic), polyoxyethylated amines, quaternary ammonium salts and quaternized polyoxyethylated amines (cationic), alkali metal salts of higher fatty acids containing about 8 to 24 carbon atoms, alkyl sulfates, alkyl polyethoxylate sulfates and alkylbenzene sulfonates (anionic), and amine oxides, N-alkyl betaines and sulfobetaines (zwitterionic). Other suitable surfactants include dioctyl sodium sulfosuccinate, lactylated fatty acid esters of glycerin and propylene glycol, lactic acid esters of fatty acids, sodium alkyl sulfates, polysorbate 20, polysorbate 60, polysorbate 65, polysorbate 80, lecithin, acetylated fatty acid esters of glycerin and propylene glycol, and acetylated esters of fatty acids, and combinations thereof. In various embodiments, the amount of surfactant in the fiber ranges from about 0.01 wt.% to about 2.5 wt.%, from about 0.1 wt.% to about 2.5 wt.%, from about 1.0 wt.% to about 2.0 wt.%, from about 0.01 wt.% to 0.25 wt.%, or from about 0.10 wt.% to 0.20 wt.%.

[0082] In embodiments, the fibers and / or nonwoven webs of the present disclosure may include an active agent. The active agent may be added to the fibers themselves, or during carding of the nonwoven web, and / or may be added to the nonwoven web prior to bonding. An active agent added to the fibers during carding may be distributed throughout the nonwoven web. An active agent added to the nonwoven web after carding but prior to bonding may be selectively added to one or both surfaces of the nonwoven web. Additionally, the active agent may be added to the surface of a pouch or other article prepared from the nonwoven web. In embodiments, the active agent is provided as part of a plurality of fibers, dispersed within the nonwoven web, provided on a surface of the nonwoven web, or a combination thereof.

[0083] The active agent provides additional functionality to the nonwoven web when present in the fibers and / or nonwoven web in an amount of at least about 1 wt%, or in a range of about 1 wt% to about 99 wt%. In embodiments, the active agent may include one or more components including, but not limited to, enzymes, oils, fragrances, colorants, odor absorbers, fragrances, insecticides, fertilizers, activators, acid catalysts, metal catalysts, ion scavengers, detergents, disinfectants, surfactants, bleaching agents, bleaching components, fabric softeners, or combinations thereof. In embodiments, the active agent may include colorants, surfactants, or combinations thereof. The active agent may take any desired form including solids (e.g., powders, granules, crystals, flakes, or ribbons), liquids, mulls, pastes, gases, and the like, and may be encapsulated, if desired.

[0084] In certain embodiments, the active agent may include an enzyme. Suitable enzymes include enzymes classified into one of the six traditional Enzyme Commission (EC) classifications: EC1 oxidoreductases (catalyzing oxidation / reduction reactions), EC2 transferases (transferring functional groups, e.g., methyl or phosphate groups), EC3 hydrolases (catalyzing the hydrolysis of various bonds), EC4 lyases (cleaving various bonds by means other than hydrolysis and oxidation), EC5 isomerases (catalyzing isomerization changes within a molecule), and EC6 ligases (covalently linking two molecules together). Examples of such enzymes include EC1 dehydrogenases and oxidases, EC2 transaminases and kinases, EC3 lipases, cellulases, amylases, mannases and peptidases (also known as proteases or proteolytic enzymes), EC4 decarboxylases, EC5 isomerases and mutases, and EC6 synthetases and synthases. Suitable enzymes from each class are described, for example, in US Pat. No. 9,394,092, the entire disclosure of which is incorporated herein by reference.

[0085] Enzymes for use in laundry and dishwashing applications may include one or more of proteases, amylases, lipases, dehydrogenases, transaminases, kinases, cellulases, mannases, peptidases, decarboxylases, isomerases, mutases, synthetases, synthases, and oxido-reductase enzymes, including oxido-reductase enzymes that catalyze the formation of bleach.

[0086] Non-fragrant oils may include flavoring and coloring agents.

[0087] In one class of embodiments, the active agent comprises a flavor or combination of flavors. Suitable flavors include, but are not limited to, spearmint oil, cinnamon oil, oil of wintergreen (methyl salicylate), peppermint oil, and natural fruit flavors, including synthetic flavors and citrus oils.

[0088] In some embodiments, the active agent may be a colorant or a combination of colorants. Examples of suitable colorants include food colorants, caramel, paprika, cinnamon and saffron. Other examples of suitable colorants can be found in U.S. Patent No. 5,002,789, the entirety of which is incorporated herein by reference.

[0089] Another class of embodiments includes one or more odor absorbing agents as active agents. Odor absorbing agents suitable for use as active agents according to the present disclosure include, but are not limited to, zeolites and complex zinc salts of ricinoleic acid. Odor absorbing active agents may also include fixatives known in the art as nearly odor neutral fragrances, including, but not limited to, ladanum, extracts of Styrax japonica and derivatives of abietic acid.

[0090] Another class of embodiments includes one or more fragrances as active agents. As used herein, the term fragrance refers to any applicable material that volatilizes sufficiently to produce a scent. The embodiments that include a fragrance as an active agent may include fragrances that are pleasant to humans, or alternatively fragrances that are repelling to humans, animals, and / or insects. Suitable fragrances include, but are not limited to, fruity scents, including, but not limited to, lemon, apple, cherry, grape, pear, pineapple, orange, strawberry, raspberry, musk, and floral scents, including, but not limited to, lavender-like, rose-like, iris-like, and carnation-like. Optionally, the fragrance is also one that is not a flavoring. Other fragrances include, but are not limited to, herbaceous scents, including, but not limited to, rosemary, thyme, and sage, and woodland scents derived from pine, spruce, and other woodland scents. Fragrances may also be derived from various oils, including, but not limited to, essential oils, or plant materials, including, but not limited to, peppermint, spearmint, and the like. Suitable fragrance oils can be found in US Pat. No. 6,458,754, which is incorporated herein by reference in its entirety.

[0091] The fragrance may include a perfume. The perfume may include a neat perfume, an encapsulated perfume or a mixture thereof. Preferably, the perfume includes a neat perfume. A portion of the perfume may be encapsulated in a core-shell capsule. In another type of embodiment, the perfume is not encapsulated in a core-shell capsule.

[0092] As used herein, the term "perfume" includes perfume raw materials (PRMs) and perfume formulations. The term "perfume raw materials" as used herein refers to compounds having a molecular weight of at least about 100 g / mol and useful either alone or together with other perfume raw materials to impart an odor, fragrance, essence or scent. As used herein, the terms "perfume ingredient" and "perfume raw materials" are interchangeable. The term "formulation" as used herein refers to a mixture of two or more PRMs.

[0093] Applicable insect repellent fragrances include one or more of dichlorvos, pyrethrin, allethrin, naled and / or fenthion insecticides disclosed in U.S. Patent No. 4,664,064, the entirety of which is incorporated herein by reference.Suitable insect repellents are citronellal (3,7-dimethyl-6-octanal), N,N-diethyl-3-methylbenzamide (DEET), vanillin, and volatile oils extracted from turmeric (Curcuma longa), kaffir lime (Citrus hystrix), Chinese laurel grass (Cymbopogon winterianus) and Thai basil (Ocimum americanum).Furthermore, applicable insect repellents can be mixtures of insect repellents.

[0094] In one class of embodiments, the active agent according to the present disclosure comprises one or more pesticides. Suitable pesticides may include, but are not limited to, insecticides, herbicides, miticides, fungicides, and larvicides.

[0095] Another class of embodiments includes one or more fertilizers as activators. As used herein, the term fertilizer refers to any applicable material that releases one or more of nitrogen, phosphorus, potassium, calcium, magnesium, sulfur, boron, chlorine, copper, iron, manganese, molybdenum, or zinc. Suitable fertilizers include, but are not limited to, zeolites. For example, clinoptilolite is a zeolite that releases potassium and, if preloaded with ammonium, may also release nitrogen.

[0096] One class of embodiments includes an acid catalyst as an activator. As used herein, the term acid catalyst refers to any species that serves as a proton source, thereby facilitating a chemical reaction. In one type of embodiment, the acid catalyst is a non-oxidizing organic acid. A suitable organic acid is para-toluenesulfonic acid. In some embodiments, the acid catalyst activator promotes reactions including, but not limited to, acetalization, esterification, or transesterification. Additional acid-catalyzed reactions are well known in the art.

[0097] In one class of embodiments, the activator comprises a metal catalyst. These catalysts mediate reactions including, but not limited to, oxidation or reduction, hydrogenation, carbonylation, C-H bond activation and bleaching. Suitable metals for use as metal catalysts include, but are not limited to, VIIIA and IB transition metals, such as iron, cobalt, nickel, copper, platinum, rhodium, ruthenium, silver, osmium, gold and iridium. The metals that mediate catalytic reactions can be in any suitable oxidation state.

[0098] In an alternative embodiment, the active agent may optionally be an ion scavenger. Suitable ion scavenger agents include, but are not limited to, zeolites. Optionally, zeolites may be added to water-soluble packets containing encapsulated laundry or dishwashing detergent as a water softener.

[0099] Inorganic and organic bleaching agents are suitable cleaning actives for use herein. Inorganic bleaching agents include peroxygen salts, including but not limited to perborates, percarbonates, perphosphates, persulfates, and persilicates. Inorganic peroxygen salts are usually alkali metal salts. Alkali metal percarbonates, especially sodium percarbonate, are suitable peroxygen salts for use herein. Organic bleaching agents may include diacyl and tetraacyl peroxides, especially organic peroxyacids, including but not limited to diperoxydodecanedioic acid, diperoxytetradecanedioic acid, and diperoxyhexadecanedioic acid. Dibenzoyl peroxide is a suitable organic peroxyacid according to the present disclosure. Other organic bleaching agents include peroxyacids, specific examples being alkyl peroxyacids and aryl peroxyacids.

[0100] In one class of embodiments, the activator may include a bleach sensitizer comprising an organic peracid precursor that enhances the bleaching action of the cleaning process at temperatures of 60° C. and below. Bleach sensitizers suitable for use herein include compounds that under perhydrolysis conditions provide aliphatic peroxoycarboxylic acids having 1-10 carbon atoms, or 2-4 carbon atoms, and / or optionally substituted perbenzoic acids. Suitable materials have O-acyl and / or N-acyl groups of the specified number of carbon atoms, and / or optionally substituted benzoyl groups. Suitable substances include, but are not limited to, polyacylated alkylenediamines, particularly tetraacetylethylenediamine (TAED), acylated triazine derivatives, particularly 1,5-diacetyl-2,4-dioxohexahydro-1,3,5-triazine (DADHT), acylated glycolurils, particularly tetraacetylglycoluril (TAGU), N-acylimides, particularly N-nonanoylsuccinimide (NOSI), acylated phenolsulfonates, particularly n-nonanoyl- or isononanoyloxybenzenesulfonate (n- or iso-NOBS), carboxylic anhydrides, particularly phthalic anhydride, acylated polyhydric alcohols, particularly triacetin, ethylene glycol diacetate and 2,5-diacetoxy-2,5-dihydrofuran, and also triethyl acetylcitrate (TEAC).

[0101] In embodiments that include a fabric softener as an active agent, various rinse-off fabric softeners, particularly the fine smectite clays of U.S. Patent No. 4,062,647, the entireties of which are incorporated herein by reference, and other softener clays known in the art, can be used to provide fabric softening benefits along with fabric cleaning, if desired. Clay softeners can be used in combination with amine and cationic softeners, for example, as disclosed in U.S. Patent Nos. 4,375,416 and 4,291,071, the entireties of which are incorporated herein by reference.

[0102] In embodiments, the active agent may include a germicide. Germicides suitable for use herein may include, but are not limited to, hydrogen peroxide, inorganic peroxides and their precursors, sodium metabisulfite, quaternary ammonium cation-based compounds, chlorine, activated carbon, and hypochlorite.

[0103] In embodiments, the active agent may include a surfactant. Surfactants suitable for use herein include, but are not limited to, propylene glycol, diethylene glycol, monoethanolamine, polyoxyethylated polyoxypropylene glycol, alcohol ethoxylates, alkylphenol ethoxylates, tertiary acetylenic glycols and alkanolamides (non-ionic), polyoxyethylated amines, quaternary ammonium salts and quaternized polyoxyethylated amines (cationic), alkali metal salts of higher fatty acids containing about 8 to 24 carbon atoms, alkyl sulfates, alkyl polyethoxylates, tertiary acetylenic glycol ... The lactylate sulfates and alkylbenzenesulfonates (anionic), amine oxides, N-alkylbetaines and sulfobetaines (zwitterionic), dioctyl sodium sulfosuccinate, lactylated fatty acid esters of glycerin and propylene glycol, lactylic acid esters of fatty acids, sodium alkyl sulfates, polysorbate 20, polysorbate 60, polysorbate 65, polysorbate 80, lecithin, acetylated fatty acid esters of glycerin and propylene glycol, and acetylated esters of fatty acids, and combinations thereof.

[0104] The active agent may be solid or liquid. An active agent that is solid may have an average particle size (e.g., Dv50) of at least about 0.01 μm, or, for example, a size ranging from about 0.01 μm to about 2 mm. A liquid active agent may be applied directly to the nonwoven web, mixed with a carrier powder, or microencapsulated. In embodiments that include a carrier powder, the average particle size of the carrier powder may be at least about 0.01 μm, or, for example, a size ranging from about 0.01 μm to about 2 mm.

[0105] In one class of embodiments, the active agent is encapsulated to allow controlled release of the active agent.Suitable microcapsules may comprise or be made from one or more of melamine formaldehyde, polyurethane, urea formaldehyde, chitosan, polymethylmethacrylate, polystyrene, polysulfone, polytetrahydrofuran, gelatin, gum arabic, starch, polyvinylpyrrolidone, carboxymethylcellulose, hydroxyethylcellulose, methylcellulose, arabinogalactan, polyvinyl alcohol, polyacrylic acid, ethylcellulose, polyethylene, polymethacrylate, polyamide, poly(ethylene vinyl acetate), cellulose nitrate, silicone, poly(lactide-co-glycolide), paraffin, carnauba, spermaceti, beeswax, stearic acid, stearyl alcohol, glyceryl stearate, shellac, cellulose acetate phthalate, zein, and combinations thereof. In one type of embodiment, the microcapsules are characterized by an average particle size (e.g., Dv50) of at least about 0.1 microns, or, for example, in the range of about 0.1 microns to about 200 microns. In alternative embodiments, the microcapsules may form agglomerates of individual particles, for example, the individual particles have an average particle size of at least about 0.1 microns, or, for example, in the range of about 0.1 microns to about 200 microns.

[0106] The treated fibers can be formed by any process known in the art, such as wet chill gel spinning, thermoplastic fiber spinning, meltblown, spunbond, electrospinning, rotary spinning, continuous filament manufacturing techniques, tow fiber manufacturing techniques, and combinations thereof.

[0107] In an embodiment, the fibers include fibers formed by wet chill gel spinning, meltblown, spunbond, or a combination thereof. In an embodiment, the fibers include fibers formed by wet chill gel spinning. In an embodiment, the fibers include water-soluble fibers and the nonwoven web prepared therefrom is formed by a continuous meltblown process. In an embodiment, the fibers include water-soluble fibers and the nonwoven web prepared therefrom is formed by a continuous spunbond process. It is standard in the art to refer to fibers and nonwoven webs by the process used to prepare them. Thus, any reference herein to, for example, "meltblown fibers" or "carded nonwoven webs" should not be understood as a product-by-process limitation to a particular meltblown or carding process, but rather, should be understood simply to identify a particular fiber or web. Thus, processing terms may be used to distinguish between fibers and / or nonwoven webs without limiting the stated fibers and / or nonwoven webs to preparation by any particular process.

[0108] The fibers to be treated can be formed as bicomponent fibers. As used herein, unless otherwise specified, "bicomponent fibers" does not refer to fibers that contain a blend of fiber-forming materials, but rather to fibers that contain two or more distinct regions of fiber-forming materials, with the composition of the fiber-forming materials differing from region to region. Examples of bicomponent fibers include, but are not limited to, core-sheath (or core-shell) bicomponent fibers, islands-in-the-sea bicomponent fibers, and side-by-side bicomponent fibers. Core-sheath bicomponent fibers generally include a core having a first composition of fiber-forming materials (e.g., a single fiber-forming material or a first blend of fiber-forming materials) and a sheath having a second composition of fiber-forming materials (e.g., a single fiber-forming material different from the core material, or a second blend of fiber-forming materials different from the first blend of fiber-forming materials of the core). Islands-in-the-sea bicomponent fibers generally include a first continuous "sea" region having a first composition of fiber-forming materials, and discrete "island" regions dispersed therein having a second composition of fiber-forming materials different from the first composition. Side-by-side bicomponent fibers generally include a first region along the length of the fiber that includes a first composition of fiber-forming material and at least an adjacent second region along the length of the fiber that includes a second composition of fiber-forming material that is different from the first composition.

[0109] The shape of the fibers is not particularly limited and may have a cross-sectional shape including, but not limited to, round, elliptical (also called ribbon), triangular (also called delta), trilobal, and / or other multilobal shapes (FIG. 1). It is understood that the shape of the fibers need not be perfectly geometric, for example, a fiber having a round cross-sectional shape need not have a perfect circle as a cross-sectional area, and a fiber having a triangular cross-sectional shape will generally have rounded corners.

[0110] It is understood that the diameter of a fiber refers to the cross-sectional diameter of the fiber along its longest cross-sectional axis. When a fiber is described as having (or not having) a particular diameter, unless otherwise specified, it is intended that the particular diameter is the average diameter of the particular fiber type being referenced, i.e., a plurality of fibers prepared from a polyvinyl alcohol fiber-forming material has an arithmetic average fiber diameter across the plurality of fibers. In the case of shapes that are typically not considered to have a "diameter", such as triangular or multi-lobal shapes, the diameter refers to the diameter of a circle that encircles the fiber shape (Figure 1).

[0111] The fibers of the present disclosure may have a diameter in the range of about 10 microns to 300 microns, e.g., at least 10 microns, at least 15 microns, at least 20 microns, at least 25 microns, at least 50 microns, at least 100 microns, or at least 125 microns, and up to about 300 microns, up to about 275 microns, up to about 250 microns, up to about 225 microns, up to about 200 microns, up to about 100 microns, up to about 50 microns, up to about 45 microns, up to about 40 microns, or up to about 35 microns, e.g., from about 10 microns to about 300 microns, from about 50 microns to about 300 microns, from about 100 microns to about 300 microns, from about 10 microns to about 50 microns, from about 10 microns to about 45 microns, or from about 10 microns to about 40 microns. In an embodiment, the fibers may have a diameter of more than 100 microns to about 300 microns. In an embodiment, the fibers comprise cellulose and have a diameter ranging from about 10 microns to about 50 microns, about 10 microns to about 30 microns, about 10 microns to about 25 microns, about 10 microns to about 20 microns, or about 10 microns to about 15 microns. In an embodiment, the fibers comprise a water-soluble fiber-forming material and have a diameter ranging from about 50 microns to about 300 microns, about 100 microns to about 300 microns, about 150 microns to about 300 microns, or about 200 microns to about 300 microns. In an embodiment, the diameter of the plurality of water-soluble fibers used to prepare the nonwoven web of the present disclosure has a substantially uniform diameter. As used herein, a fiber diameter is "substantially uniform" when the diameter variation between fibers is less than 10%, e.g., 8% or less, 5% or less, 2% or less, or 1% or less. Fibers having a substantially uniform diameter can be prepared by wet chill gel spinning or thermoplastic fiber spinning. Additionally, if a blend of fiber types is used, the average diameter of the fiber blend can be determined using a weighted average of the individual fiber types.

[0112] The fibers of the present disclosure may be of any length. In embodiments, the length of the fibers may range from about 20 mm to about 100 mm, from about 20 to about 90, from about 30 mm to about 80 mm, from about 10 mm to about 60 mm, or from about 30 mm to about 60 mm, such as at least about 30 mm, at least about 35 mm, at least about 40 mm, at least about 45 mm, or at least about 50 mm, and up to about 100 mm, up to about 95 mm, up to about 90 mm, up to about 80 mm, up to about 70 mm, or up to about 60 mm. In embodiments, the length of the fibers can be less than about 30 mm, or from about 0.25 mm to less than about 30 mm, for example, at least about 0.25 mm, at least about 0.5 mm, at least about 0.75 mm, at least about 1 mm, at least about 2.5 mm, at least about 5 mm, at least about 7.5 mm, or at least about 10 mm, and up to about 29 mm, up to about 28 mm, up to about 27 mm, up to about 26 mm, up to about 25 mm, up to about 20 mm, or up to about 15 mm. The fibers can be prepared to any length by cutting and / or crimping the extruded polymer mixture. In embodiments, the fibers can be continuous filaments prepared by processes such as, for example, spunbond, meltblown, electrospinning, and rotary spinning, and the continuous filaments are prepared and provided directly in web form. Additionally, when a blend of fiber types is used, the average length of the fibers can be determined using a weighted average of the individual fiber types.

[0113] The fibers of the present disclosure may have any length to diameter (L / D) ratio. In embodiments, the length to diameter ratio of the fibers may be greater than about 2, greater than about 3, greater than about 4, greater than about 6, greater than about 10, greater than about 50, greater than about 60, greater than about 100, greater than about 200, greater than about 300, greater than about 400, or greater than about 1000. Advantageously, the tactile feel of the nonwoven web can be controlled using the L / D ratio of the fibers in the nonwoven composition and the respective amounts of fibers having various L / D ratios. Generally, as the L / D of the fibers decreases, the stiffness and bending resistance increase and the hand becomes rougher. The fibers of the present disclosure generally impart a rough feel to the nonwoven webs comprising them when the fibers have a low L / D ratio in the range of about 0.5 to about 15, or about 0.5 to about 25, or about 1 to about 5. Such low L / D fibers may be provided in the nonwoven web in an amount ranging from about 0 to about 50 wt.%, for example, from about 0.5 wt.% to about 25 wt.%, or from about 1 wt.% to about 15 wt.%, based on the total weight of fibers in the nonwoven web. If the amount of low L / D fibers in the nonwoven web is not known, the amount can be estimated by visual inspection of a photomicrograph of the nonwoven web. As shown in FIG. 6, a population of fibers having visibly larger diameters and shorter break rates can be observed based on the total fiber population. FIG. 6A is a photomicrograph of a nonwoven web having 0% low L / D fibers and a softness rating of 1, while FIG. 6B is a photomicrograph of a nonwoven web having 25% low L / D fibers and a softness rating of 5.

[0114] The fibers of the present disclosure may have any tenacity. The tenacity of a fiber correlates with the coarseness of the fiber. Generally, as the tenacity of a fiber decreases, the coarseness of the fiber increases. The fibers of the present disclosure may have a tenacity of about 1 to about 100 cN / dtex, or about 1 to about 75 cN / dtex, or about 1 to about 50 cN / dtex, or about 1 to about 45 cN / dtex, or about 1 to about 40 cN / dtex, or about 1 to about 35 cN / dtex, or about 1 to about 30 cN / dtex, or about 1 to about 25 cN / dtex, or about 1 to about 20 cN / dtex, or about 1 to about 15 cN / dtex, or about 1 to about 10 cN / dtex, or about 1 to about 5 cN / dtex, or about 3 to about 8 cN / dtex, or about 4 to about 8 cN / dtex. dtex, or about 6 to about 8 cN / dtex, or about 4 to about 7 cN / dtex, or about 10 to about 20, or about 10 to about 18, or about 10 to about 16, or about 1 cN / dtex, about 2 cN / dtex, about 3 cN / dtex, about 4 cN / dtex, about 5 cN / dtex, about 6 cN / dtex, about 7 cN / dtex, about 8 cN / dtex, about 9 cN / dtex, about 10 cN / dtex, about 11 cN / dtex, about 12 cN / dtex, about 13 cN / dtex, about 14 cN / dtex, or about 15 cN / dtex. In embodiments, the fibers may have a toughness of about 3 cN / dtex to about 10 cN / dtex. In embodiments, the fibers may have a toughness of about 7 cN / dtex to about 10 cN / dtex. In embodiments, the fibers may have a tenacity of from about 4 cN / dtex to about 8 cN / dtex.In embodiments, the fibers may have a tenacity of from about 6 cN / dtex to about 8 cN / dtex.

[0115] The fibers of the present disclosure may have any fineness. Fiber fineness correlates to how much fiber is present in the cross section of a yarn of a given thickness. Fiber fineness is the ratio of fiber mass to length. The main physical unit of fiber fineness is 1 tex, which is equal to 1000m of fiber with a weight of 1g. Typically, the unit dtex is used, which represents 1g / 10,000m of fiber. Fiber fineness can be selected to provide a nonwoven web with suitable hardness / hand of the nonwoven web, torsional stiffness, light reflection and interaction, absorption of dyes and / or other actives / additives, ease of fiber spinning in the manufacturing process, and uniformity of the finished article. In general, as fiber fineness increases, the nonwoven fabric obtained therefrom exhibits higher uniformity, improved tensile strength, extensibility, and luster. Furthermore, without intending to be bound by theory, it is believed that finer fibers result in slower dissolution times compared to larger fibers based on density. Furthermore, without intending to be bound by theory, when a blend of fibers is used, the average fiber fineness can be determined using a weighted average of the individual fiber components. The fibers can be characterized as very fine (dtex≦1.22), fine (1.22≦dtex≦1.54), medium (1.54≦dtex≦1.93), slightly coarse (1.93≦dtex≦2.32), and coarse (dtex≧2.32). The nonwoven webs of the present disclosure can include very fine, fine, medium, slightly coarse, or combinations thereof. In an embodiment, the fibers have a fineness in the range of about 1 dtex to about 10 dtex, about 1 dtex to about 7 dtex, about 1 dtex to about 5 dtex, about 1 dtex to about 3 dtex, or about 1.7 dtex to about 2.2 dtex. In an embodiment, the fibers have a fineness of about 1.7 dtex. In an embodiment, the fibers have a fineness of about 2.2 dtex.

[0116] Wet-cooled gel spinning

[0117] In embodiments, the fibers of the present disclosure are formed according to a wet cryogel spinning process, the wet cryogel spinning process comprising: (a) dissolving a fiber-forming material (polymer) in a solution to form a polymer mixture, the polymer mixture optionally including an auxiliary agent; (b) extruding the polymer mixture through a spinneret nozzle into a solidification bath to form an extruded polymer mixture; (c) passing the extruded polymer mixture through a solvent exchange bath; (d) optionally wet-stretching the extruded polymer mixture; and (e) finishing the extruded polymer mixture to provide fibers. Includes.

[0118] The solvent in which the fiber-forming polymer is dissolved may suitably be any solvent in which the polymer is soluble. In embodiments, the solvent in which the polymer is dissolved comprises a polar aprotic solvent. In embodiments, the solvent in which the polymer is dissolved comprises dimethylsulfoxide (DMSO).

[0119] The solidification bath generally includes a cooled solvent to gel the extruded polymer mixture. The solidification bath generally can be any temperature that promotes solidification of the extruded polymer mixture. The solidification bath can include a mixture of solvents in which the polymer is soluble and solvents in which the polymer is insoluble. The solvent in which the polymer is insoluble is generally the primary solvent, and the solvent in which the polymer is insoluble constitutes more than 50% of the mixture.

[0120] After passing through the solidification bath, the extruded polymer mixture gel may be passed through one or more solvent exchange baths. Solvent exchange baths are provided to exchange a solvent in which the polymer is soluble for a solvent in which the polymer is insoluble to further solidify the extruded polymer mixture and exchange the solvent in which the polymer is soluble for a more easily evaporated solvent, thereby reducing drying time. The solvent exchange baths may include a series of solvent exchange baths having a gradient of solvents in which the polymer is soluble and solvents in which the polymer is insoluble, a series of solvent exchange baths having only a solvent in which the polymer is insoluble, or a single solvent exchange bath having only a solvent in which the polymer is insoluble.

[0121] The finished fiber is sometimes referred to as staple fiber, short cut fiber, or pulp. In an embodiment, the finishing process includes drying the extruded polymer mixture. In an embodiment, the finishing process includes cutting or crimping the extruded polymer mixture to form individual fibers. Wet drawing of the extruded polymer mixture results in a substantially uniform diameter of the extruded polymer mixture, and therefore the fibers cut therefrom. Drawing is distinct from extrusion, as is well known in the art. In particular, extrusion refers to the process of making fibers by forcing a resin mixture through a spinneret head, while drawing refers to mechanically drawing the fiber in the machine direction to improve polymer chain orientation and crystallinity so as to increase fiber strength and toughness.

[0122] In embodiments in which the fibers are prepared from a wet chill gel spinning process, the fiber-forming polymer can generally be any fiber-forming polymer or blend thereof, e.g., two or more different polymers, as generally described herein. In a refinement of the foregoing embodiment, the polymer(s) can be, for example, from 10 to 10,000,000, e.g., at least 10, at least 20, at least 50, at least 100, at least 200, at least 300, at least 400, at least 500, at least 750 or at least 1000 and up to 10,000,000, up to 5,000,000, up to 2,500,000, up to 1,000,000, up to 900,000, up to 750,000, up to 500,000, up to 250,000, up to 100,000, up to 90,000, up to 75,000, The degree of polymerization (DP) may be in the range of 0, up to 50,000, up to 25,000, up to 12,000, up to 10,000, up to 5,000, or up to 2,500, for example, 1000 to about 50,000, 1000 to about 25,000, 1000 to about 12,000, 1000 to about 5,000, 1000 to about 2,500, about 50 to about 12,000, about 50 to about 10,000, about 50 to about 5,000, about 50 to about 2,500, about 50 to about 1000, about 50 to about 900, about 100 to about 800, about 150 to about 700, about 200 to about 600, or about 250 to about 500. In an embodiment, the DP is at least 1,000. In embodiments, the fiber-forming polymer comprises a polyvinyl alcohol polymer having a degree of polymerization (DP) in the range of 1000 to about 50,000, 1000 to about 25,000, 1000 to about 12,000, 1000 to about 5,000, 1000 to about 2,500, about 50 to about 12,000, about 50 to about 10,000, about 50 to about 5,000, about 50 to about 2,500, about 50 to about 1000, about 50 to about 900, about 100 to about 800, about 150 to about 700, about 200 to about 600, or about 250 to about 500. In embodiments, the fiber-forming polymer comprises polyvinyl alcohol having a DP in the range of 1000 to about 50,000, 1000 to about 25,000, 1000 to about 12,000, 1000 to about 5,000, or 1000 to about 2,500.

[0123] The wet chill gel spinning process advantageously provides one or more advantages, such as providing fibers containing a blend of water-soluble polymers, providing control over the diameter of the fiber, providing a relatively large diameter fiber, providing control over the length of the fiber, providing control over the tenacity of the fiber, providing a high tenacity fiber, providing a fiber from a polymer having a high degree of polymerization, and / or providing a fiber that can be used to provide a self-supporting nonwoven web. Continuous processes such as spunbonding, meltblown, electrospinning, and rotary spinning generally do not allow blending water-soluble polymers (e.g., due to the difficulty in matching the melt index of various polymers), forming fibers with a large diameter (e.g., greater than 50 microns), controlling the length of the fiber, providing a high tenacity fiber, or using a polymer with a high degree of polymerization. Furthermore, the wet chill gel spinning process advantageously is not limited to only melt-processable polymers, and therefore can obtain fibers made from fiber-forming materials with very high molecular weights, high melting points, low melt flow indexes, or combinations thereof, providing fibers with stronger physical properties and different chemical functionalities compared to fibers prepared by heated extrusion processes.

[0124] Methods for preparing staple and continuous fibers are well known in the art. When staple or continuous fibers are carded, the nonwoven web is bonded. Methods for bonding staple fibers are well known in the art and can include air bonding (heat), calendar bonding (heat and pressure) and by chemical bonding. The nonwoven webs of the present disclosure can be thermally or chemically bonded. Nonwoven webs can generally be porous with a variety of pore sizes, morphologies and web inhomogeneities. The physical properties of the fibers and the type of bonding can affect the porosity of the resulting nonwoven web. Calendar bonding is achieved by applying heat and pressure and typically maintains the pore size, shape and alignment produced by the carding process. The conditions for calendar bonding can be easily determined by one skilled in the art. In general, if the heat and / or pressure applied is too low, the fibers will not bond sufficiently to form a self-supporting web, and if the heat and / or pressure is too high, the fibers will begin to fuse together. Fiber chemistry determines the upper and lower limits of heat and / or pressure for calendar bonding. Without intending to be bound by theory, it is believed that at temperatures above 235°C, polyvinyl alcohol-based fibers decompose. Methods of embossing for calendar bonding of fibers are known. Embossing can be single-sided embossing or double-sided embossing. Typically, embossing of water-soluble fibers includes single-sided embossing using a single embossing roll consisting of a regular circular array and a steel roll with a flat surface. As embossing increases (e.g., surface features are imparted to the web), the surface area of ​​the web increases. Without intending to be bound by theory, it is expected that as the surface area of ​​the web increases, the solubility of the web increases. Thus, the solubility properties of a nonwoven web can be advantageously adjusted by modifying the surface area through embossing.

[0125] In contrast to calendar bonding, chemical bonding uses a binder solution of waste polymers left over from fiber preparation to coat carded fibers under pressure, which may result in smaller and less regular pores compared to carded pores. The solvent may be any solvent that solubilizes the binder. The solvent of the chemical bonding solution is water in some embodiments. Without intending to be bound by theory, it is believed that if the polymer solution used for chemical bonding is concentrated enough and / or sufficient pressure is applied, a non-porous water-dispersible nonwoven web may be formed. The solvent used for chemical bonding induces partial solubilization of the fibers present in the web, causing the fibers to weld and bond together. The polyvinyl alcohol binder provided in the solution aids in the welding process to provide a more mechanically robust web. The temperature of the polymer solution is not particularly limited and may be provided at room temperature (about 23°C).

[0126] In some embodiments, a second layer of fibers can be used to bond the nonwoven web. Without intending to be bound by theory, it is believed that fibers prepared by meltblown process, such as water-soluble fibers, can be used to bond the nonwoven web using an in-line process. In particular, the nonwoven web passes through a meltblown process station, so that meltblown fibers are deposited after melt extrusion, and as the meltblown fibers cool and solidify, they can bond to each other and to the nonwoven web on which they are deposited. The meltblown fibers can be micro to nano-scale in length, and can be provided on the nonwoven web such that the meltblown fibers constitute about 15% by weight, about 12% by weight, about 10% by weight, about 8% by weight, about 6% by weight, or about 5% by weight of the final nonwoven web, based on the total weight of the fibers in the final nonwoven web. Without intending to be bound by theory, it is believed that the inclusion of about 5% to about 15% meltblown fibers can increase the mechanical integrity of the nonwoven web without substantially changing the solubility characteristics of the nonwoven web. Generally, when using polyvinyl alcohol fiber-forming materials to prepare meltblown fibers, the polyvinyl alcohol polymer can be a homopolymer or a copolymer, since the meltblown process requires a polymer with low viscosity and high melt flow index.

[0127] Pore ​​size can be determined using high magnification ordered surface analysis techniques including, but not limited to, Brunauer-Emmett-Teller theory (BET), small angle X-ray scattering (SAXS) and molecular adsorption.

[0128] In general, the fibers of the present disclosure can be formed by any fiber processing known in the art and then treated by post-processing hydrolysis.

[0129] The present disclosure provides a method for treating fibers comprising hydrolyzable polymers, such as polymers comprising at least one of vinyl acetate or vinyl alcohol moieties as described herein. In an embodiment, the method comprises mixing a fiber comprising such a polymer having a degree of hydrolysis less than 100% with a hydrolysis agent solution to increase the degree of hydrolysis of at least a portion of the fiber. The hydrolysis agent solution may comprise a hydrolysis agent and a solvent. The degree of hydrolysis of the fiber after mixing with the hydrolysis agent solution can be determined according to the titration method or attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopy disclosed herein. The titration method determines the average degree of hydrolysis for the fiber. For fibers characterized by a constant degree of hydrolysis across the cross-section of the fiber, the constant degree of hydrolysis is the average degree of hydrolysis for the fiber. For fibers characterized by a cross-section of the fiber having a core-sheath type or gradient distribution of degrees of hydrolysis, the titration test provides the average degree of hydrolysis across all cross-sections of the fiber. As used herein, unless otherwise specified, at least a portion of the fiber has an increased degree of hydrolysis if any portion of the fiber (e.g., exterior, sheath, interior) has an increased degree of hydrolysis after mixing compared to the degree of hydrolysis of the starting fiber. It is understood that the increase in the degree of hydrolysis to any portion of the fiber results in an increase in the average degree of hydrolysis of the fiber as determined by titration. Thus, it is understood that the degree of hydrolysis of at least a portion of the polymer in the fiber is increased if the average degree of hydrolysis of the fiber is higher after mixing the fiber with the hydrolysis agent solution compared to the average degree of hydrolysis of the fiber before mixing, as determined by titration. The ATR-FTIR technique provides an accurate measurement of the degree of hydrolysis at the sample surface based on the signal corresponding to chemical groups such as carbonyl groups.

[0130] Generally, the mixing may include immersing the fibers in the hydrolysis agent solution. In embodiments, the mixing may include agitating the mixture of the fibers and the hydrolysis agent solution.

[0131] In an embodiment, the method includes mixing the hydrolysis agent solution and the fiber under conditions sufficient to provide a predetermined degree of hydrolysis and / or a predetermined increase in the degree of hydrolysis to the fiber. In general, the degree of hydrolysis of the treated fiber and / or the increase in the degree of hydrolysis of the treated fiber can be designed and controlled by modifying the reaction conditions. The reaction conditions that can be modified to provide a predetermined degree of hydrolysis and / or an increase in the degree of hydrolysis include the selection of the hydrolysis agent, the selection of the concentration of the hydrolysis agent in the hydrolysis agent solution, the reaction (mixing) time, the reaction (mixing) temperature, the selection of a solvent for the hydrolysis agent solution, and the optional inclusion of an activator.

[0132] Generally, as the reaction time increases, the degree of hydrolysis increases. Thus, the reaction time can be selected to provide a desired increase in the degree of hydrolysis of the polymer that constitutes the fiber, e.g., a copolymer (or modified copolymer) having vinyl acetate and vinyl alcohol moieties. The reaction time can be from about 1 minute to about 48 hours, e.g., from about 1 minute to about 10 minutes (e.g., 1 minute, 2 minutes, 5 minutes, or 10 minutes), from about 2 minutes to about 36 hours, from about 2 minutes to about 24 hours, from about 2 minutes to about 12 hours, from about 2 minutes to about 6 hours, from about 2 minutes to about 4 hours, from about 2 minutes to about 2 hours, from about 2 minutes to about 1 hour, from about 5 minutes to about 1 hour, from about 5 minutes to about 2 hours, from about 5 minutes to about 5 hours, from about 5 minutes to about 10 hours, from about 5 minutes to about 12 hours, from about 5 minutes to about 24 hours, from about 1 hour to about 24 hours, from about 2 hours ... The mixing time may be from about 0 minutes to about 24 hours, from about 15 minutes to about 24 hours, from about 30 minutes to about 24 hours, from about 1 hour to about 24 hours, from about 2 hours to about 24 hours, from about 3 hours to about 24 hours, from about 4 hours to about 24 hours, from about 5 hours to about 24 hours, from about 6 hours to about 24 hours, from about 8 hours to about 24 hours, from about 10 hours to about 24 hours, from about 12 hours to about 24 hours, from about 12 hours to about 18 hours, from about 14 hours to about 20 hours, or from about 16 hours to about 24 hours. In an embodiment, the mixing time may be from about 2 minutes to about 48 hours. In an embodiment, the mixing time may be from about 12 to about 36 hours. In an embodiment, the mixing time may be from about 18 to about 28 hours.

[0133] In general, as the reaction temperature increases, the rate of hydrolysis increases. Thus, the reaction temperature, in combination with the reaction time, can be selected to provide a desired increase in the degree of hydrolysis of the polymer constituting the fiber, for example, a copolymer (or modified copolymer) having vinyl acetate and vinyl alcohol moieties. The reaction temperature is not particularly limited, so long as the fiber is not dissolved or decomposed and the solvent remains liquid under the heating conditions. The reaction temperature can be from about 10°C to about 200°C, about 10°C to about 190°C, about 10°C to about 180°C, about 10°C to about 170°C, about 10°C to about 160°C, about 10°C to about 150°C, about 10°C to about 140°C, about 10°C to about 130°C, about 10°C to about 120°C, about 10°C to about 110°C, about 10°C to about 100°C, about 10°C to about 90°C, about 10°C to about 80°C, about The reaction temperature may be from about 10°C to about 70°C, from about 10°C to about 60°C, from about 10°C to about 50°C, from about 10°C to about 40°C, from about 10°C to about 30°C, from about 20°C to about 100°C, from about 20°C to about 90°C, from about 20°C to about 80°C, from about 30°C to about 100°C, from about 30°C to about 90°C, from about 30°C to about 80°C, from about 30°C to about 70°C, from about 30°C to about 60°C, or from about 30°C to about 50°C. Without intending to be bound by theory, it is believed that at high temperatures, as the polarity of the solvent increases, the fibers begin to swell, gel and / or dissolve. Thus, the reaction temperature can be selected such that, in combination with the solvent, the fibers remain insoluble and do not decompose. In an embodiment, the method further comprises the step of heating the mixture of fibers and hydrolyzing agent solution.

[0134] The selection of hydrolysis agent can affect the rate of hydrolysis reaction. Thus, the hydrolysis agent can be selected in combination with the reaction time and temperature to provide the desired increase in the degree of hydrolysis of the polymer that constitutes the fiber, for example, a copolymer (or modified copolymer) having vinyl acetate and vinyl alcohol moieties. In embodiments in which the hydrolysis is carried out by acid- or base-catalyzed transesterification of esters or amides, the reaction rate can be modified based on the nucleophilic strength of the hydrolysis agent, and, as a secondary factor, the solubility of the hydrolysis agent in the solvent of the hydrolysis agent solution. In embodiments in which the hydrolysis is carried out by reduction of functional groups to -OH moieties, the reaction rate can be modified based on the reducing strength of the hydrolysis agent, and, as a secondary factor, the solubility of the hydrolysis agent in the solvent of the hydrolysis agent solution.

[0135] The hydrolysis agent may be any agent capable of hydrolyzing or reducing the functional groups of the polymer backbone to -OH moieties and / or catalyzing the same. Non-limiting examples of hydrolysis agents include, but are not limited to, metal hydroxides, metal hydrides, sulfites, sulfur dioxide, dithionates, thiosulfates, hydrazine, oxalic acid, formic acid, ascorbic acid, dithiothreitol, phosphites, hypophosphites, phosphorus acids, sulfuric acid, sulfonic acid, hydrochloric acid, ammonium hydroxide, water, and combinations thereof. In embodiments, the hydrolysis agent includes metal hydroxides, metal hydrides, sulfites, sulfur dioxide, dithionates, thiosulfates, hydrazine, oxalic acid, formic acid, ascorbic acid, dithiothreitol, phosphites, hypophosphites, phosphorus acids, sulfuric acid, sulfonic acid, hydrochloric acid, ammonium hydroxide, water, and combinations thereof. In embodiments, the hydrolysis agent comprises a metal hydroxide, a metal hydride, a sulfite, a sulfur dioxide, a dithionate, a thiosulfate, a hydrazine, an oxalic acid, a formic acid, an ascorbic acid, a dithiothreitol, a phosphite, a hypophosphite, a phosphorus acid, a sulfuric acid, a sulfonic acid, a hydrochloric acid, an ammonium hydroxide, or a combination thereof. In embodiments, the hydrolysis agent comprises a metal hydroxide, a metal hydride, a sulfite, a sulfur dioxide, a dithionate, a thiosulfate, a hydrazine, an oxalic acid, a formic acid, an ascorbic acid, a dithiothreitol, a phosphite, a hypophosphite, a phosphorus acid, a ammonium hydroxide, or a combination thereof. In embodiments, the hydrolysis agent comprises a metal hydroxide. In embodiments, the metal hydroxide hydrolysis agent comprises an alkali metal hydroxide, an alkaline earth metal hydroxide, a main group metal hydroxide, or a combination thereof. In embodiments, the metal hydroxide hydrolysis agent comprises sodium hydroxide, potassium hydroxide, calcium hydroxide, barium hydroxide, trialkyltin hydroxide, or a combination thereof. In embodiments, the metal hydroxide hydrolysis agent comprises sodium hydroxide, potassium hydroxide, or a combination thereof. In embodiments, the metal hydroxide hydrolysis agent comprises sodium hydroxide.

[0136] Generally, as the concentration of hydrolysis agent in the hydrolysis agent solution increases, the reaction rate increases. Thus, the hydrolysis agent concentration, in combination with the reaction time, reaction temperature, and selection of hydrolysis agent, can be selected to provide a desired increase in the degree of hydrolysis of the polymers that make up the fibers, e.g., copolymers of vinyl acetate and vinyl alcohol. Generally, the concentration of hydrolysis agent in the hydrolysis solution can be any concentration. Typically, the concentration is selected so that all of the hydrolysis agent provided is in solution. In embodiments, the hydrolysis agent can be provided in an amount of about 0.2% to about 75% (w / w), e.g., about 0.2% to about 75%, about 0.2% to about 50%, about 0.2% to about 25%, about 0.5% to about 20%, about 1% to about 18%, about 2% to about 16%, about 5% to about 15%, about 8% to about 12%, or about 10%, based on the weight of the solvent. In embodiments, the hydrolysis agent is provided in an amount of about 0.2% to about 25% (w / w), based on the weight of the solvent. In embodiments, the hydrolyzing agent is provided in an amount of about 2% to about 25% (w / w) based on the weight of the solvent, hi embodiments, the hydrolyzing agent is provided in an amount of about 5% to about 15% (w / w) based on the weight of the solvent.

[0137] The solvent of the hydrolysis agent solution can generally be any solvent in which the hydrolysis agent is soluble and in which the treated fiber is insoluble at the temperature at which the treatment is carried out and for the duration of time the fiber is in contact with the solvent. In an embodiment, the fiber is insoluble in the solvent before treatment. In an embodiment, the fiber is insoluble in the solvent during treatment. In an embodiment, the fiber is insoluble in the solvent after treatment. In general, the solvent can be selected to provide a desired increase in the degree of hydrolysis of the polymer that constitutes the fiber, for example, a copolymer of vinyl acetate and vinyl alcohol, in combination with the reaction time, reaction temperature, and the selection of the hydrolysis agent and its concentration. As the polarity of the solvent increases, the diffusion of the solvent into the polymer matrix of the fiber generally increases, which results in an increase in the diffusion of the hydrolysis agent into the polymer matrix. Without intending to be bound by theory, it is believed that as the polarity of the solvent increases, the degree of hydrolysis of the inner / core section of the fiber may increase, and the degree of hydrolysis may increase across the cross section of the fiber. Furthermore, without intending to be bound by theory, as the polarity of the solvent decreases, the diffusion of the solvent into the polymer matrix of the fiber generally decreases and the degree of hydrolysis may increase only in the polymer at the surface / exterior / sheath / shell portion of the fiber. Hydrolysis of the polymer of the fiber at the surface / exterior / sheath / shell portion of the fiber also results in an average increase in the degree of hydrolysis across the cross section of the fiber. Without intending to be bound by theory further, a combination of solvents may be used to provide a diffusion-controlled radial gradient of the degree of hydrolysis of the polymer of the treated fiber.

[0138] In embodiments, the solvent for the hydrolysis agent solution may be characterized by the Hansen Solubility Parameters (HSP). Without intending to be bound by theory, the three HSP values ​​dispersion, molar volume and hydrogen bonding are believed to be indicative of the miscibility of polyvinyl alcohol and therefore its solvation or swelling by a particular solvent, and furthermore, hydrogen bonding is the greatest predictor of these expected behaviors, with the sum of all parameters, H totalis also believed to be predictive. In general, if the HSP value of the solvent is lower than the HSP value of the polyvinyl alcohol, the greater the difference in HSP values ​​between the solvent and the polyvinyl alcohol, the lower the diffusivity of the solvent into the polyvinyl alcohol. Without intending to be bound by theory, total The value is H of polyvinyl alcohol. total It is believed that when the H of the solvent is about 4 to about 15 units lower than this value, the rate of solvent uptake and the diffusivity of the solvent into the polyvinyl alcohol are such that a gradient of solvent uptake, and therefore hydrolysis agent uptake, occurs, providing a gradient of hydrolysis degree of the fiber across the cross section, with a higher degree of hydrolysis in the surface regions compared to the inner core region. Without intending to be bound by theory, it is believed that the H total The value is H of polyvinyl alcohol. total It is believed that when the H of the solvent is about 4 to about 15 units higher than this value, the rate of solvent uptake and the diffusivity of the solvent into the polyvinyl alcohol are such that the solvent uptake, and therefore the hydrolysis agent uptake, occurs quickly, providing a uniform degree of hydrolysis across the cross-section of the polyvinyl alcohol fiber. Further, without intending to be bound by theory, it is believed that the H of the solvent is about 4 to about 15 units higher than this value, the rate of solvent uptake and the diffusivity of the solvent into the polyvinyl alcohol are such that the solvent uptake, and therefore the hydrolysis agent uptake, occurs quickly, providing a uniform degree of hydrolysis across the cross-section of the polyvinyl alcohol fiber. total The value of the fiber polyvinyl alcohol is H total If the value is more than 15 units lower than the H value, the diffusivity is restricted such that only the outer surface of the fiber is treated with the hydrolysis agent, and the H total The value of the fiber polyvinyl alcohol is H total If it is more than 15 units higher than this value, the solvent is considered to dissolve the polyvinyl alcohol of the fiber.

[0139] In an embodiment, the solvent comprises a polar solvent. In an embodiment, the solvent comprises octanol, heptanol, hexanol, pentanol, butanol, propanol, tetrahydrofuran, dichloromethane, acetone, ethanol, N-methylpyrrolidone, methanol, acetonitrile, ethylene glycol, N,N-dimethylformamide, glycerol, dimethylsulfoxide, formic acid, water, or a combination thereof. In an embodiment, the solvent comprises n-octanol, n-heptanol, n-hexanol, n-pentanol, n-butanol, isobutanol, sec-butanol, tert-butanol, n-propanol, isopropanol, acetone, ethanol, N-methylpyrrolidone, methanol, acetonitrile, N,N-dimethylformamide, dimethylsulfoxide, formic acid, water, or a combination thereof. In an embodiment, the solvent comprises n-propanol, acetone, ethanol, N-methylpyrrolidone, methanol, acetonitrile, N,N-dimethylformamide, dimethylsulfoxide, formic acid, water, or a combination thereof. In embodiments, the solvent comprises an alcohol that is liquid under the mixed conditions. In embodiments, the solvent comprises methanol. In embodiments, the solvent comprises methanol and at least one additional solvent. In embodiments, the solvent comprises methanol and water. In embodiments, the solvent comprises at least one of butanol, pentanol, hexanol, heptanol, and octanol in combination with water. In embodiments, the solvent comprises DMSO and water. In embodiments, the solvent comprises DMSO and water, the DMSO and water being provided in a weight ratio of about 40 / 60 to 80 / 20. Without intending to be bound by theory, it is believed that as the amount of water increases beyond 60% or the amount of DMSO increases beyond about 80%, the interaction of the respective solvent with the polyvinyl alcohol increases, resulting in increased swelling and gelling of the polymer.

[0140] In embodiments, the solvent comprises a non-polar solvent, hi embodiments, the solvent comprises hexane, cyclohexane, methylpentane, pentane, cyclopropane, dioxane, benzene, pyridine, xylene, toluene, diethyl ether, chloroform, or a combination thereof.

[0141] In an embodiment, the solvent comprises a mixture of a first solvent and a second solvent. In an embodiment, the first solvent comprises a polar solvent and the second solvent comprises a non-polar solvent. In an embodiment, the first solvent has a first dielectric constant and the second solvent has a second dielectric constant, the dielectric constant of the first solvent being higher than the dielectric constant of the second solvent. In an embodiment, the first dielectric constant is 5 or less, 4 or less, 3 or less, or 2 or less. In an embodiment, the second dielectric constant is greater than 5, greater than 7.5, greater than 10, greater than 15, greater than 18, greater than 20, greater than 25, or greater than 30. In an embodiment, the difference between the first dielectric constant and the second dielectric constant is at least 3, at least 5, at least 8, or at least 10. In embodiments where the solvent comprises a mixture of a first solvent and a second solvent, the first solvent and the second solvent may be provided in any ratio provided that the hydrolyzing agent is soluble in the mixture and the fibers are insoluble in the mixture before, during and after treatment. In embodiments, the first solvent and the second solvent may be provided in a weight ratio of about 99 / 1 to about 1 / 99, about 95 / 5 to about 5 / 95, about 90 / 10 to about 10 / 90, about 85 / 15 to about 15 / 85, about 80 / 20 to about 20 / 80, about 75 / 25 to about 25 / 75, about 70 / 30 to about 30 / 70, about 65 / 35 to about 35 / 65, about 60 / 40 to about 40 / 60, about 55 / 45 to about 45 / 55 or about 50 / 50.

[0142] In some embodiments, the first solvent is methanol and the second solvent is hexane. Methanol and hexane can be in any suitable weight ratio or volume ratio. For example, a solvent that comprises 10% by weight of methanol and 90% by weight of hexane catalyzes the secondary saponification of at least a portion of the fibers that comprise the polymer as described herein.

[0143] In an embodiment, the method of the present disclosure further comprises mixing an activator with the fiber and the hydrolysis agent solution. The activator may be any additive that facilitates the treatment of the fiber with the hydrolysis agent. The activator may include, for example, a catalyst that reduces the activation energy of the reaction between the polymer of the fiber and the hydrolysis agent, or a compound that facilitates the diffusion of the hydrolysis agent into the polymer matrix.

[0144] The reaction conditions can also be selected to engineer and control the solubility mechanism and / or absorption capacity and retention of the treated fibers. For example, the reaction conditions can be selected to provide fibers with cross-sections characterized by (a) a core-sheath structure in which the polymer in the sheath has a higher degree of hydrolysis than the polymer in the core (FIG. 2A), (b) an increasing radial gradient of the degree of hydrolysis of the polymer from the interior region to the surface region (FIG. 2B, FIG. 3), or (c) a consistent degree of hydrolysis across the cross-section (FIG. 2C), and the resulting fibers can have different solubility mechanisms (e.g., immediate release, delayed release, or triggered release) and / or absorption capacity and retention properties. The reaction conditions that can be altered to provide a given fiber structure include the selection of the hydrolysis agent, the selection of the concentration of the hydrolysis agent in the hydrolysis agent solution, the reaction (mixing) time, the reaction (mixing) temperature, the selection of a solvent for the hydrolysis agent solution, and the optional inclusion of an activator.

[0145] Fibers having a core-sheath structure can be prepared by treating fibers having a polymer with a degree of hydrolysis less than 100% as described herein with a hydrolysis agent solution under conditions sufficient to minimize radial diffusion of the solvent and hydrolysis agent into the inner core region of the fiber. Diffusion of the solvent and hydrolysis agent into the inner core region of the fiber can be minimized, for example, by selecting a short reaction time, a low reaction temperature, and / or including a non-polar solvent. In an embodiment, the blending of the disclosed method is carried out under conditions sufficient to provide a polyvinyl alcohol fiber having a cross-section characterized by a core-sheath structure in which the sheath polymer has a higher degree of hydrolysis than the core polymer. In an embodiment, conditions sufficient to provide a polyvinyl alcohol fiber having a cross-section characterized by a core-sheath structure in which the sheath polymer has a higher degree of hydrolysis than the core polymer include including in the hydrolysis agent solution a solvent having a dielectric constant of 20 or less, 18 or less, 14 or less, or 10 or less. In embodiments, conditions sufficient to provide polyvinyl alcohol fibers having a cross-section characterized by a core-sheath structure in which the sheath polymer has a higher degree of hydrolysis than the core polymer include mixing the fibers and hydrolyzing agent solution at a temperature in the range of about 10° C. to about 30° C., about 10° C. to about 25° C., or about 15° C. to about 25° C. In embodiments, conditions sufficient to provide polyvinyl alcohol fibers having a cross-section characterized by a core-sheath structure in which the sheath polymer has a higher degree of hydrolysis than the core polymer include mixing the fibers and hydrolyzing agent solution for a time of about 2 minutes to about 6 hours, about 2 minutes to about 4 hours, about 5 minutes to about 3 hours, about 10 minutes to about 2 hours, or about 15 minutes to about 1 hour.In embodiments, conditions sufficient to provide polyvinyl alcohol fibers having a cross-section characterized by a core-sheath structure, in which the polymer of the sheath has a higher degree of hydrolysis than the polymer of the core, include including a solvent in the hydrolyzing agent solution having a dielectric constant of 20 or less, 18 or less, 14 or less, or 10 or less, mixing the fibers and hydrolyzing agent solution at a temperature in the range of about 10° C. to about 30° C., about 10° C. to about 25° C., or about 15° C. to about 25° C., and mixing the fibers and hydrolyzing agent solution for a time of about 2 minutes to about 6 hours, about 2 minutes to about 4 hours, about 5 minutes to about 3 hours, about 10 minutes to about 2 hours, or about 15 minutes to about 1 hour. Such fibers having a cross-section characterized by a core-sheath structure in which the polymer of the sheath has a higher degree of hydrolysis than the polymer of the core may provide delayed release properties of an active material provided within the fiber, triggered release of an active material provided within the fiber, increased absorbency compared to fibers having a consistent degree of hydrolysis across the cross-section, and / or improved retention of absorbed fluid compared to fibers having a consistent degree of hydrolysis across the cross-section.

[0146] As used herein, unless otherwise specified, "delayed release" of an active material from a fiber means that the entire active material is not immediately released from the fiber when contacted with a solvent (usually water) under the conditions of the end use application of the fiber. For example, a fiber containing an active material and used in a laundry application may not immediately release the entire active material under washing conditions. Rather, the active material may diffuse out of the fiber over time. As used herein, unless otherwise specified, "triggered release" of an active material from a fiber means that no active material is released from the fiber until a triggering condition is met. For example, a fiber containing an active material and used in a laundry application may not release the active material until the wash water reaches a predetermined temperature and / or pH.

[0147] The triggering conditions may include, but are not limited to, temperature, pH, UV / VIS radiation, IR radiation, the presence of ions, the presence of a catalyst, or a combination thereof.

[0148] Without intending to be bound by theory, it is believed that fibers having a cross-section characterized by a core-sheath structure in which the polymer in the sheath has a higher degree of hydrolysis than the polymer in the core may have increased fluid absorption and / or retention compared to fibers having a consistent degree of hydrolysis across the cross-section because the presence of the sheath allows the core to expand when in contact with fluid, allowing for increased absorbent capacity without fiber collapse, and fluid is retained until the fiber is contacted with an inducing condition, such as immersion in hot water.

[0149] As the thickness of the sheath structure increases, the stability of a fiber having a core swollen and saturated with fluid increases, but the amount of polymer available in the core to absorb fluid decreases. The thickness of the sheath can be controlled by controlling the diffusion of the hydrolysis agent into the polymer structure of the fiber. It is understood that since the treatment of the inner portion of the fiber is diffusion controlled, the sheath can have a variation in thickness around the outer edge of the fiber, and the inner portion of the sheath can have a lower degree of hydrolysis of the polymer at the outer surface of the sheath, but a higher degree of hydrolysis than the polymer at the center of the fiber. Thus, in some embodiments, the cross section of the fiber can be characterized by a core-sheath structure and can be characterized as having an increasing gradient from the inner portion of the fiber to the outer portion of the fiber.

[0150] Fibers having a cross-section characterized by an increasing radial gradient structure can be prepared by treating a fiber having a polymer, such as a polyvinyl alcohol copolymer or modified copolymer, having a degree of hydrolysis less than 100% with a hydrolysis agent solution under conditions sufficient to modify the radial diffusion of the solvent and hydrolysis agent to the interior region of the fiber. In embodiments, polyvinyl alcohol fibers having a cross-section characterized by an increasing radial gradient structure from the interior region to the exterior region can be prepared by using multiple solvents with different diffusion rates (simultaneous or stepwise), varying the temperature during mixing to modify the diffusion rate of the solvent and hydrolysis agent into the fiber, and / or selecting a reaction time long enough to allow some hydrolysis agent to diffuse to the interior region and modify the degree of hydrolysis of the polymer, but not so long as to allow the polymer in the interior portion to hydrolyze to the same extent as the polymer in the exterior / surface portion. In embodiments, the mixing of the disclosed method is carried out under conditions sufficient to provide a fiber having a cross-section characterized by an increasing gradient of the degree of hydrolysis of the polymer from the interior region of the fiber to the surface region of the fiber. Such fibers having a cross-section characterized by an increasing gradient of degree of hydrolysis may provide delayed release properties of active material provided within the fiber, triggered release of active material provided within the fiber, increased absorbency, and / or improved retention of absorbed fluids compared to fibers having a consistent degree of hydrolysis across the cross-section.

[0151] Fibers having a cross-section characterized by a core-sheath structure and / or an increasing radial structure can have an active agent loaded in the core / inner region. The active material can be loaded in the core / inner region by contacting the fiber with a solution of the active agent and allowing the active agent solution to diffuse into the polymer structure, resulting in the core / inner region of the fiber absorbing the active agent solution and expanding. The active agent can be any active agent disclosed herein that is soluble in the active agent solution solvent. The solvent can be any solvent disclosed herein. Without intending to be bound by theory, it is believed that as the polarity of the solvent increases, the rate of diffusion into the core / inner region of the fiber increases. An exemplary solvent is water, provided that the water of the active agent solution is maintained at a temperature lower than the dissolution temperature of the polymer that constitutes the core / inner region of the fiber and the sheath / shell / external region of the fiber.

[0152] Fibers having a cross-section characterized by a polymer having the same degree of hydrolysis across the cross-section (entirely) can be prepared by treating a fiber having a polymer, such as a polyvinyl alcohol copolymer or modified copolymer, having a degree of hydrolysis less than 100%, with a hydrolysis agent solution under conditions sufficient to maximize radial diffusion of the solvent and hydrolysis agent into the inner core region of the fiber. Diffusion of the solvent and hydrolysis agent into the inner core region of the fiber can be maximized, for example, by selecting a long reaction time, a high reaction temperature, and / or including a highly polar solvent. In an embodiment, the blending of the disclosed method is carried out under conditions sufficient to provide a fiber having a cross-section characterized by a polymer having the same degree of hydrolysis across the cross-section.

[0153] Without intending to be bound by theory, for fibers that include polyvinyl alcohol copolymers or modified copolymers as fiber-forming materials, it is believed that the average degree of hydrolysis across the cross-section of the fiber conveys information about the solubility mechanism of the fiber and the absorption capacity of the fiber. In particular, without intending to be bound by theory, it is believed that as the average degree of hydrolysis across the cross-section of the fiber increases, the fiber is expected to survive longer in water with increasing water temperature. Furthermore, without intending to be bound by theory, it is believed that as the average degree of hydrolysis across the cross-section of the fiber increases, the absorption capacity of the fiber decreases.

[0154] Advantageously, as the degree of hydrolysis of the polymer in the surface region of the fiber increases relative to the degree of hydrolysis of the polymer in the interior region of the fiber, the bulk solubility of the fiber decreases, allowing for more precise tailoring of the solubility parameters of the fiber and the differing solubility characteristics of the fiber compared to simply selecting a fiber with a consistent degree of hydrolysis throughout the fiber.

[0155] The present disclosure further provides a method of treating a fiber comprising a hydrolyzable polymer, comprising contacting a surface of a fiber comprising a hydrolyzable polymer, such as a polymer comprising at least one of a vinyl acetate moiety or a vinyl alcohol moiety as described herein, having a degree of hydrolysis less than 100%, with a hydrolyzable agent solution to increase the degree of hydrolysis of the hydrolyzable polymer in an area of ​​the fiber comprising at least the surface of the fiber. In embodiments, the contacting can be by immersion, spraying, transfer coating, imbibing, foaming, brushing, rolling, moistening, vapor deposition, printing, or a combination thereof. The hydrolyzable polymer can be any hydrolyzable polymer disclosed herein. In embodiments, the hydrolyzable polymer comprises a polymer comprising at least one of a vinyl acetate moiety or a vinyl alcohol moiety, which can be selected from the group consisting of a polyvinyl acetate homopolymer, a polyvinyl alcohol copolymer, a modified polyvinyl alcohol copolymer, or a combination thereof. The hydrolyzable agent solution can comprise any hydrolyzable agent disclosed herein and any solvent disclosed herein. In an embodiment, the method may further include contacting the surface of the fiber with the hydrolysis agent solution after the fiber is formed as part of a continuous in-line process. For example, the fiber may be formed from the polymer mixture at a first station and then transferred to a second station to treat the surface of the fiber. In another example, the fiber may be treated in an apparatus including a polyvinyl alcohol fiber supply station, a polyvinyl alcohol fiber treatment station, and a polyvinyl alcohol fiber collection station. In an embodiment, the fiber is in motion during contact of the surface of the fiber. In an embodiment, the contacting of the surface of the fiber with the hydrolysis agent solution is performed in batches by a batch process. For example, the fiber may be prepared in bulk and treated with the hydrolysis agent prior to forming the fiber into a nonwoven web. In an embodiment, the fiber includes staple fiber, staple yarn, fiber fill, needle punch fabric, bonded fiber, or a combination thereof. In an embodiment, the fiber includes staple fiber. In an embodiment, the method further includes washing and drying the fiber after contacting the surface of the fiber with the hydrolysis agent solution.Washing may be by rinsing the fibers with a non-solvent Drying the fibers may be by air jet drying, stirring, vortexing or centrifugation.

[0156] Although the methods disclosed herein describe treating fibers to increase the degree of hydrolysis of at least a portion of the polymers that make up the fibers, it is understood that the fibers may be treated to decrease the degree of hydrolysis of at least a portion of the polymers that make up the fibers. Thus, the present disclosure further provides a method of acylation of at least a portion of a polyvinyl alcohol polymer, comprising mixing a fiber comprising a polyvinyl alcohol polymer with an acylating agent solution to decrease the degree of hydrolysis of at least a portion of the polyvinyl alcohol polymer in the fiber.

[0157] The mixing conditions can be any of those described herein for mixing fibers with a hydrolysis agent solution. Instead of a hydrolysis agent, the acylating agent solution includes an acylating agent. The mixing conditions can be selected to provide a predetermined degree of hydrolysis or a predetermined decrease in the degree of hydrolysis, as described herein for the method of increasing the degree of hydrolysis. Fibers treated with an acylating agent solution can have a cross-section characterized by a core-sheath structure in which the polymer in the sheath has a smaller degree of hydrolysis than the polymer in the core, a decreasing gradient of the degree of hydrolysis of the polymer from the interior region to the surface region, or a polymer with the same degree of hydrolysis across the cross-section.

[0158] An acylating agent can be any agent that, when contacted with a polymer having a pendant hydroxyl (-OH) or amine (-NR2), converts the hydrogen of the pendant hydroxyl or amine to an acyl group (RC(O)-). Suitable acylating agents include, but are not limited to, aldehydes, acyl anhydrides, acyl chlorides, and acyl coenzymes. In embodiments, the acylating agent comprises an aldehyde in the presence of an acid catalyst, such as hydrochloric acid. In embodiments, the acylating agent comprises acetic anhydride and / or acetyl chloride, optionally in the presence of a tertiary or aromatic amine base. In embodiments, the acylating agent comprises acetyl-coenzyme A (acetyl-CoA) in the presence of the enzyme acetyltransferase.

[0159] The present disclosure provides fibers treated according to the methods of the present disclosure.

[0160] The present disclosure provides a fiber having a surface region and an interior region, the fiber comprising a hydrolyzable polymer and having a cross-section characterized by the hydrolyzable polymer of the surface region having a higher degree of hydrolysis than the hydrolyzable polymer of the interior region. In an embodiment, the present disclosure provides a fiber having a surface region and an interior region, the fiber comprising a polymer comprising at least one of a vinyl acetate moiety or a vinyl alcohol moiety and having a cross-section characterized by the polymer of the surface region having a higher degree of hydrolysis than the polymer of the interior region.

[0161] The fibers of the present disclosure may have a fiber cross-section characterized by an increasing gradient of the degree of hydrolysis of the hydrolyzable polymer from the interior region to the surface region. In embodiments, the fibers of the present disclosure may have a fiber cross-section characterized by an increasing gradient of the degree of hydrolysis of the polymer from the interior region to the surface region.

[0162] As shown in FIG. 3, the present disclosure provides a fiber comprising a cross-section characterized by a core-sheath structure, the fiber comprising a first core region (designated 401 in FIG. 3) comprising a hydrolyzable polymer having a degree of hydrolysis less than 100%, and a second sheath region (designated 402 in FIG. 3) comprising a hydrolyzable polymer having a degree of hydrolysis higher than the hydrolyzable polymer of the first region. In an embodiment, the fiber may comprise a cross-section characterized by a core-sheath structure, the fiber comprising a first core region comprising a polyvinyl alcohol polymer having a degree of hydrolysis less than 100%, and a second sheath region comprising a polymer having a degree of hydrolysis higher than the polymer of the first region. In an embodiment, the fiber further comprises a third intermediate region (designated 403 in FIG. 3) disposed between the first and second regions and comprising a hydrolyzable polymer having a degree of hydrolysis higher than the hydrolyzable polymer of the first region and lower than the hydrolyzable polymer of the second region. In an embodiment, the hydrolyzable polymer of the first, second and third regions may comprise a polyvinyl alcohol polymer. In an embodiment, the fiber may include a plurality of third intermediate regions (designated 403A, 403B in FIG. 3) disposed between the first and second regions, and the cross-section of the fiber is characterized by an increasing gradient of the degree of hydrolysis of the hydrolyzable polymer from the first region to the second region. In an embodiment, the plurality of third intermediate regions may include a polyvinyl alcohol polymer, and the cross-section of the fiber is characterized by an increasing gradient of the degree of hydrolysis of the polymer from the first region to the second region.

[0163] In embodiments, the fibers of the present disclosure can have a difference in the degree of hydrolysis of the polymer in the first and second regions in the range of about 1%, about 2%, about 3%, about 5%, about 7%, about 10%, about 11%, about 12%, about 15%, about 18%, about 20%, about 23%, about 25%, about 27%, or about 29%, e.g., from 1% to 29%, from about 1% to about 25%, from about 1% to about 20%, from about 2% to about 18%, from about 2% to about 15%, from about 3% to about 12%, or from about 3% to about 11%. In embodiments, the cross-section of the fiber may be characterized by an average radius, and the second region may be about 0.5%, e.g., about 1%, about 2%, about 3%, about 5%, about 7%, about 9%, about 10%, about 12%, about 15%, about 20%, about 25%, about 50%, about 75%, about 80%, about 85%, about 90%, about 92%, about 94%, about 96%, or about 98%, e.g., about 1 % to about 98%, about 1% to about 90%, about 1% to about 75%, about 1% to about 50%, about 1% to about 25%, about 1% to about 20%, about 1% to about 15%, about 1% to about 12%, about 1% to about 10%, about 1% to about 8%, about 1% to about 6%, about 1% to about 5%, about 1% to about 4%, about 2% to about 25%, about 4% to about 25%, about 6% to about 35%, or about 8% to about 20%.

[0164] In an embodiment, the hydrolyzable polymer in the first, second and optional third regions has the same degree of polymerization. In an embodiment, the hydrolyzable polymer in the first, second and optional third regions comprises polyvinyl alcohol having the same degree of polymerization. In an embodiment, the hydrolyzable polymer in the first, second and optional third regions comprises modified polyvinyl alcohol polymer having the same degree of modification.

[0165] Although the fibers disclosed herein having a cross-section characterized by a core-sheath structure or gradient hydrolysis degree are described as having a higher degree of hydrolysis in the sheath and / or surface region of the fiber, it is understood that the fibers can be prepared (i.e., with an acylating agent) such that the degree of hydrolysis of the polymer in the sheath and / or surface region of the fiber is lower than the degree of hydrolysis of the polymer in the core and / or inner surface region. Thus, the present disclosure further provides a fiber having a surface region and an interior region, comprising a hydrolyzable polymer, and having a cross-section characterized by the hydrolyzable polymer in the surface region having a lower degree of hydrolysis than the hydrolyzable polymer in the interior region. In an embodiment, the present disclosure provides a fiber having a surface region and an interior region, comprising a polyvinyl alcohol polymer, and having a cross-section characterized by the polyvinyl alcohol polymer in the surface region having a lower degree of hydrolysis than the polyvinyl alcohol polymer in the interior region.

[0166] The fibers of the present disclosure may have a fiber cross-section characterized by a decreasing gradient of the degree of hydrolysis of the hydrolyzable polymer from the interior region to the surface region. In embodiments, the fibers of the present disclosure may have a fiber cross-section characterized by a decreasing gradient of the degree of hydrolysis of the polymer from the interior region to the surface region.

[0167] In the fibers having a surface region and an interior region provided herein, the polymer in the interior region has a first degree of hydrolysis and the polymer in the surface region has a second degree of hydrolysis higher than the first degree of hydrolysis. In some embodiments, the first degree of hydrolysis is in the range of about 79% to about 96% and the second degree of hydrolysis is in the range of about 88% to 100%, e.g., about 90% to 100%, about 88% to 99%, or about 90% to about 99%. In some embodiments, the first degree of hydrolysis is in the range of about 79% to about 92% and the second degree of hydrolysis is in the range of about 88% to about 96%.

[0168] The fibers have a dissolution time of less than 200 seconds in water at 23° C. The fibers have a shrinkage percentage along the longitudinal axis of the fiber in the range of 20% to 70% upon contact with water at a temperature in the range of 10° C. to 23° C. In embodiments, the polymer in the interior region has a glass transition temperature (T g ) and the polymer in the surface region has a T in the range of about 73° C. to about 85° C. g has.

[0169] In some embodiments, the fibers provided herein have a longitudinal axis and a cross-section perpendicular to the longitudinal axis of the fiber. The fiber further has a core and sheath structure along at least a portion of the longitudinal axis. The fiber includes a core region of the core and sheath structure that includes a polymer that includes at least one of a vinyl acetate moiety or a vinyl alcohol moiety, the polymer having a first degree of hydrolysis less than 100%.

[0170] The fiber has a sheath region of a core and sheath structure disposed radially outward from the core region in cross-section. The sheath region comprises a polymer comprising at least one of a vinyl acetate moiety or a vinyl alcohol moiety having a second degree of hydrolysis higher than the first degree of hydrolysis. As described herein, in embodiments, the polymer comprising at least one of a vinyl acetate moiety or a vinyl alcohol moiety comprises a polyvinyl alcohol homopolymer, a polyvinyl acetate homopolymer, a copolymer of vinyl acetate and vinyl alcohol, a modified polyvinyl alcohol copolymer, or a combination thereof. The difference between the first degree of hydrolysis and the second degree of hydrolysis is at least 1%. The difference between the first degree of hydrolysis and the second degree of hydrolysis may be in the range of 1% to 29%. The first and second degrees of hydrolysis may be within the ranges as described above. For example, in a sheath region having a second degree of hydrolysis in the range of about 88% to about 96%, the fiber has a dissolution time of less than 200 seconds in water at 23° C., the fiber has a drying shrinkage in the range of about 20% to about 70% after immersion in water at a temperature in the range of 10° C. to 23° C., and the polymer in the sheath region has a glass transition temperature in the range of about 73° C. to about 85° C. The core and sheath (or shell) structure may include at least one intermediate layer, as described above.

[0171] The present disclosure also provides a fiber comprising a first region and a second region. The first region comprises a polymer comprising at least one of a vinyl acetate moiety or a vinyl alcohol moiety having a first degree of hydrolysis less than 100%. The second region comprises a polymer comprising at least one of a vinyl acetate moiety or a vinyl alcohol moiety having a second degree of hydrolysis higher than the first degree of hydrolysis. In an embodiment, such a polymer comprises a polyvinyl alcohol homopolymer, a polyvinyl acetate homopolymer, a copolymer of vinyl acetate and vinyl alcohol, a modified polyvinyl alcohol copolymer, or a combination thereof. The fiber has a longitudinal axis. The first region forms a core region of the fiber along the longitudinal axis, and the second region forms a sheath region of the fiber surrounding at least a portion of the core region. The fiber has a cross section perpendicular to the longitudinal axis.

[0172] The fiber may further include an intermediate region disposed between the first and second regions of the cross-section. The intermediate region comprises a polymer having a third degree of hydrolysis higher than the first degree of hydrolysis and lower than the second degree of hydrolysis. The fiber has a cross-section perpendicular to the longitudinal axis. The fiber may further include a plurality of intermediate regions disposed between the first and second regions comprising the polymer, the cross-section having an increasing gradient of degree of hydrolysis from the first region to the second region. As described above, the difference between the first degree of hydrolysis and the second degree of hydrolysis is at least 1%, for example, in the range of 1% to 29%. The polymer in each of the first region, the second region and the third region may have the same degree of polymerization, for example, the polymer comprises a modified polyvinyl alcohol polymer having the same degree of modification.

[0173] Nonwoven Web

[0174] The nonwoven web of the present disclosure is generally a sheet-like structure having two outer surfaces, the nonwoven web comprising a plurality of fibers. As used herein, unless otherwise specified, the "outer surface" of the nonwoven web refers to the surface of the sheet-like structure shown at 100 and 101 in FIG. 7. The nonwoven web generally refers to an arrangement of fibers bonded together, the fibers being neither woven nor knitted. Generally, the plurality of fibers can be arranged in any orientation. In an embodiment, the plurality of fibers is randomly arranged (i.e., has no orientation). In an embodiment, the plurality of fibers is arranged in a unidirectional orientation. In an embodiment, the plurality of fibers is arranged in a bidirectional orientation. In some embodiments, the plurality of fibers is multidirectional, with different arrangements in different regions of the nonwoven web. In an embodiment, the nonwoven web can comprise a single type of water-soluble fiber. In an embodiment, the nonwoven web can comprise a single type of water-insoluble fiber. In embodiments, the nonwoven web may comprise a single type of water-soluble fiber and one or more different types of water-insoluble fiber. In embodiments, the nonwoven web may comprise one or more different types of water-soluble fiber and one or more different types of water-insoluble fiber. In embodiments, the nonwoven web may consist of water-soluble fiber or consist essentially of water-soluble fiber. In embodiments, the nonwoven web may consist of water-insoluble fiber or consist essentially of water-insoluble fiber. In some embodiments, the nonwoven web may comprise a single type of fiber-forming material (i.e., all fibers have the same composition of fiber-forming material), but may comprise fibers prepared by one or more fiber-forming processes, such as wet-cooled gel spinning, thermoplastic fiber spinning, meltblown, spunbond, or a combination thereof. In some embodiments, the nonwoven web may comprise a single type of fiber-forming material, and the fibers are made from a single fiber-forming process. In some embodiments, the nonwoven web may comprise two or more fiber-forming materials (e.g., a blend of fibers having fiber-forming materials of different compositions, fibers comprising a blend of fiber-forming materials, or both), and the fibers may be prepared by one or more fiber-forming methods, such as wet chill gel spinning, thermoplastic fiber spinning, meltblowing, spunbonding, or a combination thereof.In some embodiments, the nonwoven web may include two or more fiber-forming materials, and the fibers are made from a single fiber-forming process. In embodiments, the fibers of the nonwoven web may have substantially the same diameter or different diameters.

[0175] In embodiments in which the nonwoven web of the present disclosure comprises a blend of fibers including first and second fibers, the first and second fibers may have characteristics such as length to diameter (L / D ratio), tenacity, shape, stiffness, elasticity, solubility, melting point, glass transition temperature (T g ), fiber forming material, color, or a combination thereof.

[0176] As is well understood in the art, the term machine direction (MD) refers to the direction in which a nonwoven web travels as it is produced, for example, on a commercial nonwoven fabric making machine. Similarly, the term cross direction (CD) refers to the direction in the plane of the web perpendicular to the machine direction. In the context of nonwoven composite articles, wipes, absorbent articles, or other articles that include the nonwoven composite articles of the present disclosure, these terms refer to the corresponding direction of the article with respect to the nonwoven web used to produce the article.

[0177] The toughness of the nonwoven web may be the same or different from the toughness of the fibers used to prepare the web. Without intending to be bound by theory, it is believed that the toughness of the nonwoven web is related to the strength of the nonwoven web, the higher the toughness, the stronger the nonwoven web. In general, the toughness of the nonwoven web can be modified by using fibers with different toughness. The toughness of the nonwoven web can also be affected by processing. In general, the water-dispersible web of the present disclosure may have a relatively high toughness, i.e., the water-dispersible nonwoven web is a self-supporting web that can be used as the sole material to prepare an article and / or pouch. In an embodiment, the nonwoven web is a self-supporting web. In contrast, nonwoven webs prepared by meltblown, electrospinning and / or rotary spinning methods typically have low toughness and may not be self-supporting or may not be able to be used as the sole web to form an article or pouch. Thus, in some embodiments, the nonwoven web is not self-supporting and is used in combination with a second nonwoven web and / or a water-soluble film.

[0178] In embodiments, nonwoven webs of the present disclosure may have a ratio of machine direction toughness to cross direction toughness (MD:CD) in the range of about 0.5 to about 1.5, about 0.75 to about 1.5, about 0.80 to about 1.25, about 0.90 to about 1.1, or about 0.95 to about 1.05, or about 1. In embodiments, nonwoven webs of the present disclosure have a toughness ratio MD:CD of about 0.8 to about 1.25. In embodiments, nonwoven webs of the present disclosure have a toughness ratio MD:CD of about 0.9 to about 1.1. In embodiments, nonwoven webs of the present disclosure have a toughness of about 1. Without intending to be bound by theory, it is believed that as the toughness ratio MD:CD approaches 1, the durability of the nonwoven increases and imparts superior resistance to degradation to the nonwoven when stress is applied to the nonwoven during use, for example, by pulling / tugging of the nonwoven caused by scrubbing with a flushable wipe comprising a nonwoven web of the present disclosure or movement during donning of a wearable absorbent article.

[0179] The nonwoven web of the present disclosure may have a rough surface compared to water-soluble films, which results in less contact between the surface and the nonwoven web than between the surface and the water-soluble film. Advantageously, this surface roughness may improve consumer feel (i.e., cloth-like hand instead of rubber-like hand), improve aesthetics (i.e., less gloss than water-soluble films), and / or facilitate processability in thermoforming and / or vertical forming, filling and sealing and / or multi-chamber packet preparation, which require the web to be stretched along the surface of a processing machine / mold. Thus, the fibers must be rough enough to provide surface roughness to the resulting nonwoven web, without being so rough that it creates drag.

[0180] Nonwoven webs can be characterized by their basis weight. The basis weight of a nonwoven is the mass per unit area of ​​the nonwoven. The basis weight can be modified by changing the manufacturing conditions, as known in the art. The nonwoven web can have the same basis weight before and after bonding. Alternatively, the bonding method can change the basis weight of the nonwoven web. For example, when bonding occurs by the application of heat and pressure, the thickness of the nonwoven (and therefore the area of ​​the nonwoven) can decrease, thereby increasing the basis weight. Thus, as used herein, unless otherwise specified, the basis weight of a nonwoven refers to the basis weight of the nonwoven after bonding.

[0181] The nonwoven web of the present disclosure has a viscosity of about 0.1 g / m 2 ~about 700g / m 2 , about 0.5g / m 2 ~about 600g / m 2 , about 1g / m 2 ~about 500g / m 2 , about 1g / m 2 ~about 400g / m 2 , about 1g / m 2 ~about 300g / m 2 , about 1g / m 2 ~about 200g / m 2 , about 1g / m 2 ~about 100g / m 2 , about 30g / m 2 ~about 100g / m2 , about 20g / m 2 ~about 100g / m 2 , about 20g / m 2 ~about 80g / m 2 or about 25 g / m 2 ~about 70g / m 2 The sheet may have any basis weight in the range of 1000 to 15000 grammage.

[0182] In an embodiment, the nonwoven web may be carded and has a thickness of about 5 g / m 2 ~about 15g / m 2 , about 7g / m 2 ~Approx. 13g / m 2 , about 9g / m 2 ~Approx. 11g / m 2 or about 10 g / m 2 In an embodiment, the nonwoven web may be carded and have a basis weight of 30 g / m 2 or larger, e.g. 30 g / m 2 ~about 70g / m 2 , about 30g / m 2 ~about 60g / m 2 , about 30g / m 2 ~about 50g / m 2 , about 30g / m 2 ~about 40g / m 2 , or about 30 g / m 2 ~Approx. 35g / m 2 In an embodiment, the nonwoven web may be meltspun and have a basis weight in the range of about 1 g / m 2 ~about 20g / m 2 , about 2g / m 2 ~about 15g / m 2 , about 3g / m 2 ~about 10g / m 2 , about 5g / m 2 ~about 15g / m 2 , about 7g / m 2 ~Approx. 13g / m 2 , about 9g / m 2 ~Approx. 11g / m 2 or about 10 g / m 2 In an embodiment, the nonwoven web may be meltspun and have a basis weight of about 0.1 g / m 2 ~about 10g / m 2 , about 0.1g / m2 ~about 8g / m 2 , about 0.2g / m 2 ~about 6g / m 2 , about 0.3g / m 2 ~ approx. 4g / m 2 , about 0.4 g / m 2 ~about 2g / m 2 , or about 0.5 g / m 2 ~about 1g / m 2 The sheet may have a basis weight of 100 g.

[0183] The basis weight is related to the fiber volume density and porosity of the nonwoven fabric. Nonwoven webs as prepared and before bonding generally have a fiber density of about 30% or less by volume, i.e., for a given volume of nonwoven fabric, 30% or less of the volume is composed of fibers, and the remaining volume is air. Thus, nonwoven webs are generally highly porous. The fiber volume density and porosity of nonwoven fabrics are inversely related properties of nonwoven fabrics, for example, a nonwoven fabric with a fiber volume density of about 30% by volume will have a porosity of about 70% by volume. It is well understood in the art that as fiber volume density increases, porosity decreases. Fiber volume density can be increased by increasing the basis weight of the nonwoven fabric, for example, by bonding with the application of heat and pressure, potentially reducing the thickness (and therefore volume) of the nonwoven fabric. Thus, as used herein, unless otherwise specified, the fiber volume density and porosity of a nonwoven fabric refer to the fiber volume density and porosity of the nonwoven fabric after bonding.

[0184] The nonwoven webs of the present disclosure may have a porosity of from about 50% to about 95%, e.g., at least about 50%, at least about 60%, at least about 70%, at least about 75% or at least about 80%, and up to about 95%, up to about 90%, up to about 85%, up to about 80%, up to about 75%, up to about 70%, or in the range of about 50% to about 95%, about 50% to about 80%, about 50% to about 70%, about 60% to about 75%, about 60% to about 80%, about 60% to about 90%, about 75% to about 85%, about 75% to about 90%, or about 75% to about 95%.

[0185] Pore ​​size can be determined using high magnification ordered surface analysis techniques including, but not limited to, Brunauer-Emmett-Teller theory (BET), small angle X-ray scattering (SAXS) and molecular adsorption.

[0186] The nonwoven web of the present disclosure may have any thickness. Suitable thicknesses include, but are not limited to, about 5 to about 10,000 μm (1 cm), about 5 to about 5,000 μm, about 5 to about 1,000 μm, about 5 to about 500 μm, about 200 to about 500 μm, about 5 to about 200 μm, about 20 to about 100 μm, or about 40 to about 90 μm, or about 50 to 80 μm, or about 60 to 65 μm, for example, 50 μm, 65 μm, 76 μm, or 88 μm. The nonwoven web of the present disclosure may be characterized by high loft or low loft. Generally, loft refers to the ratio of thickness to basis weight. High loft nonwoven webs can be characterized by a high ratio of thickness to basis weight. As used herein, "high loft" refers to a nonwoven web of the present disclosure having a basis weight as defined herein and a thickness greater than 200 μm. The thickness of a nonwoven web can be determined according to ASTM D5729-97, ASTM D5736 and ISO 9073-2:1995, and can include, for example, subjecting the nonwoven web to a load of 2N and measuring the thickness. High loft materials can be used according to methods known in the art, such as air-through bonding, or cross-wrapping, using a cross-wrap to fold an unbonded web on itself to create loft and basis weight. Without intending to be bound by theory, it is believed that the solubility of a nonwoven web containing water-soluble fibers is independent of the thickness of the web, as opposed to a water-soluble film, where the solubility of the film may depend on the thickness of the film. In this regard, it is believed that the basis weight is the parameter that limits the access of water to the fibers, and thereby the dissolution of the fibers in a water-soluble nonwoven web, since the individual fibers provide a larger surface area than a water-soluble film, regardless of the thickness of the film.

[0187] The water solubility of the nonwoven web of the present disclosure is generally a function of the type of fiber(s) used to prepare the web and the basis weight of the water-dispersible web. Without intending to be bound by theory, it is believed that for a nonwoven web that includes a single fiber type that includes a single fiber-forming material, the solubility profile of the nonwoven web follows the same solubility profile as the fiber(s) used to prepare the nonwoven web, and the solubility profile of the fiber generally follows the same solubility profile as the fiber-forming polymer(s) from which the fiber is prepared. For example, for a nonwoven web that includes PVOH fibers, the degree of hydrolysis of the polymer can be selected so that the water solubility of the nonwoven web is also affected. Generally, at a given temperature, as the degree of hydrolysis of the polymer increases from partial hydrolysis (88% DH) to full hydrolysis (≧98% DH), the water solubility of the polymer generally decreases. Thus, in one option, the nonwoven web can be cold water soluble. In the case of co-poly(vinyl acetate=vinyl alcohol) polymers that do not contain any other monomers (e.g., not copolymerized with anionic monomers), the cold water-soluble webs that are soluble in water at temperatures below 10° C. may comprise fibers of PVOH copolymers having a degree of hydrolysis in the range of about 75% to about 90%, or in the range of about 80% to about 90%, or in the range of about 85% to about 90%. In another alternative, the nonwoven web may be hot water-soluble. In the case of co-poly(vinyl acetate=vinyl alcohol) polymers that do not contain any other monomers (e.g., not copolymerized with anionic monomers), the hot water-soluble webs that are soluble in water at temperatures of at least about 60° C. may comprise fibers of PVOH copolymers having a degree of hydrolysis of at least about 98%.

[0188] The modification of the PVOH copolymer increases the solubility of the PVOH copolymer. Therefore, at a given temperature, the solubility of the water-dispersible nonwoven web prepared from the modified PVOH copolymer is expected to be higher than that of the nonwoven web prepared from the unmodified PVOH copolymer with the same degree of hydrolysis as the PVOH copolymer. According to these trends, water-dispersible nonwoven webs with specific solubility characteristics can be designed.

[0189] Surprisingly, for nonwoven webs containing blends of fiber types, where each fiber type has a single fiber-forming material, the solubility of the nonwoven web does not follow the rules of mixtures as would be expected for blends of fiber types. Rather, for nonwoven webs containing blends of two fiber types, when the two fiber types are provided in a ratio other than 1:1, the solubility of the nonwoven web tends toward the solubility of the less soluble fiber (i.e., fiber that requires higher temperatures to completely dissolve and dissolves more slowly at temperatures below the complete dissolution temperature). For nonwoven webs containing 1:1 blends of fibers, the solubility of the nonwoven web was generally lower than that of nonwoven webs containing blends other than the 1:1 blend (i.e., at a given temperature, the nonwoven web containing the 1:1 blend took longer to break, disintegrate, and dissolve than, for example, nonwoven webs containing fiber types in 3:1 and 1:3 ratios). This trend was particularly evident at temperatures below the complete dissolution temperature of the less soluble fiber.

[0190] The inclusion of water-insoluble fibers in the nonwoven web can also be used to design a nonwoven web (e.g., when the nonwoven web is included in a water-dispersible pouch) with a particular solubility and / or delayed release characteristics. Without intending to be bound by theory, it is believed that as the weight percent of water-insoluble fibers included in the nonwoven web (based on the total weight of the nonwoven web) increases, the solubility of the nonwoven web generally decreases and the delayed release characteristics of the pouch including the nonwoven web generally increase. Upon contact with water at or above the dissolution temperature of the water-soluble fibers, the nonwoven web including water-soluble and water-insoluble fibers begins to thin as the water-soluble fibers dissolve, thereby degrading the web structure and / or increasing the pore size of the pores in the nonwoven web. In general, the greater the degradation or increase in pore size of the web structure, the faster the water will reach the contents of the pouch and the faster the contents of the pouch will be released. Similarly, delayed release of the contents of the pouch including the nonwoven web of the present disclosure can be achieved by using a blend of water-soluble fibers with different dissolution characteristics and / or different dissolution temperatures. Generally, for nonwoven webs comprising water soluble fibers including polyvinyl alcohol fiber forming materials, at water temperatures at or above 50% of the complete dissolution temperature of the water soluble fibers (e.g., 40° C. for fibers having a complete dissolution temperature of 70° C.), the fibers undergo polymer network swelling and softening, but the overall structure remains intact. In embodiments where the nonwoven web comprises water soluble and water insoluble fibers, the ratio of soluble to insoluble fibers is not particularly limited. The water soluble fibers may constitute about 1% to about 99%, about 20% to about 80%, about 40% to about 90%, about 50% to about 90%, or about 60% to about 90% by weight of the total weight of the fibers, and the water insoluble fibers may constitute about 1% to about 99%, about 20% to about 80%, about 10% to about 60%, about 10% to about 50%, or about 10% to about 40% by weight of the total weight of the fibers.

[0191] Furthermore, as the basis weight of a nonwoven web increases, the dissolution rate of the web decreases, although the fiber composition and bonding parameters remain constant, as more material dissolves. For example, at a given temperature, a nonwoven web prepared from fibers containing PVOH polymer(s) and weighing, for example, 40 g / m 2 A water-soluble web having a basis weight of, for example, 30 g / m 2 The water-dispersible nonwoven web is expected to dissolve more slowly than an otherwise identical nonwoven web having a basis weight of about 1 g / m. This relationship was particularly evident when the temperature of the water for dissolution was below the complete dissolution temperature of the fibers that make up the nonwoven web. Thus, basis weight can also be used to modify the dissolution characteristics of the water-dispersible nonwoven web. The nonwoven web is expected to dissolve more slowly than an otherwise identical nonwoven web having a basis weight of about 1 g / m. 2 ~about 700g / m 2 , about 1g / m 2 ~about 600g / m 2 , about 1g / m 2 ~about 500g / m 2 , about 1g / m 2 ~about 400g / m 2 , about 1g / m 2 ~about 300g / m 2 , about 1g / m 2 ~about 200g / m 2 , about 1g / m 2 ~about 100g / m 2 , about 30g / m 2 ~about 100g / m 2 , about 20g / m 2 ~about 100g / m 2 , about 20g / m 2 ~about 80g / m 2 , about 25g / m 2 ~about 70g / m 2 , or about 30 g / m 2 ~about 70g / m 2 The sheet may have any basis weight in the range of 1000 to 15000 grammage.

[0192] In addition, the calendar settings have a secondary effect on the solubility profile of the nonwoven webs of the present disclosure. For example, for nonwoven webs with the same fiber chemistry and similar basis weight, at a given calendar pressure, the nonwoven web dissolution time generally increases as the calendar temperature increases. This relationship was particularly evident when the temperature of the water for dissolution was lower than the complete dissolution temperature of the fibers that make up the nonwoven web.

[0193] Without intending to be bound by theory, it is believed that the solubility (e.g., in terms of time to dissolution according to MSTM-205) of a water-soluble nonwoven web would be expected to exceed that of a water-soluble film of the same size (L×W) and / or mass prepared from the same PVOH polymer. This is due to the larger surface area found in the nonwoven compared to the film, resulting in faster dissolution.

[0194] The nonwoven web of the present disclosure may include any of the auxiliary agents disclosed herein. The auxiliary agent may be distributed throughout the web, for example, between fibers, or may be applied to one or more surfaces of the nonwoven web. The auxiliary agent may be added to the nonwoven web using the "simultaneous forming" method developed by Kimberly Clark during the melt-spun process, as is well known in the art. The auxiliary agent may also be added to one or more surfaces of the nonwoven web or the article prepared therefrom by any suitable means.

[0195] In embodiments, the nonwoven webs of the present disclosure are substantially free of adjuvants. As used herein, unless otherwise specified, "substantially free of adjuvants" means that the nonwoven web contains less than about 0.01 wt.%, less than about 0.005 wt.%, or less than about 0.001 wt.% of adjuvants based on the total weight of the nonwoven web.

[0196] In one embodiment, one or more stationary powder spray guns are used to direct a stream of supplemental powder onto the web or article from one or more directions, while the web or article is conveyed through the coating zone by a belt conveyor. In an alternative embodiment, the article is conveyed through a suspension of supplemental powder in air. In yet another alternative embodiment, the article is tumble mixed with the supplemental powder in a tubular device. In another embodiment, which can be combined with any other embodiment, electrostatic forces are used to enhance the attraction between the supplemental powder and the article. This type of process is typically based on negatively charging the powder particles and directing these charged particles to a grounded article. In other alternative embodiments, the supplemental powder is applied to the article by a secondary transfer tool, including but not limited to a rotating brush in contact with the powder, or by a powdering glove that can transfer the powder from a container to the article. In yet another embodiment, the supplemental powder is applied by dissolving or suspending the powder in a non-aqueous solvent or carrier, which is then atomized and sprayed onto the nonwoven or article. In one type of embodiment, the solvent or carrier is then evaporated, leaving behind the adjuvant powder. In one class of embodiments, the adjuvant powder is applied to the nonwoven or article in a precise dosage. This class of embodiments utilizes a closed system dry lubricant application equipment, such as a PekuTECH powder application equipment PM 700 D. In this process, the adjuvant powder is fed into the application equipment feed trough in batches or continuously as needed. The nonwoven web or article is transferred from the exit belt of the standard rotary drum pouching equipment onto the conveyor belt of the powder application equipment, where a controlled dosage of the adjuvant is applied to the nonwoven web or article.

[0197] The liquid adjuvant can be applied to the nonwoven web or article by, for example, spin casting, spraying a solution such as an aerosolized solution, roll coating, flow coating, curtain coating, extrusion, knife coating, and combinations thereof.

[0198] In embodiments, the nonwoven web may be colored, pigmented, and / or dyed to provide improved aesthetic effects compared to water-soluble films. Suitable colorants may include indicator dyes, such as pH indicators (e.g., thymol blue, bromothymol, thymolphthalein, and thymolphthalein), moisture / water indicators (e.g., hydrochromic inks or leuco dyes), or thermochromic inks, where the ink changes color as the temperature increases and / or decreases. Suitable colorants include, but are not limited to, triphenylmethane dyes, azo dyes, anthraquinone dyes, perylene dyes, indigoid dyes, Food, Drug, and Cosmetic (FD&C) colors, organic pigments, inorganic pigments, or combinations thereof. Examples of colorants include, but are not limited to, FD&C Red #40, Red #3, FD&C Black #3, Black #2, mica-based pearlescent pigments, FD&C Yellow #6, Green #3, Blue #1, Blue #2, titanium dioxide (food grade), brilliant black, and combinations thereof.

[0199] When included in the water soluble fibers, the colorant may be provided in an amount of 0.01% to 25% by weight of the water soluble polymer mixture, for example, 0.02%, 0.05%, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, and 24% by weight of the water soluble polymer mixture.

[0200] Advantageously, the nonwoven web of the present disclosure may exhibit preferential shrinkage in the presence of heat and / or water (e.g., humidity). Thus, the nonwoven web may be heat and / or water shrunk when formed into a packet. Even more advantageously, the nonwoven web of the present disclosure may exhibit increased robustness (i.e., mechanical properties) and improved solubility performance after storage in high heat and moisture environments (e.g., 38°C and 80% relative humidity (RH)). Such increased robustness and improved solubility performance are surprising, since predictions based on compositionally similar water-soluble films would suggest that robustness and solubility performance would not be affected by storage in high heat and moisture conditions. In particular, after removal of a comparable water-soluble film from the conditioned environment, the water-soluble film re-equilibrates with the surrounding environment, which does not result in long-term or permanent changes in the performance properties of the film.

[0201] The nonwoven web of the present disclosure can be used as a single layer or can be layered with other nonwoven webs and / or water-soluble films. In some embodiments, the nonwoven web comprises a single layer of a nonwoven web. In some embodiments, the nonwoven web is a multi-layer nonwoven web comprising two or more layers of a nonwoven web. One or more layers can be laminated to each other. In refinements of the foregoing embodiments, the two or more layers can be the same (e.g., prepared from the same fibers and have the same basis weight). In refinements of the foregoing embodiments, the two or more layers can be different (e.g., prepared from different types of fibers and / or have different basis weights). In embodiments, the nonwoven web can be laminated to a water-soluble film. In refinements of the foregoing embodiments, the nonwoven web and the water-soluble film can be prepared from the same polymer (e.g., a PVOH copolymer or modified copolymer having a particular viscosity, degree of hydrolysis, and amount of modification in the case of modified polymers). In a refinement of the foregoing embodiment, the nonwoven web and water-soluble film can be prepared from different polymers (e.g., the polymer used to prepare the fibers of the nonwoven web can have a different fiber chemistry (e.g., modification), viscosity, degree of polymerization, degree of hydrolysis, and / or solubility than the polymer that makes up the water-soluble film). Advantageously, the multi-layer nonwoven webs and laminates can be used to adjust the moisture vapor transmission rate (MVTR) of the pouch or packet made therefrom. The multi-layer materials can be prepared according to various processes known in the art, such as melt extrusion, coating (e.g., solvent coating, aqueous coating, or solid coating), spray bonding, material transfer, hot lamination, cold lamination, and combinations thereof.

[0202] A multi-layer nonwoven web can have a basis weight that is the sum of the basis weights of the individual layers. Thus, the multi-layer nonwoven web takes longer to dissolve than any of the individual layers provided as a single layer. In an embodiment, the multi-layer nonwoven web has a basis weight of about 1 g / m 2 ~about 100g / m 2In addition, without intending to be bound by theory, it is believed that if the pore size and pore arrangement are dissimilar between layers, the pores of each layer will not align, thereby providing a multi-layer nonwoven web with smaller pores than the individual layers. Thus, a non-porous water-dispersible nonwoven web can be prepared by layering multiple porous water-dispersible nonwoven webs.

[0203] The nonwoven web can also be laminated to a water-soluble film. The laminate can be formed using any method known in the art, including, but not limited to, heat and pressure, chemical bonding, and / or solvent welding. Chemical bonding can include functionalizing the surface of the nonwoven web and / or the surface of the water-soluble film with ionic or covalent bonds, such that when the surface of the nonwoven web contacts the surface of the water-soluble film, a chemical reaction occurs, covalently bonding the nonwoven web and the water-soluble film together. The multilayer nonwoven web can include three or more layers. In an embodiment, the multilayer nonwoven web can include a first layer including a water-soluble film, a second layer including a nonwoven web, and a third layer including a water-soluble film. In an embodiment, the multilayer nonwoven web can include a first layer including a nonwoven web, a second layer including a water-soluble film, and a third layer including a nonwoven web.

[0204] Advantageously, the laminate can be prepared simultaneously with the pouch formation, for example by bonding the nonwoven web and the water-soluble film layer together using heat applied during thermoforming. The water-soluble film can have the same solubility and / or chemical compatibility characteristics as the nonwoven web, or the water-soluble film can have a different solubility and / or chemical compatibility characteristics than the nonwoven web. In embodiments, the water-soluble film has the same solubility and / or chemical compatibility characteristics as the nonwoven web. In some embodiments, the water-soluble film has a different solubility and / or chemical compatibility characteristics than the nonwoven web. Advantageously, when the water-soluble film has a different solubility and / or chemical compatibility characteristics than the nonwoven web, the laminate can be used to form a pouch with an inner surface having a first solubility and / or chemical compatibility, and an outer surface having a second solubility and / or chemical compatibility.

[0205] The water-soluble film used for the laminate can be any water-soluble film, such as those already known in the art. The polymer used to form the water-soluble film can be any water-soluble polymer or combination thereof, such as those described herein. The water-soluble film can contain at least about 50wt.%, 55wt.%, 60wt.%, 65wt.%, 70wt.%, 75wt.%, 80wt.%, 85wt.%, or 90wt.% and / or up to about 60wt.%, 70wt.%, 80wt.%, 90wt.%, 95wt.%, or 99wt.% water-soluble polymer, such as PVOH polymer or polymer blend.

[0206] The water-soluble film may contain other auxiliary and processing agents, such as, but not limited to, plasticizers, plasticizer compatibilizers, surfactants, lubricants, release agents, fillers, extenders, crosslinkers, antiblocking agents, antioxidants, detackifying agents, antifoaming agents, nanoparticles such as layered silicate nanoclays (e.g., sodium montmorillonite), bleaching agents (e.g., sodium metabisulfite, sodium bisulfite or others), aversive agents such as bittering agents (e.g., denatonium salts such as denatonium benzoate, denatonium sugar and denatonium chloride; sucrose octaacetate; quinine; flavonoids such as quercetin and naringenin; and cassinoids such as cassine and brucine) and pungent agents (e.g., capsaicin, piperine, allyl isocyanate and resiniferatoxin), and other functional ingredients, in amounts suitable for their intended purpose. Preferred are embodiments that include plasticizers. The amount of such agents, individually or collectively, may be up to about 50 wt.%, 20 wt.%, 15 wt.%, 10 wt.%, 5 wt.%, 4 wt.% and / or at least 0.01 wt.%, 0.1 wt.%, 1 wt.%, or 5 wt.% of the film.

[0207] The present disclosure provides a method of treating a nonwoven web comprising a plurality of fibers comprising a hydrolyzable polymer, such as at least one of a vinyl acetate moiety or a vinyl alcohol moiety, and having a degree of hydrolysis less than 100%, comprising contacting at least a portion of the nonwoven web with a hydrolyzing agent solution as described herein to increase the degree of hydrolysis of the hydrolyzable polymer of the fibers of the nonwoven web. In an embodiment, the portion of the nonwoven web contacted with the hydrolyzing agent can be a surface of the nonwoven web. In an embodiment, the contacting can be by immersion, spraying, transfer coating, imbibing, foaming, brushing, rolling, moistening, vapor deposition, printing, or a combination thereof. In an embodiment, the contacting is performed simultaneously with bonding the plurality of fibers into the nonwoven web. In an embodiment, the contacting and bonding comprises chemical bonding. In an embodiment, the contacting and bonding comprises a heat-activated catalyst. The hydrolyzable polymer can be any hydrolyzable polymer disclosed herein. In embodiments, the hydrolyzable polymer comprises a polymer comprising at least one of a vinyl acetate moiety or a vinyl alcohol moiety, which may be selected from a polyvinyl acetate homopolymer, a polyvinyl alcohol homopolymer, a polyvinyl alcohol copolymer, a modified polyvinyl alcohol copolymer, and combinations thereof. In embodiments, the polyvinyl alcohol copolymer comprises an anionically modified copolymer. In embodiments, the anionically modified copolymer comprises a carboxylate, a sulfonate, or a combination thereof. In embodiments, the fiber further comprises an additional polymer. The hydrolyzing agent solution may comprise any hydrolyzing agent disclosed herein and any solvent disclosed herein. In embodiments, the hydrolyzing agent comprises a metal hydroxide, a metal hydride, a sulfite compound, sulfur dioxide, a dithionate, a thiosulfate, a hydrazine, an oxalic acid, a formic acid, an ascorbic acid, a dithiothreitol, a phosphite, a hypophosphite, an acid of phosphorus, a sulfuric acid, a sulfonic acid, a hydrochloric acid, an ammonium hydroxide, water, or a combination thereof. In embodiments, the hydrolyzing agent is provided in an amount of about 0.2% to about 75% (w / w) based on the weight of the solvent. In embodiments, the fibers are insoluble in the solvent before, during, and after treatment.In embodiments, the hydrolyzing agent solution further comprises an activating agent.

[0208] The present disclosure provides a method of treating a nonwoven web comprising a plurality of fibers comprising a polymer, such as a polymer comprising at least one of a vinyl acetate moiety or a vinyl alcohol moiety and having a degree of hydrolysis of less than or equal to 100% and greater than 0%, comprising contacting at least a portion of the nonwoven web with an acylating agent solution to reduce the degree of hydrolysis of the polymer of the portion of the fibers of the nonwoven web. In an embodiment, the portion of the nonwoven web contacted with the acylating agent can be a face of the nonwoven web. In an embodiment, the contacting can be by immersion, spraying, transfer coating, imbibing, foaming, brushing, rolling, moistening, vapor deposition, printing, or a combination thereof. In an embodiment, the contacting is performed simultaneously with bonding the plurality of fibers into the nonwoven web. In an embodiment, the contacting and bonding comprises chemical bonding. In an embodiment, the contacting and bonding comprises a heat-activated catalyst. The polymer can be any hydrolyzable polymer disclosed herein comprising hydroxide or amine groups that can be acylated. In an embodiment, the hydrolyzable polymer comprises a polyvinyl alcohol polymer, such as a polyvinyl alcohol copolymer, a modified polyvinyl alcohol copolymer, and combinations thereof. In an embodiment, the polyvinyl alcohol copolymer comprises an anionically modified copolymer. In an embodiment, the anionically modified copolymer comprises a carboxylate, a sulfonate, or a combination thereof. In an embodiment, the fiber further comprises an additional polymer. The acylating agent solution may comprise any acylating agent disclosed herein and any solvent disclosed herein. In an embodiment, the fiber is insoluble in the solvent before, during, and after treatment.

[0209] The present disclosure further provides a nonwoven web treated according to the method of the present disclosure.The present disclosure provides a nonwoven web comprising the fibers of the present disclosure.The present disclosure provides a multi-layer nonwoven web comprising a first layer comprising a nonwoven web treated according to the method of the present disclosure or a nonwoven web comprising the fibers of the present disclosure.

[0210] biodegradable

[0211] Polyvinyl alcohol polymers are generally biodegradable because they degrade under aerobic, anaerobic, soil and compost conditions (in the presence of water), in the presence of water and enzymes. Generally, the biodegradation activity of polyvinyl alcohol polymers increases as the degree of hydrolysis of the polyvinyl alcohol polymer increases up to about 80%. Without intending to be bound by theory, it is believed that increasing the degree of hydrolysis beyond 80% does not appreciably affect biodegradability. Furthermore, the stereoregularity of the hydroxyl groups of the polyvinyl alcohol polymer has a large effect on the level of biodegradation activity; the more isotactic the hydroxyl groups in the polymer sequence, the higher the degradation activity. Without intending to be bound by theory, it is believed that for soil and / or compost biodegradation, nonwoven webs prepared from polyvinyl alcohol fibers have a higher level of biodegradation activity compared to water-soluble films prepared from similar polyvinyl alcohol polymers due to the increased polymer surface area provided by the nonwoven web compared to films. Furthermore, without intending to be bound by theory, it is believed that while the degree of polymerization of a polyvinyl alcohol polymer has little or no effect on the biodegradability of a film or nonwoven web prepared with the polymer, the polymerization temperature may have an effect on the biodegradability of the film or nonwoven because it may affect the crystallinity and aggregation state of the polymer. In particular, as the crystallinity decreases, the polymer chain hydroxyl groups become less aligned in the polymer structure, the polymer chains become more disordered, and the chains may accumulate as amorphous aggregates, thereby decreasing the availability of the ordered polymer structure and biodegradation activity is expected to decrease for soil and / or compost biodegradation mechanisms in which the polymer does not dissolve.Without intending to be bound by theory, it is believed that the stereoregularity of the hydroxyl groups of polyvinyl alcohol polymers has a large effect on the biodegradation activity level, so that substitution of functional groups other than hydroxyl groups (e.g., anionic AMPS functional groups, carboxylate groups, or lactone groups) is expected to reduce the biodegradation activity level compared to polyvinyl alcohol homopolymers or copolymers with the same degree of hydrolysis, unless the functional groups themselves are also biodegradable and the biodegradability of the polymer can be increased by substitution. Furthermore, while the biodegradation activity level of substituted polyvinyl alcohol (or modified polyvinyl alcohol copolymers) may be lower than that of the corresponding homopolymer or copolymer, the substituted polyvinyl alcohol is still believed to be biodegradable.

[0212] Methods for determining biodegradation activity are known in the art, for example, as described in Chiellini et al., Progress in Polymer Science, Volume 28, Issue 6, 2003, pp. 963-1014, which is incorporated herein by reference in its entirety. Further methods and standards can be found in ECHA's Annex XV Restriction Report - Microplastics, Version number 1, January 11, 2019, which is incorporated herein by reference in its entirety. Suitable standards include OECD 301B (ready biodegradation), OECD 301B (enhanced biodegradation), OECD 302B (intrinsic biodegradation), OECD 311 (anaerobic) and ASTM D5988 (soil).

[0213] In an embodiment, the fibers and nonwoven webs of the present disclosure may be of the standard ready biodegradability, enhanced biodegradability or inherent biodegradability. As used herein, the term "ready biodegradability" refers to a standard that is met when a material (e.g., fiber) reaches 60% biodegradation (mineralization) within 28 days of the start of the test according to the OECD 301B test as described in ECHA's Annex XV. As used herein, the term "enhanced degradation" refers to a standard that is met when a material (e.g., fiber) reaches 60% biodegradation within 60 days of the start of the test according to the OECD 301B test as described in ECHA's Annex XV. In an embodiment, the fibers and nonwoven webs of the present disclosure meet the standard for ready biodegradability. In an embodiment, the fibers and nonwoven webs of the present disclosure meet the standard for ready biodegradability or enhanced biodegradability. In an embodiment, the fibers and nonwoven webs of the present disclosure meet the standard for inherent biodegradability. In an embodiment, the fibers and nonwoven webs of the present disclosure meet the standard for enhanced biodegradability. In embodiments, the fibers and nonwoven webs of the present disclosure meet inherent, enhanced or easy degradability specifications. In embodiments, the laminates (nonwovens and films) of the present disclosure meet easy or enhanced degradability specifications.

[0214] use

[0215] The nonwoven web of the present disclosure is suitable for various commercial applications.Suitable commercial applications of the nonwoven web of the present disclosure may include, but are not limited to, water-dispersible or flushable pouches and packets;medical applications, such as surgical masks, medical packaging, shoe covers, wound dressings and drug delivery;filtration systems, such as for gasoline and oil, mineral processing, vacuum bags, air filters and allergen membranes or laminates;personal care products, such as body wipes, makeup removal wipes, exfoliating cloths, cosmetics, and wearable absorbent articles, such as diapers and adult incontinence products;office supplies, such as shopping bags or envelopes;and others, such as eyeglass cleaning wipes, indoor cleaning wipes, potting materials for plants, antibacterial wipes, agricultural seed strips, fabric softener sheets, clothing / laundry bags, food packaging, food care wipes, pet care wipes, scouring tools, dust removal and hand cleaning.

[0216] Sealing pouch

[0217] The present disclosure further provides a pouch comprising a nonwoven web according to the present disclosure in the form of a pouch defining an interior pouch volume. In some embodiments, the pouch may comprise a laminate comprising a water-soluble film and a nonwoven web of the present disclosure. The pouch may be a water-dispersible pouch, optionally a water-soluble pouch and / or a flushable pouch. The present disclosure further provides a method of preparing a packet comprising a nonwoven web of the present disclosure, comprising forming the nonwoven web into the form of a pouch, filling the pouch with a composition to be encapsulated, and sealing the pouch to form a packet. In some embodiments, the sealing may comprise heat sealing, solvent welding, adhesive sealing, or a combination thereof.

[0218] The nonwoven webs and laminates disclosed herein are useful for making sealed articles in the form of a pouch defining an interior pouch volume containing a composition therein for release into an aqueous environment. A "sealed article" includes sealed compartments, optionally with vent holes, for example in embodiments where the compartment encapsulates an off-gassing solid, but more commonly will be a fully sealed compartment.

[0219] The pouch may contain a single compartment or multiple compartments. The pouch may be formed from two layers of nonwoven web or laminate sealed at the interface, or from a single nonwoven web or laminate folded over itself and sealed. The nonwoven web or laminate forms at least one sidewall of the pouch, optionally the entire pouch, and preferably the outer surface of at least one sidewall. In another type of embodiment, the nonwoven web or laminate forms the inner wall of the packet, for example as a partition between compartments. The nonwoven web or laminate can also be used in combination with a water-soluble film, for example as an outer wall, inner wall and / or compartment lid.

[0220] The composition enclosed in the pouch may include, but is not limited to, any of the various compositions described herein. In embodiments that include multiple compartments, each compartment may contain the same and / or different compositions. The composition may then take any suitable form, including, but not limited to, liquid, solid, gel, paste, mul, compressed solid (tablet) and combinations thereof (e.g., a solid suspended in a liquid).

[0221] In some embodiments, the pouch includes multiple compartments. The multiple compartments are generally stacked such that the compartments share a bulkhead inside the pouch. The compartments of the multi-compartment pouch may be of the same or different size and / or volume. The compartments of the present multi-compartment pouch may be separated or combined in any suitable manner. In an embodiment, the second and / or third and / or subsequent compartments are stacked on the first compartment. In one embodiment, the third compartment may be stacked on the second compartment, which is then stacked on the first compartment in a sandwich configuration. Alternatively, the second and third compartments may be stacked on the first compartment. However, it is equally envisioned that the first, second and / or third and / or subsequent compartments are oriented side-by-side or concentrically. The compartments may be packaged in a string in which each compartment is individually separated by a perforation line. Thus, each compartment may be individually pulled apart from the remainder of the string by the end user. In some embodiments, the first compartment may be surrounded by at least a second compartment, for example, in a tire and rim arrangement or a pouch-in-pouch arrangement.

[0222] The geometries of the compartments may be the same or different. In embodiments, the optional third and subsequent compartments each have a different geometry and shape compared to the first and second compartments. In these embodiments, the optional third and subsequent compartments are configured with a design relative to the first or second compartments. The design may be decorative, educational, or illustrative, for example, to illustrate a concept or instruction and / or show the origin of the product.

[0223] How to Make a Pouch

[0224] The pouches and packets may be made using any suitable equipment and methods. For example, single compartment pouches may be made using vertical fill, horizontal fill or rotary drum fill techniques commonly known in the art. Such processes may be either continuous or intermittent. The nonwoven web, layered nonwoven web and film, or laminate structure may be moistened and / or heated to increase its malleability. The method may also include the use of a vacuum to draw the nonwoven web, layered nonwoven web and film or laminate structure into a suitable mold. The vacuum to draw the nonwoven web or laminate into the mold may be applied for about 0.2 to about 5 seconds, or about 0.3 to about 3, or about 0.5 to about 1.5 seconds after the nonwoven web, layered nonwoven web and film or laminate structure is on the horizontal portion of the surface. The vacuum may for example be such as to provide a pressure in the range of 10 mbar to 1000 mbar, or in the range of 100 mbar to 600 mbar.

[0225] The molds in which the packets may be made may have any shape, length, width and depth depending on the required dimensions of the pouch. The molds may also vary in size and shape from one another, if desired. For example, the volume of the final pouch may be from about 5 ml to about 300 ml, or from about 10 ml to 150 ml, or from about 20 ml to about 100 ml, and the size of the molds adjusted accordingly.

[0226] thermoforming

[0227] Thermoformable nonwoven webs or laminates are those that can be shaped through the application of heat and force. Thermoforming of nonwoven webs, layered nonwoven webs and film or laminate structures is a process of heating a nonwoven web, layered nonwoven webs and film or laminate structures, shaping it (e.g., in a mold), and then cooling the resulting nonwoven web or laminate, during which the nonwoven web or laminate retains its shape, e.g., the shape of the mold. Heat may be applied using any suitable means. For example, the nonwoven web or laminate may be directly heated by passing it under a heating element or through hot air before or once it is applied onto a surface. Alternatively, the nonwoven web or laminate may be indirectly heated, for example, by heating the surface or by applying a heat item onto the nonwoven web or laminate. In an embodiment, the nonwoven web or laminate is heated using infrared light. The nonwoven web or laminate may be heated to a temperature ranging from about 50° C. to about 200° C., from about 50° C. to about 170° C., from about 50° C. to about 150° C., from about 50° C. to about 120° C., from about 60° C. to about 130° C., from about 70° C. to about 120° C., or from about 60° C. to about 90° C. Thermoforming can be performed by any one or more of the following processes: manual draping of a heat-softened nonwoven web or laminate onto a mold, or pressure-induced forming (e.g., vacuum forming) of a softened nonwoven web or laminate onto a mold, or automatic high speed indexing of a freshly extruded sheet having a precisely known temperature into a forming and trimming station, or automatic placement, plugging and / or air stretching and pressure forming of the nonwoven web or laminate.

[0228] Alternatively, the nonwoven web or laminate may be wetted by any suitable means, for example, directly by spraying a wetting agent (including water, a polymeric composition, a plasticizer for the nonwoven web or laminate composition, or any combination of the foregoing) onto the nonwoven web or laminate before or once it is applied to the surface, or indirectly by wetting the surface or by applying a wetting item onto the nonwoven web or laminate.

[0229] Once heated and / or wetted, the nonwoven web or laminate may be drawn into a suitable mold, preferably using a vacuum. Filling of the molded nonwoven web or laminate may be accomplished by utilizing any suitable means. In an embodiment, the most preferred method depends on the product form and the required filling speed. In an embodiment, the molded nonwoven web or laminate is filled by an in-line filling technique. The filled open packet is then closed to form a pouch using a second nonwoven web or laminate, by any suitable method. This may be accomplished during a horizontal position and continuous constant motion. Closure may be accomplished by continuously feeding a second nonwoven web or laminate, preferably a water-soluble nonwoven web or laminate, onto the open packet and then preferably sealing the first and second nonwoven webs or laminates together, typically in the area between the molds and thus between the packets.

[0230] Pouch sealing

[0231] Any suitable method of sealing the pouch and / or its individual compartments may be utilized. Non-limiting examples of such means include heat sealing, solvent welding, solvent or wet sealing and combinations thereof. Typically, only the area where the seal is to be formed is treated with heat or solvent. Heat or solvent may be applied by any method, typically to the closure material, typically only to the area where the seal is to be formed. When solvent or wet sealing or welding is used, it may be preferred that heat is also applied. A preferred wet or solvent sealing / welding method involves selectively applying a solvent onto the area between the dies or onto the closure material, for example, by spraying or printing it onto these areas and then applying pressure onto these areas to form the seal. For example, sealing rolls and belts (which also provide heat, if necessary) can be used.

[0232] In an embodiment, the inner nonwoven web or laminate is sealed to the outer nonwoven web(s) or laminate(s) by solvent sealing. The sealing solution is generally an aqueous solution. In an embodiment, the sealing solution comprises water. In an embodiment, the sealing solution comprises water and further comprises one or more polyols, diols and / or glycols, such as 1,2-ethanediol (ethylene glycol), 1,3-propanediol, 1,2-propanediol, 1,4-butanediol (tetramethylene glycol), 1,5-pentanediol (1,5-pantanediol) (pentamethylene glycol), 1,6-hexanediol (hexamethylene glycol), 2,3-butanediol, 1,3-butanediol, 2-methyl-1,3-propanediol, various polyethylene glycols (e.g., diethylene glycol, triethylene glycol) and combinations thereof. In an embodiment, the sealing solution comprises erythritol, threitol, arabitol, xylitol, ribitol, mannitol, sorbitol, galactitol, fucitol, iditol, inositol, volemitol, isomer, maltitol, lactitol. In an embodiment, the sealing solution comprises a water soluble polymer.

[0233] The sealing solution can be applied to the interface area of ​​the inner nonwoven web or laminate in any amount suitable for bonding the inner and outer nonwoven webs or laminates. As used herein, the term "coat weight" refers to the amount of sealing solution applied to the nonwoven web or laminate in grams of solution per square meter of nonwoven web or laminate. In general, if the coat weight of the sealing solvent is too low, the nonwoven web or laminate will not bond well and the risk of pouch failure at the seam will increase. Furthermore, if the coat weight of the sealing solvent is too high, the risk of solvent migration from the interface area will increase and the probability that etch holes may form in the side of the pouch will increase. The coat weight window refers to the range of coat weights that can be applied to a given film while maintaining good adhesion and avoiding the formation of etch holes. A wide coat weight window is desirable because the wider the window, the more robust the seal will be under a wide range of operations. A suitable coat weight window is at least about 3 g / m 2 , or at least about 4 g / m 2 , or at least about 5 g / m 2 , or at least about 6 g / m 2 It is.

[0234] Packet Drop

[0235] The formed packets may be cut by a cutting device. The cutting may be accomplished using any known method. It may also be preferred that the cutting is done in a continuous manner, preferably at a constant speed, preferably in a horizontal position. The cutting device may be, for example, a sharp item, or a thermal item, or a laser, in the latter case, the thermal item or laser "burns" through the film / sealed area.

[0236] Forming and filling multi-compartment pouches

[0237] The different compartments of the multi-compartment pouch may be made together in a side-by-side or concentric style, and the resulting combined pouch may or may not be separated by cutting. Alternatively, the compartments may be made separately.

[0238] In an embodiment, the pouch may be made according to a process comprising the steps of: a) forming a first compartment (as described above); b) forming recesses in or on all of the closed compartments formed in step (a) to produce a second molded compartment superimposed on the first compartment; c) filling and closing the second compartment with a third nonwoven web, laminate or film; d) sealing the first, second and third nonwoven webs, laminates or films; and e) cutting the nonwoven webs or laminates to produce a multi-compartment pouch. The recesses formed in step (b) may be achieved by applying a vacuum to the compartments prepared in step (a).

[0239] In an embodiment, the second and / or third compartment may be made in a separate step and then combined with the first compartment, as described in European Patent Application No. 08101442.5 or US Patent Application Publication No. 2013 / 240388A1 or WO2009 / 152031.

[0240] In an embodiment, the pouch may be made according to a process including the steps of: a) forming a first compartment in a first former using heat and / or vacuum, if desired, with a first nonwoven web or laminate; b) filling the first compartment with a first composition; c) optionally filling the second compartment with a second composition; d) sealing the first and optional second compartments to the first nonwoven web or laminate with a second nonwoven web or laminate; and e) cutting the nonwoven web or laminate to produce the multi-compartment pouch.

[0241] In an embodiment, the pouch may be made according to a process including: a) forming a first compartment in a first former using a first nonwoven web or laminate, optionally using heat and / or vacuum; b) filling the first compartment with a first composition; c) deforming a second nonwoven web or laminate in a second former, optionally using heat and vacuum, to create a second and optionally third formed compartment; d) filling the second and optionally third compartment; e) sealing the second and optionally third compartment with a third nonwoven web or laminate; f) placing the sealed second and optionally third compartment onto the first compartment; g) sealing the first, second and optionally third compartments; and h) cutting the nonwoven web or laminate to produce a multi-compartment pouch.

[0242] The first and second formers may be selected based on their suitability for carrying out the above process. In an embodiment, the first former is preferably a horizontal former and the second former is preferably a rotary drum former, preferably located above the first former.

[0243] It should be appreciated that by use of an appropriate supply station it may be possible to manufacture a multi-compartment pouch incorporating several different or separate compositions and / or different or separate liquid, gel or paste compositions.

[0244] In an embodiment, the nonwoven web or laminate and / or pouch is sprayed or dusted with a suitable material, such as an active agent, a lubricant, an aversive agent, or mixtures thereof. In an embodiment, the nonwoven web or laminate and / or pouch is printed, for example, with an ink and / or an active agent.

[0245] Vertical Form, Fill and Seal

[0246] In an embodiment, the nonwoven web or laminate of the present disclosure may be formed into a sealed article. In an embodiment, the sealed article is a vertical form, fill and seal article. The vertical form, fill and seal (VFFS) method is a conventional automated process. The VFFS includes an apparatus, such as an assembly machine, that wraps a single piece of nonwoven web or laminate around a vertically oriented feed tube. The machine heat seals or otherwise fastens opposing ends of the nonwoven web or laminate together to create a side seal and form a hollow tube of the nonwoven web or laminate. The machine then heat seals or otherwise creates a bottom seal, thereby defining a container portion with an open top where a top seal is later formed. The machine introduces a specific amount of flowable product into the container portion through the open top end. Once the container contains a desired amount of product, the machine sends the nonwoven web or laminate to another heat sealing device, for example, which creates a top seal. Finally, the machine feeds the nonwoven web or laminate to a cutter which cuts the film just above the top seal to provide a filled package.

[0247] During operation, an assembly machine feeds the nonwoven web or laminate from a roll to form a package, therefore the nonwoven web or laminate must be able to advance easily through the machine, must not adhere to the machine assemblies, and must not be so brittle that it will break during processing.

[0248] Pouch contents

[0249] In any embodiment, the pouch may contain (enclose) the composition in a defined internal volume of the pouch. The composition may be selected from a liquid, a solid, or a combination thereof. In embodiments in which the composition comprises a liquid, the nonwoven web may be a nonporous nonwoven web or a porous nonwoven web laminated with a water-soluble film, the water-soluble film forming the inner surface of the pouch. In embodiments in which the composition is a solid, the pouch may comprise a nonporous nonwoven web, a porous nonwoven web laminated with a water-soluble film, or a porous nonwoven web. In embodiments in which the pouch comprises a porous nonwoven web, the particle size of the solid composition is smaller than the pore size of the nonwoven web.

[0250] In an embodiment, the sealed article of the present disclosure may enclose in the internal pouch volume a composition comprising a liquid laundry detergent, an agricultural composition, an automatic dishwashing composition, a household cleaning composition, a water treatment composition, a personal care composition, a food and nutritional composition, an industrial cleaning composition, a medical composition, a germicidal composition, a pet composition, an office composition, a livestock composition, an industrial composition, an aquatic composition, a commercial composition, a military composition, a recreational composition, or a combination thereof. In an embodiment, the water-dispersible sealed article of the present disclosure may enclose in the internal pouch volume a composition comprising a liquid laundry detergent, an agricultural composition, an automatic dishwashing composition, a household cleaning composition, a water treatment composition, a personal care composition, a food and nutritional composition, an industrial cleaning composition, or a combination thereof. In an embodiment, the water-dispersible sealed article of the present disclosure may enclose in the internal pouch volume a composition comprising a liquid laundry detergent, an agricultural composition, an automatic dishwashing composition, a household cleaning composition, a water treatment composition, a personal care composition, or a combination thereof. In embodiments, the water-dispersible sealed article of the present disclosure may enclose a composition, including an agricultural composition or a water treatment composition, in an interior pouch volume.

[0251] As used herein, "liquid" includes free-flowing liquids, as well as pastes, gels, foams and mousses. Non-limiting examples of liquids include light-weight and heavy-weight liquid detergent compositions, dish detergents for hand and / or machine washing; hard surface cleaning compositions, fabric strengtheners, detergent gels commonly used in laundry, bleaches and laundry additives, shaving creams, skin care, hair care compositions (shampoos and conditioners), and body washes. Such detergent compositions may include surfactants, bleaches, enzymes, perfumes, dyes or colorants, solvents and combinations thereof. Optionally, the detergent composition is selected from the group consisting of laundry detergents, dish washing detergents, hard surface cleaning compositions, fabric strengthener compositions, shaving creams, skin care, hair care compositions (shampoos and conditioners) and body washes, and combinations thereof.

[0252] Non-limiting examples of liquids include agricultural compositions, automotive compositions, aviation compositions, food and nutritional compositions, industrial compositions, livestock compositions, aquatic compositions, medical compositions, commercial compositions, military and paramilitary compositions, office compositions, recreational and park compositions, pet compositions, and water treatment compositions, including cleaning and detergent compositions applicable for any such use.

[0253] Gases, e.g., suspended bubbles, or solids, e.g., particles, may be contained within the liquid. As used herein, "solids" includes, but is not limited to, powders, aggregates, and mixtures thereof. Non-limiting examples of solids include granules, microcapsules, beads, noodles, and pearl balls. Solid compositions may provide technical benefits, including, but not limited to, washability benefits, pretreatment benefits, and / or aesthetic effects.

[0254] The composition may be a non-household care composition.For example, the non-household care composition may be selected from agricultural compositions, aviation compositions, food and nutritional compositions, industrial compositions, livestock compositions, aquatic compositions, medical compositions, commercial compositions, military and paramilitary compositions, office compositions, recreational and park compositions, pet compositions, and water treatment compositions, including cleaning and detergent compositions applicable to any such use, but excluding fabric and household care compositions.

[0255] In one embodiment, the composition may comprise agrochemicals, such as one or more insecticides, fungicides, herbicides, insecticides, acaricides, repellents, attractants, defoliants, plant growth regulators, fertilizers, bactericides, micronutrients and trace elements.Suitable agrochemicals and secondary agents are described in U.S. Patent Nos. 6,204,223 and 4,681,228, and EP 0989803 A1. For example, suitable herbicides include paraquat salts (e.g., paraquat dichloride or paraquat bis(methyl sulfate), diquat salts (e.g., diquat dibromide or diquat alginate), and glyphosate or its salts or esters (e.g., glyphosate isopropylammonium, glyphosate sesquisodium, or glyphosate trimesium, also known as sulfosate). Incompatible pairs of crop protection chemicals can be used in separate chambers, for example, as described in U.S. Pat. No. 5,558,228. Incompatible pairs of crop protection chemicals that can be used include, for example, bensulfuron methyl and molinate; 2,4-D and thifensulfuron methyl; 2,4-D and methyl 2-[[[[N-4-methoxy-6-methyl-1,3,5-triazin-2-yl)-N-methylamino]carbonyl ]amino]-sulfonyl]benzoate; 2,4-D and metsulfuron methyl; maneb or mancozeb and benomyl; glyphosate and metsulfuron methyl; tralomethrin and any organophosphate, such as monocrotophos or dimethoate; bromoxynil and N-[[4,6-dimethoxypyrimidin-2-yl)-amino]carbonyl]-3-(ethylsulfonyl)-2-pyridine-sulfonamide; bromoxynil and methyl 2-[[[[(4-methyl-6-methoxy)-1,3,5-triazin-2-yl)amino]carbonyl]amino]sulfonyl]-benzoate; bromoxynil and methyl 2-[[[[N-(4-methoxy-6-methyl-1,3,5-triazin-2-yl)-N-methylamino]carbonyl]amino]-sulfonyl]benzoate.In another related type of embodiment, the composition may include one or more seeds, optionally together with soil, and optionally together with one or more additional components selected from mulch, sand, peat moss, water jelly crystals, and fertilizer, including, for example, the type of embodiments described in U.S. Pat. No. 8,333,033.

[0256] In another type of embodiment, the composition is a water treatment agent. Such agents can include aggressive chemicals, such as aggressive oxidizing chemicals, as described, for example, in US Patent Application Publication No. 2014 / 0110301 and US Patent No. 8,728,593. For example, disinfectants can include hypochlorites, such as sodium hypochlorite, calcium hypochlorite and lithium hypochlorite; chlorinated isocyanurates, such as dichloroisocyanuric acid (also called "dichloro" or dichloro-s-triazinetrione, 1,3-dichloro-1,3,5-triazinane-2,4,6-trione) and trichloroisocyanuric acid (also called "trichloro" or 1,3,5-trichloro-1,3,5-triazinane-2,4,6-trione). Salts and hydrates of disinfectant compounds are also contemplated. For example, dichloroisocyanuric acid may be provided as sodium dichloroisocyanurate, sodium dichloroisocyanurate dihydrate, among others. Bromine-containing disinfectants, such as 1,3-dibromo-5,5-dimethylhydantoin (DBDMH), 2,2-dibromo-3-nitrilopropionamide (DBNPA), dibromocyanoacetamide, 1-bromo-3-chloro-5,5-dimethylhydantoin; and 2-bromo-2-nitro-1,3-propanediol, among others, may also be suitable for use in unit dose packaging applications. The oxidizing agent may be one described in U.S. Pat. No. 7,476,325, such as potassium hydrogen peroxymonosulfate. The composition may be a pH-adjusting chemical, such as, for example, as described in U.S. Patent Application Publication No. 2008 / 0185347, and may include an acidic component and an alkaline component, such that the composition is effervescent when in contact with water and adjusts the pH of the water. Suitable ingredients include sodium bicarbonate, sodium bisulfate, potassium hydroxide, sulfamic acid, organic carboxylic acids, sulfonic acids, and potassium dihydrogen phosphate. The buffer blend may include, for example, boric acid, sodium carbonate, glycolic acid, and oxone monopersulfate.

[0257] The water treatment agent may be or include a flocculant, for example, as described in US Patent Application Publication No. 2014 / 0124454. The flocculant may include a polymer flocculant, such as polyacrylamide, polyacrylamide copolymers, such as acrylamide copolymers of diallydimethylammonium chloride (DADMAC), dimethylaminoethyl acrylate (DMAEA), dimethylaminoethyl methacrylate (DMAEM), 3-methylamidopropyl trimethylammonium chloride (MAPTAC), or acrylic acid; cationic polyacrylamide; anionic polyacrylamide; neutral polyacrylamide; polyamine; polyvinylamine; polyethyleneimine; polydimethyldiallylammonium chloride; polyoxyethylene; polyvinyl alcohol; polyvinylpyrrolidone; polyacrylic acid; polyphosphoric acid; polystyrene sulfonic acid; or any combination thereof. The flocculant may be selected from chitosan acetate, chitosan lactate, chitosan adipate, chitosan glutamate, chitosan succinate, chitosan malate, chitosan citrate, chitosan fumarate, chitosan hydrochloride, and combinations thereof. The water treatment composition may include a phosphate removing material, such as one or more selected from zirconium compounds, rare earth lanthanide salts, aluminum compounds, iron compounds, or combinations thereof.

[0258] The composition may be, for example, a limescale removal composition, such as citric acid or maleic acid, or sulfates thereof, or any mixtures thereof, as described, for example, in US Patent Application Publication No. 2006 / 0172910.

[0259] Various other types of compositions are contemplated for use in the packets described herein, including particulates, e.g., feathers, e.g., as described in US RE29059 E; superabsorbent polymers, e.g., as described in US Patent Application Publication Nos. 2004 / 0144682 and 2006 / 0173430; pigments and tinters, e.g., as described in US Patent Application Publication Nos. 3,580,390 and 2011 / 0054111; brazing fluxes (e.g., alkali metal fluoroaluminates, alkali metal fluorosilicates and alkali metal fluorozincates), e.g., as described in US Patent Application Publication No. 8,163,104; foodstuffs (e.g., coffee powder or dried soup), e.g., as described in US Patent Application Publication No. 2007 / 0003719; and wound dressings, e.g., as described in US Patent Application Publication No. 4,466,431.

[0260] In the pouches containing the laundry, laundry additive and / or fabric enhancer compositions, the compositions may include one or more of the following non-limiting list of ingredients: fabric care benefit agents; cleaning enzymes; deposition aids; rheology modifiers; builders; bleach; bleaching agents; bleach precursors; bleach boosters; bleach catalysts; perfumes and / or perfume microcapsules (see, for example, US 5,137,646); perfume loaded zeolites; starch encapsulated accords; polyglycerol esters; skin lightening agents; pearlescent agents; enzyme stabilization systems; scavenging agents including anionic dye fixing agents, anionic surface active complexing agents and mixtures thereof; optical brighteners or fluorescent agents; polymers including, but not limited to, soil releasing polymers and / or soil suspending polymers; dispersants; defoamers; non-aqueous solvents; fatty acids; suds suppressors, such as silicone suds suppressors (see US 2003 / 0060390 A1, paragraphs 65-77); cationic dendritic Pungents (see US2004 / 0204337A1 and US2007 / 0219111A1); scum dispersants (see US2003 / 0126282A1, paragraphs 89-90); direct dyes; shade dyes (see US2014 / 0162929A1); colorants; opacifiers; antioxidants; hydrotropes, such as toluenesulfonates, cumenesulfonates, and naphthalenesulfonates; color spots; colored beads, spheres, or extrudates; clay softeners; and antibacterial agents. Any one or more of these ingredients are further described in U.S. Patent Application Publication No. US2010 / 305020A1, U.S. Publication No. 2003 / 0139312A1, and U.S. Patent Application Publication No. US2011 / 0023240A1. Additionally or alternatively, the composition may include a surfactant, a quaternary ammonium compound, and / or a solvent system. The quaternary ammonium compound may be present in a fabric enhancer composition, such as a fabric softener, and may have the structure NR4 + where R is an alkyl or aryl group.

[0261] composite article

[0262] A composite article of the present disclosure includes at least two layers of nonwoven webs. The composite article of the present disclosure may have a first layer of a first nonwoven web including a first plurality of fibers having a first diameter, a second layer of a second nonwoven web including a second plurality of fibers having a second diameter, and a first interface including at least a portion of the first nonwoven web and at least a portion of the second nonwoven web, where the portion of the first nonwoven web and the portion of the second nonwoven web are fused together, the second diameter being smaller than the first diameter. Any nonwoven layer of the composite article may include a water-soluble film laminated thereto.

[0263] The composite articles of the present disclosure may provide one or more advantages including, but not limited to, increased mechanical strength compared to the same nonwoven web of the single layer composite article alone, improved liquid acquisition functionality (e.g., a liquid acquisition layer in a diaper, or a wipe to absorb spills) compared to the same nonwoven web of the single layer composite article alone, and / or improved liquid retention and / or active composition (e.g., an active lotion in a wet wipe) compared to the same nonwoven web of the single layer composite article alone.

[0264] The first interface, which includes at least a portion of the first nonwoven web and at least a portion of the second nonwoven web, is a region of the composite where the first and second nonwoven webs overlap and the first and second plurality of fibers are intermingled. Typically, the portion of the first nonwoven web that forms the first interface is the outer surface of the first nonwoven web. In an embodiment, the first interface comprises 50% or less of the thickness of the first nonwoven web, 40% or less, 30% or less, 25% or less, 20% or less, 10% or less, 5% or less, 2.5% or less, or 1% or less of the thickness of the first nonwoven web. In an embodiment, the first interface comprises at least 0.1%, at least 0.5%, at least 1%, or at least 5% of the thickness of the first nonwoven web. In an embodiment, the first interface comprises about 0.1% to about 25% of the thickness of the first nonwoven web. Generally, the portion of the second nonwoven web that forms the interface is the outer surface of the second nonwoven web. In an embodiment, the interface comprises 75% or less, 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, 25% or less, 20% or less, or 15% or less of the thickness of the second nonwoven web. In an embodiment, the first interface comprises at least 1%, at least 5%, at least 10%, at least 20%, at least 25%, at least 30%, or at least 40% of the thickness of the second nonwoven web. In an embodiment, the first interface comprises about 1% to about 75% of the thickness of the second nonwoven web.

[0265] As used herein, unless otherwise specified, two layers of nonwoven webs are "fused" when at least a portion of the fibers from each web are bonded to the fibers from the other web. As described herein, fiber bonding includes fiber entanglement. The two layers of nonwoven webs may be fused using any suitable method. In an embodiment, a portion of the first nonwoven web and a portion of the second nonwoven web are heat fused, solvent fused, or both. In an embodiment, a portion of the first nonwoven web and a portion of the second nonwoven web are heat fused. Heat fusion may include the use of heat and / or pressure. In an embodiment, one or both of the two separate nonwoven webs may be heated until the fibers soften, and then the webs are compressed together, and as the fibers cool, at least a portion of the fibers from each web are bonded to at least a portion of the fibers from the other web. In an embodiment, one or both of the first and second nonwoven webs may be applied in an in-line process such that the melt-spun, heated soft fibers are applied directly to the pre-formed nonwoven web after passing through the die assembly and fuse to the fibers of the pre-formed nonwoven forming a fused interface. In an embodiment, a portion of the first nonwoven web and a portion of the second nonwoven web are solvent fused. Solvent fusing may include applying a binder solution to one or both of the nonwoven webs, followed by contacting the nonwoven webs such that, upon drying, at least a portion of the fibers from each web bond to at least a portion of the fibers from the other web. Solvent fusing may be performed as a separate process involving two separate pre-formed webs, or it may be an in-line process in which a binder solution is applied to a pre-formed nonwoven web and a second nonwoven web is formed on the pre-formed nonwoven web in a continuous process. The binder solution for solvent fusing of the nonwoven webs may be any binder solution described herein for bonding. As used herein, unless otherwise specified, "preformed nonwoven web" includes formed but unbonded nonwoven webs, and formed and bonded nonwoven webs.As used herein, unless otherwise specified, "separate nonwoven webs" encompasses nonwoven webs formed by carding or air laying staple fibers or by a continuous process, and the nonwoven webs may be bonded or unbonded. In embodiments, fusion of two nonwoven webs can also be used to bond one or both of the nonwoven webs.

[0266] In an embodiment, the first interface is solvent fused and the solvent is selected from the group consisting of water, ethanol, methanol, DMSO, glycerin, and combinations thereof. In an embodiment, the first interface is solvent fused and the solvent is selected from the group consisting of water, glycerin, and combinations thereof. In an embodiment, the first interface is solvent fused using a binder solution comprising polyvinyl alcohol and water, glycerin, or a combination thereof. In an embodiment, the first interface is solvent fused using a binder solution comprising polyvinyl alcohol, latex, or a combination thereof, and water, glycerin, or a combination thereof.

[0267] As used herein, unless otherwise specified, if the average fiber diameter of a first type of fiber is smaller than the average fiber diameter of a second type of fiber, the first type of fiber has a diameter "smaller" than the diameter of the second type of fiber. For example, a first type of fiber may have a diameter size distribution that overlaps with a second type of fiber, and still have a smaller diameter as long as the average fiber diameter for the first type of fiber is smaller than the average fiber diameter of the second type of fiber. In an embodiment, the smaller fiber type has an average fiber diameter that is smaller than the minimum diameter of the diameter size distribution of the larger fiber type. A diameter difference exists when the difference can be visualized using projection microscope imaging, as outlined in SO137:2015. In an embodiment, for example, when multiple meltspun layers are used, the diameter difference between the smaller and larger fiber types can be submicron. In embodiments, the difference in diameter between the smaller and larger fiber types can be about 1 micron to about 300 microns, about 5 microns to about 300 microns, about 5 microns to about 250 microns, about 5 microns to about 200 microns, about 10 microns to about 150 microns, about 10 microns to about 100 microns, about 10 microns to about 90 microns, about 15 microns to about 80 microns, about 15 microns to about 70 microns, about 20 microns to about 60 microns, about 20 microns to about 50 microns, or about 25 microns to about 45 microns. In embodiments, the difference in diameter between the smaller and larger fiber types can be about 5 microns to about 75 microns. In embodiments, the difference in diameter between the smaller and larger fiber types can be about 20 microns to about 80 microns. Without intending to be bound by theory, it is believed that by providing a composite of two nonwoven webs where the nonwoven webs are fused together and the second nonwoven web has a smaller fiber diameter than the first nonwoven web, the adsorption / absorption rate and fluid capacity of the composite article may be advantageously improved, direct adsorption / absorption from the larger diameter fibers to the smaller diameter fibers where fluid preferentially migrates; the surface to volume ratio of the nonwoven composite article may be increased compared to a single diameter material, resulting in increased loading capacity and / or improved dispersion and / or improved overall dissolution of the nonwoven composite article compared to a nonwoven having a single diameter material.The average diameter of the fibers of the individual web layers can be any diameter presented herein. In embodiments, the first plurality of fibers of the first layer of the first nonwoven fabric can have a diameter of about 10 microns to about 300 microns, about 50 microns to about 300 microns, or greater than about 100 microns to about 300 microns. In embodiments, the first plurality of fibers can have an average diameter of greater than about 100 microns to about 300 microns. In embodiments where the nonwoven fabric layer of the nonwoven fabric composite comprises a blend of fiber types having different diameters, if the distribution of fiber diameters is unimodal, the average fiber diameter refers to the average fiber diameter of the blend. The blend of fiber types can have a bimodal or higher distribution of fiber diameters of the nonwoven fabric layer. When a blend of fibers has a bimodal or higher order modal diameter distribution, a fiber has a smaller diameter than the fibers of said blend if it has an average fiber diameter smaller than the average of the distribution of the smallest diameter fibers of the blend, and a fiber has a larger diameter than the fibers of said blend if it has an average fiber diameter larger than the average of the distribution of larger diameter fibers of the blend.

[0268] In an embodiment, the composite article further comprises a third layer of a third nonwoven web comprising a third plurality of fibers. In an embodiment in which the nonwoven composite article comprises a third layer of a third nonwoven web, the second layer may be provided between the first layer and the third layer, and at least a second portion of the second nonwoven web and at least a portion of the third nonwoven web may be fused to provide a second interface. The second interface, comprising at least a second portion of the second nonwoven web and at least a portion of the third nonwoven web, is an area of ​​the composite where the second and third nonwoven webs overlap and the second plurality of fibers and the third plurality of fibers are intermingled. In some embodiments, depending on the thickness of the second layer of the second nonwoven web, the first plurality of fibers and the third plurality of fibers may be intermingled and / or fused such that there is no clear delineation between the first interface and the second interface. Typically, the portion of the second nonwoven web that forms the second interface is the outer surface of the second nonwoven web opposite the outer surface of the second nonwoven web that is fused to the first nonwoven web. In an embodiment, the second interface constitutes 75% or less, 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, 25% or less, 20% or less, or 15% or less of the thickness of the second nonwoven web. In an embodiment, the second interface constitutes at least 1%, at least 5%, at least 10%, at least 20%, at least 25%, at least 30%, or at least 40% of the thickness of the second nonwoven web. In an embodiment, the second interface constitutes about 1% to about 75% of the thickness of the second nonwoven web. In an embodiment, the portion of the third nonwoven web that forms the second interface is the outer surface of the third nonwoven web. In embodiments, the second interface comprises 50% or less of the thickness of the third nonwoven web, 40% or less, 30% or less, 25% or less, 20% or less, 10% or less, 5% or less, 2.5% or less, or 1% or less of the thickness of the first nonwoven web. In embodiments, the second interface comprises at least 0.1%, at least 0.5%, at least 1%, or at least 5% of the thickness of the third nonwoven web.In an embodiment, the second interface comprises about 0.1% to about 25% of the thickness of the third nonwoven fabric.

[0269] In an embodiment, the second portion of the second nonwoven web and a portion of the third nonwoven web are heat fused, solvent fused, or both. In an embodiment, the second portion of the second nonwoven web and a portion of the third nonwoven web are heat fused. In an embodiment, the second portion of the second nonwoven web and a portion of the third nonwoven web are solvent fused.

[0270] In an embodiment, the second interface is solvent fused, and the solvent is selected from the group consisting of water, ethanol, methanol, DMSO, glycerin, and combinations thereof. In an embodiment, the second interface is solvent fused, and the solvent is selected from the group consisting of water, glycerin, and combinations thereof. In an embodiment, the second interface is solvent fused using a binder solution comprising polyvinyl alcohol and water, glycerin, or a combination thereof. In an embodiment, the second interface is solvent fused using a binder solution comprising polyvinyl alcohol, latex, or a combination thereof, and water, glycerin, or a combination thereof.

[0271] In an embodiment, the first layer of the first nonwoven web and the second layer of the second nonwoven web have different porosities. As used herein, unless otherwise specified, two nonwoven webs have "different porosities" if the difference in porosity of the nonwoven webs is at least about 1%. In an embodiment, the difference in porosity between two layers of the nonwoven web of a composite article can be from about 1% to about 20%. For example, one layer of the nonwoven web of the composite article can have a porosity of about 80% and the second layer of the nonwoven web of the composite article can have a porosity of about 85%, with a porosity difference of 5%. In an embodiment, the porosity of the second nonwoven web is lower than the porosity of the first nonwoven web. In an embodiment, the porosity of the second nonwoven web is the same as the porosity of the first nonwoven web. As used herein, unless otherwise specified, two nonwoven webs have the "same porosity" if the difference in porosity value between the two nonwoven webs is less than 1%.

[0272] In embodiments where the composite article includes a third layer of a third nonwoven web, the third nonwoven web may have the same or different porosity as the first nonwoven web. In embodiments, the third nonwoven web may have the same porosity as the first nonwoven web. In embodiments, the third nonwoven web may have a different porosity than the first nonwoven web. In embodiments, the third nonwoven web may have a lower porosity than the first nonwoven web. In embodiments, the third nonwoven web may have the same porosity as the second nonwoven web. In embodiments, the third nonwoven web may have a different porosity than the second nonwoven web. In embodiments, the third nonwoven web may have a lower porosity than the second nonwoven web. In embodiments, the second nonwoven web may be less porous than the first nonwoven web and the third nonwoven web may be less porous than the second nonwoven web. In an embodiment, the nonwoven composite article may have a gradient of porosity between the layers of the nonwoven web, one outer surface of the composite structure may have the greatest porosity and the other outer surface of the composite structure may have the least porosity. In an embodiment, the composite structure may have a gradient of porosity between the layers of the nonwoven web, the outer surface of the composite structure may have the greatest porosity and the middle layer(s) of the composite structure may have the least porosity. In an embodiment, the composite structure may include a fourth or more layers of nonwoven web, the middle layer(s) may include the second and third layers of nonwoven web (in the case of a four-layer composite structure), or the third layer of nonwoven web (in the case of a five-layer composite structure).

[0273] Without intending to be bound by theory, it is believed that when the porosity of a composite structure includes a gradient, the composite structure advantageously has enhanced liquid absorption from the more porous outer surface to the less porous outer surface or to the less porous intermediate layer(s).

[0274] The fibers of any given nonwoven layer of the composite article may be any of the fibers disclosed herein and may be the same or different. In embodiments, the composition of the fiber-forming material of the first, second, and third pluralities of fibers may be the same or different, and may differ in characteristics such as, for example, diameter, length, toughness, shape, stiffness, elasticity, solubility, melting point, glass transition temperature (T g ), fiber-forming material, color, or any combination thereof. Table 1 below illustrates contemplated composite articles in which the nonwoven layers may include fibers having three different fiber compositions, where each of the letters "A," "B," and "C" refers to a particular fiber composition, and "-" means that the contemplated composite article does not include a third layer of nonwoven web. Each of the fiber compositions A, B, and C may be (a) a single fiber type with a single fiber-forming material, (b) a single fiber type with a blend of fiber-forming materials, (c) a blend of fiber types where each fiber type includes a single fiber-forming material, (d) a blend of fiber types where each fiber type includes a blend of fiber-forming materials, or (e) a blend of fiber types where each fiber type includes a single fiber-forming material or a blend of fiber-forming materials. [Table 1]

[0275] In an embodiment, the first plurality of fibers comprises a water-soluble polyvinyl alcohol fiber-forming material. In an embodiment, the second plurality of fibers comprises a water-soluble polyvinyl alcohol fiber-forming material. In an embodiment, the first plurality of fibers and the second plurality of fibers comprise a water-soluble polyvinyl alcohol fiber-forming material. In an embodiment including a third layer of the nonwoven web having a third plurality of fibers, the third plurality of fibers may comprise a water-soluble polyvinyl alcohol fiber-forming material. In an embodiment, the polyvinyl alcohol fiber-forming material may be present in one or more fiber types of the plurality of fibers. The water-soluble polyvinyl alcohol fiber-forming material of any of the first plurality, second plurality, or third plurality of fibers may be any water-soluble polyvinyl alcohol fiber-forming material disclosed herein. In embodiments where two or more of the first plurality of fibers, the second plurality of fibers, and / or the third plurality of fibers comprise a polyvinyl alcohol fiber-forming material, the polyvinyl alcohol may be the same or different in each plurality and may be the sole fiber-forming material or part of a blend of fiber-forming materials in each plurality, and when each plurality comprises different polyvinyl alcohol fibers, the length to diameter ratio (L / D), toughness, shape, stiffness, elasticity, solubility, melting point, glass transition temperature (T g ), fiber chemistry, color or a combination thereof.

[0276] In embodiments, the fibers of the first plurality of fibers, the second plurality of fibers and / or the third plurality of fibers may include a fiber forming material other than a polyvinyl alcohol fiber forming material.

[0277] In an embodiment, the first nonwoven web has a toughness ratio (MD:CD) of about 0.5 to about 1.5. In an embodiment, the first nonwoven web has a MD:CD of about 0.8 to about 1.25. In an embodiment, the first nonwoven web has a MD:CD of about 0.9 to about 1.1. In an embodiment, the second nonwoven web has a toughness ratio (MD:CD) of about 0.5 to about 1.5. In an embodiment, the second nonwoven web has a MD:CD of about 0.8 to about 1.25. In an embodiment, the second nonwoven web has a MD:CD of about 0.9 to about 1.1. In an embodiment, the third nonwoven web has a toughness ratio (MD:CD) of about 0.5 to about 1.5. In an embodiment, the third nonwoven web has a MD:CD of about 0.8 to about 1.25. In an embodiment, the third nonwoven web has a MD:CD of about 0.9 to about 1.1. In an embodiment, the nonwoven composite article has a toughness ratio (MD:CD) ranging from about 0.5 to about 1.5, about 0.8 to about 1.25, about 0.9 to about 1.1, or about 0.95 to about 1.05. In an embodiment, the nonwoven composite article has a MD:CD of about 0.8 to about 1.5. In an embodiment, the nonwoven composite article has a MD:CD of about 0.9 to 1.1. The MD:CD of a nonwoven composite article is related to the MD:CD ratio of each individual layer of the nonwoven web present in the composite article. Without intending to be bound by theory, it is believed that the MD:CD of a composite article cannot be determined by considering the MD and CD of each layer of the nonwoven web individually, but that the MD and CD of the nonwoven composite article must be measured. Without intending to be bound by theory, it is believed that as the toughness ratio MD:CD of a nonwoven composite article approaches 1, the durability of the composite article increases and provides the nonwoven with greater resistance to degradation when stressed during use. Additionally, without intending to be bound by theory, it is believed that a composite article that includes at least one layer of a meltspun nonwoven web has an MD:CD ratio that is closer to 1:1 than an otherwise identical composite article that includes all carded layers.

[0278] The basis weight of the nonwoven composite article of the present disclosure is not particularly limited and may be about 5 g / m 2 ~Approx. 150g / m 2 , about 5g / m2 ~Approx. 125g / m 2 , about 5g / m 2 ~about 100g / m 2 , about 5g / m 2 ~about 70g / m 2 , about 5g / m 2 ~about 50g / m 2 , about 5g / m 2 ~About 30g / m 2 In an embodiment, the nonwoven composite article of the present disclosure may have a fiber densitometry range of about 5 g / m 2 ~about 50g / m 2 In an embodiment, the nonwoven composite article of the present disclosure may have a basis weight of about 50 g / m 2 ~Approx. 150g / m 2 In an embodiment, the first layer of the nonwoven web may have a basis weight of about 30 g / m 2 ~about 70g / m 2 and the nonwoven composite article may have a basis weight of about 60 g / m 2 ~Approx. 150g / m 2 In an embodiment, the first layer of the nonwoven web may have a basis weight of about 5 g / m 2 ~about 15g / m 2 In an embodiment, the first layer of the nonwoven web may have a basis weight of about 5 g / m 2 ~about 15g / m 2 and the nonwoven composite article may have a basis weight of about 15 g / m 2 ~about 50g / m 2 In an embodiment, the third layer of nonwoven web may have a basis weight in the range of about 5 g / m 2 ~about 15g / m 2 In an embodiment, the first layer of the nonwoven web may have a basis weight of about 5 g / m 2 ~about 15g / m 2 and the third layer of nonwoven web may have a basis weight of about 5 g / m 2 ~about 15g / m 2In an embodiment, the second layer of nonwoven web may be present in the composite article at about 2.5 wt.% to about 10 wt.%, based on the total weight of the composite article. In an embodiment, the second layer of nonwoven web may be present in the composite article at about 2.5 wt.% to about 10 wt.%, based on the total weight of the composite article, and the first layer of nonwoven web may be present in the composite article at about 90 wt.% to about 97.5 wt.%, based on the total weight of the composite article. In an embodiment, the second layer of nonwoven web may be present in the composite article at about 2.5 wt.% to about 10 wt.%, based on the total weight of the composite article, and the first layer of nonwoven web and the third layer of nonwoven web together are present at about 90 wt.% to about 97.5 wt.%, based on the total weight of the composite article. In an embodiment, the third layer of nonwoven web may be included in the composite article at about 2.5 wt.% to about 10 wt.%, based on the total weight of the composite article, and the first layer of nonwoven web and the second layer of nonwoven web together include about 45 wt.% to about 48 wt.%, based on the total weight of the composite article.

[0279] In embodiments, the fiber diameter of the first plurality of fibers may be substantially uniform. In embodiments, the fiber diameter of the second plurality of fibers may be substantially uniform. In embodiments, the fiber diameter of the third plurality of fibers may be substantially uniform. In embodiments, the fiber diameter of the first plurality of fibers and the third plurality of fibers may be substantially uniform. In embodiments, the fiber diameter of each of the first plurality of fibers, the second plurality of fibers, and the third plurality of fibers may be substantially uniform.

[0280] In an embodiment, the nonwoven composite article may have improved modulus, tensile strength, elongation, toughness, or a combination thereof, in the machine direction, cross direction, or both, compared to an identical article including only the first layer. In an embodiment, the nonwoven composite article may have improved modulus, tensile strength, elongation, toughness, or a combination thereof, in the machine direction, compared to an identical article including only the first layer. In an embodiment, the nonwoven composite article may have improved modulus, tensile strength, elongation, toughness, or a combination thereof, in the cross direction, compared to an identical article including only the first layer. In an embodiment, the nonwoven composite article may have improved modulus, tensile strength, elongation, toughness, or a combination thereof, in the machine direction and cross direction, compared to an identical article including only the first layer.

[0281] Method for preparing a composite article

[0282] Generally, the composite article can be made using any process known in the art suitable for combining two or more layers of nonwoven webs such that at least a portion of the first layer and a portion of the second layer are fused together, thereby forming an interface.

[0283] In an embodiment, a method of forming a nonwoven composite article of the present disclosure includes: (a) depositing a second layer comprising a second nonwoven web onto a first layer comprising the first nonwoven web under conditions sufficient to fuse at least a portion of the first nonwoven web to at least a portion of the second nonwoven web, thereby forming a first interface; and (b) optionally depositing a third layer comprising a third nonwoven web onto the second layer comprising the second nonwoven web under conditions sufficient to fuse at least a second portion of the second nonwoven web to at least a portion of the third nonwoven web, thereby forming a second interface. may include.

[0284] In embodiments, steps (a) and (b) may be repeated to include additional nonwoven layers in the composite structure, for example a fourth nonwoven layer, a fifth nonwoven layer, etc.

[0285] Generally, conditions sufficient to fuse at least a portion of a first nonwoven web to at least a portion of a second nonwoven web and / or fuse at least a second portion of the second nonwoven web to at least a portion of a third nonwoven web may include heat fusing and / or solvent fusing as described herein.

[0286] In an embodiment of the aforementioned method, the first layer may comprise a carded nonwoven web. In an embodiment of the aforementioned method, the third layer may comprise a carded nonwoven web or a meltspun nonwoven web. In an embodiment of the aforementioned method, the second layer may comprise a meltspun nonwoven web or an airlaid nonwoven web. In an embodiment, the first layer may comprise a carded nonwoven web, the second layer may comprise a meltspun nonwoven web, and the third layer may comprise a carded nonwoven web. In an embodiment, the first layer may comprise a carded nonwoven web, the second layer may comprise a meltblown nonwoven web, and the third layer may comprise a carded nonwoven web. In an embodiment, the second layer may comprise an airlaid nonwoven web. In an embodiment, the first layer may comprise a carded nonwoven web, the second layer may comprise an airlaid nonwoven web, and the third layer may comprise a meltspun nonwoven web. In an embodiment, the first layer may comprise a carded nonwoven web, the second layer may comprise an airlaid nonwoven web, and the third layer may comprise a meltblown nonwoven web. In an embodiment, the nonwoven composite article may comprise five layers of nonwoven webs, the first layer may comprise a carded nonwoven web, the second layer may comprise an airlaid nonwoven web, the third layer may comprise a meltspun nonwoven web, the fourth layer may comprise an airlaid nonwoven web, and the fifth layer may comprise a carded nonwoven web. In an embodiment, the nonwoven composite article may comprise five layers of nonwoven webs, the first layer may comprise a carded nonwoven web, the second layer may comprise an airlaid nonwoven web, the third layer may comprise a meltblown nonwoven web, the fourth layer may comprise an airlaid nonwoven web, and the fifth layer may comprise a carded nonwoven web. In embodiments, the second nonwoven web may include a cellulosic fiber forming material.

[0287] Flushable Wipes

[0288] Flushable wipes of the present disclosure may comprise a nonwoven web of the present disclosure and / or a composite article according to the present disclosure.

[0289] Flushable wipes may comprise a plurality of fibers of the present disclosure, which may include water soluble fibers and optionally water insoluble fibers.

[0290] In embodiments in which the flushable wipe comprises a nonwoven web comprising water soluble and water insoluble fibers, the ratio of water insoluble fiber to water soluble fiber can be in the range of about 1:18 to about 4:1, about 1:10 to about 3:1, about 1:5 to about 2:1, or about 1:2 to about 2:1, e.g., about 1:18, 1:16, 1:14, 1:12, 1:10, 1:5, 1:3, 1:2, 1:1, 2:1, 3:1, or 4:1.

[0291] The flushable wipes of the present disclosure may include a cleaning lotion. The flushable wipes of the present disclosure generally include fibers with a surface energy high enough to allow the fibers to be easily wetted by a cleaning lotion during the wetting step of the wipe manufacturing process. Thus, in an embodiment, at least a portion of at least one outer layer of the nonwoven composite article of the flushable wipe includes hydrophilic fibers. In an embodiment, at least a portion of each outer layer of the nonwoven composite article used to prepare the flushable wipe includes hydrophilic fibers. As used herein, unless otherwise specified, "hydrophilic fiber" refers to any fiber whose surface is hydrophilic. The fiber may have a hydrophilic surface if the fiber includes, for example, a hydrophilic fiber-forming material, the fiber is a core / sheath type bicomponent fiber that includes a hydrophilic fiber-forming material in the sheath, and / or the fiber is surface-treated to include a hydrophilic material on its surface. Without intending to be bound by theory, it is believed that the hydrophilic fibers of the nonwoven fabric may promote capillary action / wicking of liquid from the surface of the nonwoven fabric, providing improved liquid acquisition compared to the same nonwoven fabric without the hydrophilic fibers.

[0292] Non-limiting examples of uses for the wipes include surface cleaning, skin cleaning, automotive applications, baby care, feminine care, hair cleaning, as well as the removal or application of makeup, skin conditioners, ointments, sunscreens, insect repellents, medicines, varnishes, or industrial and institutional cleaning.

[0293] Lotion Composition

[0294] The flushable wipes of the present disclosure may include a lotion composition that moistens the substrate to facilitate cleaning. In embodiments in which the flushable wipe is a personal care wipe, the lotion composition may also include ingredients to, for example, soothe, soften or care for the skin, improve lotion feel, improve residue removal from the skin, provide a pleasant fragrance and / or prevent bacterial growth.

[0295] The lotion composition may have a pH of about 5.5 or close to physiological skin pH. A low pH lotion composition may have a pH of about 3.8 or close to, which may be useful when the wipe is used to remove alkaline residues, such as residues from bowel waste, helping to restore a healthy acidic skin pH of approximately 5, and / or rendering irritants from bowel waste non-irritating by inactivating fecal enzymes. A low pH lotion may also inhibit microbial growth. In an embodiment where the pH of the lotion composition is about 4 or less, the fibers of the first plurality of fibers, the second plurality of fibers and / or the third plurality of fibers may comprise a polyvinyl alcohol copolymer. The copolymer may be provided as the sole fiber-forming material in a fiber of a fiber blend or as one component of a fiber-forming material in a fiber that comprises a blend of fiber-forming materials. In a refinement of the foregoing embodiment, the fiber may comprise a blend of polyvinyl alcohol copolymers and homopolymers. The polyvinyl alcohol copolymers and homopolymers may be provided in a ratio of about 1:1 to about 4:1. In a further refinement of the foregoing embodiment, the polyvinyl alcohol copolymer-containing fiber may be blended with a water insoluble fiber.

[0296] The lotion composition may include a superwetter, a rheology modifier, an emollient and / or an emulsifier. The superwetter may be present in an amount of about 0.01% to 0.2% by weight of the superwetter based on the total weight of the lotion composition. The superwetter may be selected from the group consisting of trisiloxane, polyether dimethicone (wherein the polyether functional group is PEG, PPG or mixtures thereof), and mixtures of the foregoing.

[0297] The rheology modifier may be present in an amount of about 0.01% to 0.5% by weight of the rheology modifier based on the total weight of the lotion composition. The rheology modifier may be selected from the group consisting of xanthan gum, modified xanthan gum and combinations thereof.

[0298] The emollient, if present, may be a viscosity emollient. Suitable emollients include, but are not limited to, PEG-10 sunflower oil glycerides, sunflower oil, palm oil, olive oil, emu oil, babassu oil, evening primrose oil, palm kernel oil, cod liver oil, cottonseed oil, jojoba oil, meadowfoam seed oil, sweet almond oil, canola oil, soybean oil, avocado oil, safflower oil, coconut oil, sesame oil, rice bran oil, grape seed oil, mineral oil, isopropyl stearate, isostearyl isononanoate, diethylhexyl fumarate, diisopropyl ether, isopropyl alcohol ... Stearyl malate, triisocetyl citrate, stearyl stearate, methyl palmitate, methylheptyl isostearate, petrolatum, lanolin oil and wax, long chain alcohols such as cetyl alcohol, stearyl alcohol, behenyl alcohol, isostearyl alcohol and 2-hexyl-decanol, myristyl alcohol, dimethicone fluids of various molecular weights and mixtures thereof, PPG-15 stearyl ether (also known as arlatone E), shea butter, olive butter, sunflower butter, coconut butter, jojoba butter, cocoa butter, squalane and squalene, isoparaffin, polyethylene glycols of various molecular weights, polypropylene glycols of various molecular weights or mixtures thereof.

[0299] The emulsifier, if present, may be a solid at room temperature. Suitable emulsifiers include, but are not limited to, laureth-23, ceteth-2, ceteth-10, ceteth-20, ceteth-21, ceteareth-20, steareth-2, steareth-10, steareth-20, oleth-2, oleth-10, oleth-20, steareth-100, steareth-21, PEG-40 sorbitan peroleate, PEG-8 stearate, PEG-40 stearate, PEG-50 stearate, PEG-100 stearate, sorbitan laurate, sorbitan palmitate, sorbitan stearate, sorbitan tristearate. , sorbitan oleate, sorbitan trioleate, polysorbate 20, polysorbate 21, polysorbate 40, polysorbate 60, polysorbate 61, polysorbate 65, polysorbate 80, polysorbate 81, polysorbate 85, PEG-40 hydrogenated castor oil, citric acid esters, microcrystalline wax, paraffin wax, beeswax, carnauba wax, ozokerite wax, cetyl alcohol, stearyl alcohol, cetearyl alcohol, myristyl alcohol, behenyl alcohol and mixtures thereof.

[0300] In embodiments, the cleansing lotion comprises an aqueous emulsion that includes an emollient and an emulsifier.

[0301] The cleaning lotion may further comprise a humectant, including but not limited to glycerin, propylene glycol and phospholipids; a fragrance, such as the essential oils and perfumes described herein; a preservative; an enzyme; a colorant; an oil absorbent; an insecticide; a fertilizer; an activator; an acid catalyst; a metal catalyst; an ion scavenger; a detergent; a bactericide; a surfactant; a bleaching agent; a bleaching component; and a fabric softener. In an embodiment, the cleaning lotion comprises a fragrance, a preservative, an enzyme, a colorant, an oil absorbent, an insecticide, an ion scavenger, a detergent, a bactericide, or a combination thereof.

[0302] The preservative prevents the growth of microorganisms in the liquid lotion, flushable wipe and / or the substrate on which the wipe is used. The preservative may be hydrophobic or hydrophilic. Suitable preservatives include, but are not limited to, parabens such as methylparaben, propylparaben, alkyl glycinates, iodine derivatives and combinations thereof.

[0303] The lotion loading may be 150% to 480%. As used herein, "loading" refers to combining the nonwoven web or composite article with the lotion composition, regardless of the method used to combine the nonwoven web or composite article with the lotion composition, i.e., dipping, spraying, kiss roll, etc., i.e., the lotion composition is loaded onto or into the nonwoven web or composite article. "Lotion loading" refers to the amount of lotion loaded onto or into the nonwoven web or composite article, expressed as a percentage of the weight of the lotion relative to the weight of the dry (unloaded) nonwoven web or composite article. It may be desirable for flushable wipes to be loaded with lotion to such an extent that some of the lotion can be readily transferred to the substrate (e.g., skin or another surface to be cleaned) during use. The transfer may enable the transfer of compounds that facilitate cleaning, provide a pleasant sensation to the user (such as a smooth skin feel or a cool feeling due to evaporation), and / or provide a beneficial function to the substrate.

[0304] Flushable wipes can be nonwoven webs or composite articles with a high density of interstitial spaces between the fibers that make up the wipe. In order to maintain sufficient lotion available on the surface of the wipe for transfer to the substrate, most of the interstitial spaces in the wipe can be filled with lotion. For example, the lotion in the interstitial spaces may not be readily available for transfer to the substrate, so that excess lotion can be loaded into the wipe in sufficient quantity to provide a sufficient wet feel, thereby informing the user that lotion is available for transfer to the substrate. Advantageously, the nonwoven composite articles used in flushable wipes can have a porosity gradient as described herein, which can facilitate the loading of lotion into the wipe.

[0305] Flushable wipes can be made by wetting a nonwoven web or composite article with at least 1 gram of liquid cleaning lotion per gram of dry fibrous composite. Suitable methods for delivering cleaning lotion to a nonwoven web or composite article include, but are not limited to, immersion, spraying, embedding, extrusion coating, and dip coating. After wetting, the wet composite article can be folded, stacked, cut to length, and wrapped as desired. Flushable wipes are generally of sufficient size to be convenient to handle, yet small enough to be easily disposed of in a sewer system. The wet composite article can be cut or folded to such size during the manufacturing process, or can be of a larger size and have a means, such as a tear line, that allows the user to separate individual wipes from the web to the desired size.

[0306] In an embodiment, the flushable wipe of the present disclosure comprises a nonwoven web of the present disclosure and a cleaning lotion. In an embodiment, the flushable wipe of the present disclosure comprises a nonwoven composite article of the present disclosure and a cleaning lotion. In an embodiment, the flushable wipe of the present disclosure consists of a nonwoven composite article of the present disclosure and a cleaning lotion.

[0307] Absorbent articles

[0308] The nonwoven webs and nonwoven composite articles of the present disclosure can be used as liquid acquisition layers in absorbent articles. Absorbent articles can include bibs, chest pads, care mats, cleaning pads (e.g., floor cleaning pads), diapers, pant diapers, incontinence liners, pads and other articles (e.g., adult incontinence diapers, adult incontinence pads, adult incontinence pants, potty training liners, potty training pads, potty training pants and pet training pads, e.g., puppy pads), interlabial devices, menstrual pads, pant liners, sanitary napkins, tampons, spill absorbing mats, spill absorbing pads, spill absorbing rolls, wound dressings, and the like. In one aspect, any of the aforementioned articles can be disposable. The term "disposable" refers to an article that is designed or intended to be discarded after a single use. That is, disposable articles are not intended to be washed or otherwise restored or reused, and in embodiments may not be capable of being washed, restored or reused.

[0309] As used herein, the term "absorbent article" includes articles that absorb and contain liquids such as body exudates. The term "absorbent article" is intended to include diapers, incontinence articles, sanitary napkins, and the like. The term "incontinence article" is intended to include pads, undergarments (pads held in place by some type of support system such as a belt or the like), absorbent article inserts, absorbent article volume boosters, briefs, bed pads, and the like, whether worn by an adult or other incontinent person. At least some such absorbent articles are intended for the absorption of bodily fluids such as menstrual flow or blood, vaginal secretions, urine, sweat, breast milk, and bowel waste.

[0310] As used herein, "diaper" refers to a device that is intended to be placed against the skin of a wearer to absorb and contain various exudates discharged from the body. Diapers are generally worn by infants and incontinent individuals around the waist and legs of the wearer on the lower torso. Examples of diapers include infant or adult diapers and pant-like diapers, such as training pants. "Training pants" as used herein refers to disposable undergarments with a waist opening and leg openings designed for infant or adult wearers. The pant may be placed in position on the wearer by inserting the wearer's legs into the leg openings and moving the pant into position around the lower torso of the wearer. The pant may be preformed by any suitable technique, including, but not limited to, connecting parts of the article together using refastenable and / or non-refastenable bonds (e.g., stitching, welding, adhesive, tight bonds, fasteners, etc.). The pant may be preformed at any location along the circumference of the article (e.g., side fastening, front waist fastening).

[0311] The absorbent article of the present disclosure typically comprises a liquid permeable topsheet, a liquid impermeable backsheet connected to the topsheet, and a liquid acquisition layer and an absorbent core between the topsheet and the backsheet. In embodiments where the absorbent article is a wearable article (e.g., an incontinence article, a sanitary napkin, etc.), the article may have a wearer-facing side and an outer side. Generally, the liquid permeable topsheet is on the wearer-facing side of the absorbent article, and the liquid impermeable backsheet is on the outer side. The absorbent core is generally a sheet-like structure, and when provided as a wearable, has a wearer-facing side and an outer side.

[0312] In general, the liquid-permeable topsheet can be any liquid-permeable topsheet known in the art. In the case of wearable articles, the topsheet can be fully or partially elasticated or shortened to provide a void between the topsheet and the absorbent core. In general, the liquid-impermeable backsheet can be any liquid-impermeable backsheet known in the art. The backsheet prevents the exudate absorbed by the absorbent core and contained within the article from contacting any substrate with which the absorbent article may come into contact. The backsheet is liquid-impermeable and can include laminates of nonwovens and thin plastic films, such as thermoplastic films. Suitable backsheet films include those manufactured by Tredegar Industries Inc. of Terre Haute, Ind. and sold under the trade names X15306, X10962 and X10964. Other suitable backsheet materials can include breathable materials that allow vapor to escape from the absorbent article while preventing liquid from passing through the backsheet. Exemplary breathable materials may include materials such as woven webs, nonwoven webs, and composite materials such as those manufactured by Mitsui Toatsu Col, Japan under the designation ESPOIR NO and by EXXON Chemical Co., Bay City, Tex. under the designation EXXAIRE.

[0313] The absorbent core is disposed between the topsheet and the backsheet. The absorbent core may generally comprise any absorbent material capable of absorbing and retaining liquids, such as urine and other body exudates. The absorbent core may comprise a wide variety of liquid-absorbing materials commonly used in disposable diapers and other absorbent articles, such as superabsorbent polymers, comminuted wood pulp (airfelt), creped cellulose wadding; absorbent foams, absorbent sponges, absorbent gelling materials, or any other known absorbent materials, or combinations of materials. The absorbent core may comprise a small amount (less than about 10%) of non-liquid-absorbing materials, such as adhesives, waxes, oils, and the like.

[0314] Generally, the liquid acquisition layer comprises a nonwoven web of the present disclosure comprising a plurality of fibers comprising a water soluble polyvinyl alcohol fiber forming material. The plurality of fibers may comprise a single fiber type or a blend of fiber types, and the fibers may comprise a single polyvinyl alcohol fiber forming material or a blend of fiber forming materials including a polyvinyl alcohol fiber forming material.

[0315] In embodiments, the liquid acquisition layer may be provided between the absorbent core and the topsheet. In wearable embodiments, the liquid acquisition layer may be provided on the wearer-facing side of the absorbent core. In embodiments, the liquid acquisition layer may be provided between the absorbent core and the backsheet. In wearable embodiments, the liquid acquisition layer may be provided on the outer surface of the absorbent core. In embodiments, the liquid acquisition layer encases the absorbent core. The liquid acquisition layer may be a single sheet encasing the absorbent core or may be provided as two individual layers that are connected. Without intending to be bound by theory, it is believed that the inclusion of a liquid acquisition layer between the absorbent core and the backsheet or on the outer surface of the absorbent core advantageously prevents leakage of liquid from the absorbent article by providing additional liquid acquisition material that captures any runoff of liquid from the topsheet side and / or wearer side.

[0316] In general, the liquid acquisition layer may be in direct contact with the absorbent core, may include a space between the absorbent core and the liquid acquisition layer, or may include an intervening layer between the absorbent core and the liquid acquisition layer. In an embodiment, the liquid acquisition layer is in contact with the absorbent core. In an embodiment, the absorbent article includes an intervening layer disposed between the acquisition layer and the absorbent core. In an embodiment, the liquid acquisition layer is in contact with the absorbent core on the topsheet side / wearer side, and an intervening layer is disposed between the acquisition layer on the backsheet side / outer side and the absorbent core. In an embodiment, the liquid acquisition layer is in contact with the absorbent core on the backsheet side / outer side, and an intervening layer is disposed between the acquisition layer on the topsheet side / wearer side and the absorbent core. The intervening layer may be, for example, a second liquid-permeable layer or a liquid acquisition layer included to help and encourage the liquid to spread from the point of deposition to cover the entire area of ​​the absorbent core.

[0317] In an embodiment, the absorbent article includes a liquid acquisition layer that is a nonwoven web of the present disclosure. In an embodiment, the wearable absorbent article includes a liquid acquisition layer that is a nonwoven web of the present disclosure. In an embodiment, the absorbent article includes a liquid acquisition layer that is a nonwoven composite article of the present disclosure. In an embodiment, the wearable absorbent article includes a liquid acquisition layer that is a nonwoven composite article of the present disclosure. Dissolution and disintegration test (MSTM-205)

[0318] The nonwoven web, water-soluble film or laminate structure can be characterized or tested by dissolution time and disintegration time according to MonoSol Test Method 205 (MSTM 205), a method known in the art. See, for example, U.S. Patent No. 7,022,656. The description provided below refers to a nonwoven web, but is equally applicable to a water-soluble film or laminate structure. Equipment and materials include: 600mL beaker, A magnetic stirrer (Labline model number 1250 or equivalent), Magnetic stirring bar (5 cm), Thermometer (0~100℃±1℃), Mold, stainless steel (3.8cm x 3.2cm), Timer (0-300 seconds, second precision), Polaroid 35mm slide mount (or equivalent), MonoSol 35mm Slide Mount Holder (or equivalent), and Distilled water.

[0319] For each nonwoven web to be tested, three test specimens, 3.8 cm by 3.2 cm specimens, are cut from the nonwoven web sample. The specimens should be cut from areas of the web evenly spaced along the cross direction of the web. Each test specimen is then analyzed using the following procedure.

[0320] Each specimen is mounted on a separate 35 mm slide mound.

[0321] Fill a beaker with 500 mL of distilled water. Measure the water temperature with a thermometer and, if necessary, heat or cool the water to maintain the temperature at the temperature at which dissolution will be determined, e.g., 20° C. (about 68° F.).

[0322] Mark the height of the water column. Place a magnetic stirrer at the base of the holder. Place the beaker on the magnetic stirrer, add a magnetic stir bar to the beaker, start the stirrer, and adjust the stirring speed until a vortex is created that is approximately one-fifth the height of the water column. Mark the depth of the vortex.

[0323] Secure the 35 mm slide mount into the alligator clamp of the 35 mm slide mount holder with the long end of the slide mount parallel to the water surface. The depth adjustment of the holder should be set so that when dropped, the end of the clamp is 0.6 cm below the water surface. One of the short ends of the slide mount should be against the side of the beaker and the other end should be placed directly against the center of the stir bar so that the nonwoven web surface is perpendicular to the water flow.

[0324] In one motion, drop the clamped slide and clamp into the water and start the timer. Fracture occurs when the sample is damaged within the slide, e.g., a hole is created. Disintegration occurs when the nonwoven web separates and no sample material remains on the slide. Once all visible nonwoven web has detached from the slide mount, remove the slide from the water while continuing to monitor the solution for undissolved nonwoven web fragments. Dissolution occurs when all nonwoven web fragments are no longer visible and the solution is clear. For nonwoven samples in which the fibers are prepared from polyvinyl alcohol with a low degree of hydrolysis (e.g., about 65-88%), fracture and dissolution may occur simultaneously. If there is a difference of 5 seconds or longer between fracture and dissolution, the dissolution time is recorded independently of the fracture time.

[0325] Attenuation time can also be determined using MSTM-205. Attenuation of a nonwoven web occurs when some of the fibers that make up the nonwoven web dissolve while other fibers remain intact. Attenuation of the web occurs prior to web collapse. Attenuation is characterized by a decrease in opacity or an increase in transparency of the nonwoven web. The change from opaque to increasingly more transparent can be observed visually. During MSTM-205, the opacity / transparency of the nonwoven web is monitored after the fixed slide and clamp are dropped into the water. When no change in opacity / transparency is observed (i.e., the web becomes less opaque or less transparent), the time is recorded as the attenuation time.

[0326] Results should include: complete sample identification, individual and average disintegration and dissolution times, and the water temperature at which the sample was tested. Method for determining single fiber solubility

[0327] The solubility of a single fiber can be characterized by its water decomposition temperature. The fiber decomposition temperature can be determined as follows: A loading of 2 mg / dtex is loaded onto a fiber with a fixed length of 100 mm. The water temperature starts at 1.5° C. and then increases in increments of 1.5° C. every 2 minutes until the fiber decomposes. The temperature at which the fiber decomposes is recorded as the water decomposition temperature.

[0328] The solubility of a single fiber can also be characterized by the temperature of complete dissolution. The temperature of complete dissolution can be determined as follows: 0.2 g of fiber with a fixed length of 2 mm is added to 100 mL of water. The water temperature starts at 1.5° C. and then is increased in increments of 1.5° C. every 2 minutes until the fiber is completely dissolved. The sample is stirred at each temperature. The temperature at which the fiber is completely dissolved in less than 30 seconds is recorded as the temperature of complete dissolution. Diameter Test Method

[0329] The diameter of individual fibers or fibers within a nonwoven web is determined using a scanning electron microscope (SEM) or optical microscope and image analysis software. A magnification between 200 and 10,000 times is selected so that the fibers are suitably magnified for measurement. If an SEM is used, the sample is sputtered with gold or palladium compounds to avoid charging and vibration of the fibers in the electron beam. A manual procedure for determining fiber diameter is used from an image (on a monitor screen) taken with an SEM or optical microscope. The mouse and cursor tool are used to locate the end of a randomly selected fiber and then measure across its width (i.e. perpendicular to the fiber direction at that point) to the other end of the fiber. A scaled and calibrated image analysis tool gives an actual reading in microns to scale. For fibers within a nonwoven web, a few fibers are randomly selected across a sample of the nonwoven web using an SEM or optical microscope. At least two pieces of nonwoven web material are cut and tested in this manner. A total of at least 100 such measurements are made and all data is then recorded for statistical analysis. The recorded data is used to calculate the average (geometric mean), standard deviation and median fiber diameter of the fibers. Tensile Strength, Elastic Modulus and Elongation Tests

[0330] Nonwoven webs, water-soluble films or laminate structures that are characterized or tested for tensile strength according to the Tensile Strength (TS) Test, modulus (or tensile stress) according to the Modulus of Elasticity (MOD) Test, and elongation according to the Elongation Test are analyzed as follows. The description provided below refers to nonwoven webs, but is equally applicable to water-soluble films or laminate structures. The procedure includes the determination of tensile strength according to ASTM D 882 ("Standard Test Method for Tensile Properties of Thin Plastic Sheets") or equivalent, and the determination of modulus at 10% elongation. An INSTRON tensile testing device (Model 5544 Tensile Tester or equivalent) is used for the collection of nonwoven web data. A minimum of three test specimens, each cut with a reliable cutting tool that ensures dimensional stability and repeatability, are tested in the machine direction (MD) (if applicable) for each measurement. Testing is performed at a standard laboratory atmosphere of 23±2.0°C and 35±5% relative humidity. A 1-inch (2.54 cm) wide sample of the nonwoven web is prepared for tensile strength or modulus determination. The sample is then transferred to an INSTRON tensile tester to proceed with testing while minimizing exposure to a 35% relative humidity environment. The tensile tester is prepared according to the manufacturer's instructions, equipped with a 500N load cell, and calibrated. Precision grips and faces are installed (INSTRON grips with rubber-coated 25 mm wide, model number 2702-032 faces, or equivalent). The sample is fitted into the tensile tester and analyzed to determine 100% modulus (i.e., the stress required to achieve 100% film elongation), tensile strength (i.e., the stress required to break the film), and elongation % (sample length at break compared to the initial sample length). In general, the higher the sample elongation %, the better the processability characteristics of the nonwoven web (e.g., increased formability into packets or pouches). Determining Basis Weight

[0331] Basis weight is determined in accordance with ASTM D3776 / D3776M-09a(2017). Briefly, it should be at least 130 cm 2 A nonwoven fabric specimen with an area of ​​at least 130 cm2, taken from different positions on the sample 2Cut several smaller die cut specimens with a total area of ​​1.5 mm. Weigh the specimen(s) on a top-loading chemical balance with a resolution of ±0.001 g to determine the mass. Protect the balance from air currents and other disturbances using a draft shield. Fabric specimens may be weighed together. Calculate mass in ounces per square yard, ounces per linear yard, pound per linear yard, or grams per square meter to three significant figures. Determination of water vapor transmission rate

[0332] Moisture vapor transmission rate (MVTR) is determined according to MSTM-136. MVTR defines how much water transfers through a sample per day. The description provided below refers to nonwoven webs, but is equally applicable to water-soluble film or laminate structures.

[0333] Equipment and materials include: Permatran-W Model 3 / 34 (or equivalent), A high pressure gas cylinder of nitrogen (99.7% or higher), Regulator-Tee (Part Number 027-343), Main line supply regulator, HPLC grade water (or equivalent), 10cc syringe with Luerlok tip (part number 800-020), Powder-free gloves, High vacuum grease (part number 930-022), (2) Test cell, Cutting mold, Cutting board, A razor blade with a handle, and Cut resistant gloves.

[0334] Permatran W-Model 3 / 34 Preparation: Ensure that the nitrogen pressure level is above 300 psi, the carrier gas regulator-tee pressure reading is 29 psi (not to exceed 32 psi), and the main line supply regulator pressure is set to 35 psi. Check the water level by opening the instrument panel door and utilizing the humidifier. If the water level is low, fill a syringe with HPLC grade water and insert the luer attached to the syringe into the "fill port" of the reservoir. Open the "fill valve" by turning it counterclockwise 2-3 times, then push the plunger into the syringe to allow the water to enter the reservoir. Close the "fill valve" and remove the syringe. Note: Do not allow the water level to exceed the line marked adjacent to the reservoir.

[0335] SAMPLE PREPARATION AND TESTING: For each nonwoven web to be tested, take the sample web and lay it flat on a cutting board. Place a template on top of the web and use a handled razor blade to cut out the sample. Ensure that you are wearing cut resistant gloves when cutting out the sample. Set the sample aside. Grease the sealing surface of the top portion of the test cell with high vacuum grease. Place the film sample on top of the top portion of the test cell. NOTE: Orientation may be important. For homogenous materials, orientation is not important. For multi-layer laminate materials, place the multi-layer film or laminate with the barrier coating or laminate on top, towards the top of the cell. For example, a single-sided wax-coated PVOH web should be placed wax side up with the wax facing the carrier gas (nitrogen). Place the top portion of the test cell on top of the bottom portion of the test cell. Ensure that the test cell is clamped together with a good seal. Press the Cell Load / Unload button to open the cell tray. Grasp the front and back ends of the test cell and lower straight down. Close the cell tray completely by gently pushing straight down into the panel. Press the Cell Load / Unload button to clamp the cell. NOTE: You should hear a click. Repeat for the second sample.

[0336] After the sample is loaded and the instrument is ready, the test parameters must be set. Note: There are two types of test parameters: Cell parameters and Instrument parameters. Cell parameters are specific to each cell while Instrument parameters are common to all cells. Touch the "Test button" on the screen. Select "Tab A" under "Auto Test". Touch the "Cell tab". Enter the following by touching each bubble: ID, Area (cm 2 ), thickness (mils). Note: The area of ​​the mold is 50 cm 2 Repeat for "Tab B". Touch the "Instrument Tab". Enter the following by touching each bubble: Cell Temperature (°C) and Test Gas RH (%). Note: Ensure 100% RH is set to OFF. Cell Temperature can be set from a minimum of 10°C to a maximum of 40°C. Test Gas RH can be set from a minimum of 5% to 90%. If 100% RH is required a different method is required. Repeat for "Tab B". Once the test parameters are set, select "Start Selected" or "Start All" depending on the number of samples. Note: The indicator lights for each cell on the front panel should be green to indicate the start of the test. Surface resistivity measurement

[0337] The surface resistivity of nonwoven webs and films can be measured according to ASTM D257. Softness Grade

[0338] The hand feel of the nonwoven web or pouch of the present disclosure relates to the softness of the sample and can be evaluated using the relevant test method. The tester performing the softness evaluation uses clean hands to touch the sample in whatever individually selected manner or manner to determine the softness rating of the nonwoven web and article of the present disclosure in comparison with a control material comprising a nonwoven web made of polyvinyl alcohol homopolymer with 88% degree of hydrolysis and fibers with 2.2 dtex / 51 mm section, having a softness rating of 1 (softest), and a control material made of 75% polyvinyl alcohol homopolymer, with 88% degree of hydrolysis, fibers with 2.2 / 51 mm section and 25% PET fibers with 22 dtex / 38 mm, having a softness rating of 5 (roughest / coarsest). The hand panel is performed in a blinded study to ensure that the evaluators are not influenced by the knowledge of the sample name. The samples are graded from 1 to 5. Flushing test

[0339] The flushability of nonwoven webs and / or laminates of the present disclosure for septic or municipal wastewater treatment systems can be determined according to the modified INDA / EDANA flushable product certification standards as set forth below. The following tests refer to nonwoven web samples, but it is understood that the methods can also be used for laminate structures.

[0340] Equipment and materials include: Rocking Digital Platform Shaker, Two clear plastic 12 x 5 x 3.9 inch containers, 2 sieves (12.5mm opening), a dry nonwoven web sample, and Oven at 100°C.

[0341] Parameters include: Rocking platform set at 18 RPM and 11° tilt intervals; 1 litre of tap water per container, as well as The test duration is 30 minutes.

[0342] Test procedure: 1. Place two containers on a rocking platform. This method tests two samples simultaneously. 2. Measure 1 litre of tap water into a beaker and pour into one of the plastic containers. Repeat for the other container. Ensure the tap water in the container is at 15°C ± 1°C before the test begins. 3. Record the weight of the initial dry test sample (initial sample mass (g)) and the weight of the sieve (initial sieve mass (g)) and record separately. 4. Set the appropriate parameters on the digital locking platform. 5. Place each test sample into its corresponding container and immediately begin the agitation process (rock the platform). 6. Once the process is complete (after 30 minutes), take each container and pour through their corresponding sieve. Pour at a height of 10 cm above the sieve plate. 7. Rinse and sieve the container to ensure all remaining test sample is removed. 8. Place the sieve in a 100°C oven for 45 minutes to ensure all the water has evaporated. 9. Record the weight of the sieve and the remaining test sample together (total final mass (g)). 10. Calculate the total retained sample mass (final sample mass (g)): Final sample mass (g) = total final mass (g) - initial sieve mass (g) 11. Calculate the percent (%) decay: % disintegration = [1-(final sample mass (g) / initial sample mass (g))] x 100 12. Be sure to clean the sieve, dry it and reweigh it before starting the next test. 13. Repeat the test until N=3 replicates are completed for each particular test sample.

[0343] If the sample has a percent disintegration equal to or greater than at least 20%, the sample is sufficiently flushable for disposal by flushing into a septic or municipal wastewater treatment system. In embodiments, the nonwoven webs, laminates, and pouches of the present disclosure may have a percent disintegration of at least 20%, at least 30%, at least 35%, at least 40%, at least 45%, at least 50%, at least 55%, at least 60%, at least 65%, at least 70%, at least 75%, at least 80%, at least 85%, at least 90%, or at least 95% as measured by the Flushing Test. Liquid Release Test

[0344] FIG. 4 is a diagram of a wire frame cage (shown open at the top to better show the water-soluble pouch contained therein) for use in the liquid release tests described herein.

[0345] FIG. 5 shows an apparatus for conducting liquid release tests that includes a beaker mounted on a stand, a stand that holds a rod for lowering a cage into the beaker, and the rod can be secured by a collar having a set screw (not shown).

[0346] Water soluble nonwoven webs, films and / or pouches that are characterized by or tested for delayed solubility according to the Liquid Release Test are analyzed as follows using the following materials: A 2 L beaker and 1.2 L of deionized (DI) water, Water-soluble pouches to be tested; the pouches are preconditioned at 38°C for 2 weeks; for comparison of results, all nonwoven webs to be tested should have the same basis weight, and all films to be tested should have the same thickness, e.g., 88 μm or 76 μm; thermometer, Wire cage, and timer.

[0347] Prior to conducting the experiment, ensure that enough DI water is available to repeat the experiment five times and ensure that the wire cage and beaker are clean and dry.

[0348] The wire frame cage is a plastic coated wire cage (4 in. x 3.54 in. x 2.54 in.) or equivalent with blunt ends. The wire gauge should be approximately 1.25 mm and the wire should have an opening 0.5 in. (1.27 cm) square in size. An image of an example cage 28 including a test pouch 30 is shown in FIG. 4.

[0349] For the test setup, carefully place the water-soluble pouch into the cage while allowing free space for the pouch to move without scratching the pouch on the cage. Do not tie the pouch tightly to the wire cage, but make sure it is securely fastened and cannot move out of the cage. The orientation of the pouch within the cage should allow for natural buoyancy of the pouch, if present (i.e., position the pouch so that the floating surface faces upwards). If the pouch is symmetrical, the orientation of the pouch generally does not matter.

[0350] Next, fill a 2 L beaker with 1200 milliliters of 20° C. DI water.

[0351] The wire frame cage enclosing the pouch is then lowered into the water. Ensure that the cage is 1 inch (2.54 cm) from the bottom of the beaker. Make sure that all sides of the pouch are completely submerged. Ensure that the cage is stable and does not move, and start a timer as soon as the pouch is lowered into the water. The position of the cage relative to the water in the beaker can be adjusted and maintained by any suitable means, for example, by using a clamp fixed on the top of the beaker and a rod attached to the top of the cage. The clamp can engage the rod to fix the position of the cage, and the tension on the clamp can be reduced to allow the cage to be lowered into the water. Other means of frictional engagement can be used in place of the clamp, for example, a collar with a set screw as shown in FIG. 5 (set screw not shown). FIG. 5 shows a beaker resting on a stand that holds a rod for lowering the cage (not shown) into the beaker, and the rod can be held in a fixed vertical position, for example, by use of a collar with a set screw (not shown) that engages the rod by friction or by engagement with a hole (not shown) in the rod.

[0352] Release of liquid contents is defined as the first visual indication of liquid emerging from the submerged pouch. Determination of the degree of hydrolysis of fibers

[0353] Titration method. The degree of hydrolysis of fibers can be determined using titration. In particular, a known amount of polyvinyl alcohol fiber is dissolved in 200 mL of deionized water by stirring and heating the mixture at a temperature above 70 °C. Once all the PVOH is dissolved, the solution is cooled to room temperature. Once the solution is cooled, 4-5 drops of phenolphthalein indicator solution are added to the PVOH solution along with 20.0 mL of 0.5 N NaOH solution. The solution is mixed and allowed to stand at room temperature for a minimum of 2 hours. After this time, 20.0 mL of 0.5 N sulfuric acid is added to the solution and mixed. The solution is titrated with 0.1 N NaOH solution to the end point, which is the point at which the solution turns slightly pink and maintains this color for a minimum of 30 seconds without the solution returning to colorless. Using the measurements obtained in the previous procedure, determine the DH of PVOH from the following calculation:

number

[0354] FTIR method. FTIR can be used to determine the degree of hydrolysis of the outer portion of the fiber surface via attenuated total reflectance (ATR). The depth into the fiber that this method measures depends on the particular ATR instrument, and in particular the crystal used. Approximately 1730 cm -1 (ketone peak, due to residual acetate groups) and at approximately 1420 cm -1 By taking the ratio of the peak heights at (reference peak), the degree of hydrolysis of an unknown sample can be determined using an equation obtained by plotting the same ratio for PVOH resins against the known degree of hydrolysis.

[0355] Gradient Test Methods. The gradient of the degree of hydrolysis of fibers can be determined and quantified using cross-sectional X-ray photoelectron spectroscopy (XPS), depth XPS, NMR techniques, ultraviolet photoelectron spectroscopy (UPS), environmental SCM or Auger electron spectroscopy (AES or SAM).

[0356] For XPS analysis, the depth of the fiber that this method measures depends on the particular ion beam used during XPS analysis for the depth profile that determines the change in degree of hydrolysis as a function of cross section. By taking the ratio of the deconvoluted peaks at 287.6 eV and 288.8 eV, which represent the carboxyl and carbonyl groups of the acetate groups of the not fully hydrolyzed PVOH, to the deconvoluted peaks at 286.5 eV and 532.8 eV, which correspond to the hydroxyl groups of the PVOH, the degree of hydrolysis of an unknown sample can be determined using an equation obtained by plotting the same ratio for the PVOH resin against the known degree of hydrolysis. This method can be repeated between ion beam sputtering stages to obtain a complete depth profile of the PVOH fiber and the change in degree of hydrolysis across the cross section. The XPS method is described in Gilbert et al "Depth-profiling X-ray photoelectron spectroscopy (XPS) analysis of interlayer diffusion in polyelectrolyte multilayers" PNAS, vol. 110, no. 17, 6651-6656 (2013) (available at https: / / www.pnas.org / content / pnas / 1 / 10 / 17 / 6651.full.pdf) and European Polymer Journal 126 (2020) 109544, the entireties of which are incorporated herein by reference.

[0357] The AES method is described in ASTM E984-12, which is incorporated herein by reference in its entirety. Fiber shrinkage (%) measurement

[0358] Using the MonoSol standard operating procedure, measure the shrinkage of the fibers along the longitudinal axis of the fibers when in contact with water at temperatures ranging from 10 °C to 23 °C.

[0359] Materials include: A fiber sample (approximately 3 grams), 500mL beaker, Cold deionized water (keep in the fridge), Deionized water, paper clip, Alligator clamp (solubility stand), Stir plate, and timer.

[0360] The samples are prepared by the following steps: Obtain a small bundle of untangled fibers (approximately weighing 0.013 grams (g) to 0.015 g) such that the small bundle of fibers is securely held with a paper clip and alligator clamp; Take a paper clip and pull one end of the fiber through the cross section of the paper clip; This is done for each fiber that needs to be tested with N=3 replicates at each test temperature, eg, 23°C and 10°C.

[0361] The test apparatus as shown in FIG. 8 is set up as follows: Fill a 500 mL beaker with 400 mL of water at each temperature, and check the water temperature using a temperature probe before and during the test; Tape the ruler to the top of the alligator clamp so that the ruler hangs parallel to the clamp; The beaker is placed on a stir plate, the solubility stand is placed next to the stir plate, and a ruler is submerged in the beaker so that the fiber length can be read.

[0362] The test procedure includes the following steps: Attach the free end of the fiber, secured with a paper clip, to an alligator clamp; Submerge the test sample in the beaker and place it next to the ruler; Start the timer and record the initial length of the fiber. The test sample fiber length is from the end of the alligator ...

Claims

1. A fiber comprising: a polymer comprising at least one polyvinyl alcohol copolymer which is a copolymer of vinyl acetate and vinyl alcohol; A fiber, wherein the fiber has a higher degree of hydrolysis at an outer surface of the fiber compared to an interior of the fiber, the degree of hydrolysis from the interior of the fiber to the outer surface of the fiber forming a gradient.

2. 10. The fiber of claim 1, wherein a cross-section of the fiber has a gradient of increasing degree of hydrolysis of the polymer from the interior of the fiber to the outer surface of the fiber.

3. The fiber of claim 1 , wherein the polyvinyl alcohol copolymer comprises an anionically modified copolymer.

4. The fiber of claim 3 , wherein the anionically modified copolymer comprises a carboxylate, a sulfonate, or a combination thereof.

5. The fiber of claim 1 further comprising an additional polymer.

6. 6. The fiber of claim 5, wherein the additional polymer is selected from the group consisting of polyacrylates, water soluble acrylate copolymers, polyvinylpyrrolidone, polyethyleneimine, pullulan, guar gum, acacia gum, xanthan gum, carrageenan, starch, modified starch, polyalkylene oxides, polyacrylamides, polyacrylic acids, cellulose, cellulose ethers, cellulose esters, cellulose amides, polycarboxylic acids, polyamino acids, polyamides, gelatin, dextrins, copolymers of the foregoing, and combinations of any of the foregoing additional polymers or copolymers.

7. The fiber described in claim 1, wherein the degree of hydrolysis of the interior of the fiber is 79% to 96% and the degree of hydrolysis of the outer surface of the fiber is 88% to 100%.

8. The fiber described in claim 1, wherein the degree of hydrolysis of the interior of the fiber is 79% to 92% and the degree of hydrolysis of the outer surface of the fiber is 88% to 96%.

9. 10. The fiber of claim 1, wherein the fiber has a dissolution time in water at 23°C of less than 200 seconds.

10. 10. The fiber of claim 1, wherein the fiber has a shrinkage percentage along the longitudinal axis of the fiber when contacted with water at a temperature of from 10°C to 23°C of from 20% to 70%.

11. The polymer in the interior of the fiber has a glass transition temperature (T g ) and the polymer in the outer surface of the fiber has a T g The fiber of claim 1 having

12. A nonwoven web comprising the fibers of claim 1.

13. A multi-layer nonwoven web comprising a first layer comprising the nonwoven web of claim 12.

14. A pouch comprising the nonwoven web of claim 13 in the form of a pouch defining an interior pouch volume.

15. A sealing article comprising the nonwoven web of claim 12.

16. A flushable article comprising the nonwoven web of claim 12.

17. an absorbent core having a wearer side and an outer side; and A liquid acquisition layer comprising the nonwoven web of claim 12.

1. A wearable absorbent article comprising:

Citation Information

Patent Citations

  • Water-soluble polyvinyl alcohol binder fiber and method for heating and press-adhering the fiber

    JP1995173724A